Effects of surgical implantation of electronic tags in fishes: a review and meta-analysis - Mitchell B. Shorgan; Graham D. Raby; Amber L. Fedus; Bradley E. Howell; Laura S. E. Haniford; Leah C. Howitt; Natalie V. Klinard; Jordan K. Matley; Jacob W. Brownscombe; Steven J. Cooke; Aaron T. Fisk (Reviews in Fish Biology and Fisheries, 2026)

Sediment response to stream restoration in an agricultural watershed - John W. Clune; Gregory B. Noe; Matthew Cashman; Jessica D. DeWitt; Joseph M. Bell; Mitchell R. Weaver; James E. Colgin; Thomas R. Doody; Eliza L. Gross; Victor S. Cortes (Ecological Engineering, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Subclinical infection with Anaplasma phagocytophilum and gastrointestinal nematodes results in reduced weight gain in grazing weaned lambs - Jade M. Duncan; Mara S. Rocchi; Alison Stephen; Adam D. Hayward; Madeleine Maley; Heather McDougall; Sharon Brown; Leigh Andrews; Gillian Mitchell; Fiona Kenyon (The Veterinary Journal, 2026)

The microbial communities of a tomato crop grown in Veggie under different lighting regimes on the International Space Station - Cory J. Spern; Mary E. Hummerick; Christina LM Khodadad; Cristiana J. Morales; Anirudha R. Dixit; Lashelle E. Spencer; Cary A. Mitchell; Robert C. Morrow; Raymond M. Wheeler; Gioia D. Massa (Life Sciences in Space Research, 2026)

103 Germinal vesicle to metaphase II: Transcriptomic dynamics of single-equine oocytes following holding and in vitro maturation - S.B. Cousseau; V. Medina; C.R. Neto; M.S. Lindley; S. Loux; M.C. Azevedo; D. Rosseti; M. Mitchell; C.R.F. Pinto (Journal of Equine Veterinary Science, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Thermal history and behavioural plasticity shape reef fish tolerance to marine heatwaves - Angus Mitchell; Sean D. Connell; Ben P. Harvey; Sylvain Agostini; Jeffrey Jolly; Guinther Mitushasi; Timothy Ravasi; David J. Booth; Ivan Nagelkerken (Coral Reefs, 2026)
Marine heatwaves are becoming more frequent and intense, driving mass fish mortalities and reshaping marine ecosystems, yet the capacity of fishes to tolerate heatwaves remains unclear. We quantified physiological condition and behavioural responses of juvenile warm-water ( Abudefduf vaigiensis ) and cool-water ( Microcanthus strigatus ) fishes from three natural climate analogues—an ambient temperate reef, an ocean warming analogue, and a combined warming and extreme acidification analogue—before and during the 2023 global marine heatwave, and under a + 3 °C simulated heatwave in the laboratory. In the laboratory, warm-water fish from the warm reef began the experiment in leaner condition than cool reef fish but increased their bite rates under heatwave conditions, compensating for elevated metabolic demand and maintaining body condition. Cool-water fish showed no behavioural adjustment to the heatwave, and body condition diverged by reef origin: cool reef fish lost weight across all treatments while warm- and extreme-origin fish maintained condition, suggesting tolerance was conferred by prior thermal history rather than acute behavioural responses. In the field, warm-water fish were leaner and had lower protein content during the 2023 heatwave than before it, while cool-water fish from the extreme reef had lower body condition than those from the cool reef prior to the heatwave. Our findings suggest that behavioural plasticity can facilitate warm-water fish tolerance to heatwaves at their cold leading edges, while thermal history supports heatwave tolerance in cool-water fish within their core ranges. Populations inhabiting naturally extreme climate analogues may therefore harbour pre-adapted, climate-resilient fish in a future ocean.

Integrated modelling reveals widespread distribution of invasive wild pigs across Australia - Matthew W. Rees; David J. Mitchell; Katherina Ng; Sandra K. Parsons; Kirstin M. Proft; Scott D. Foster; David Peel; Zachary Amir; Tom Bruce; Matthew S. Luskin; Jens G. Froese (Biological Conservation, 2026)

Environmental Drivers of Recruitment Variability in Narrow‐Barred Spanish Mackerel Scomberomorus commerson Lacépède, 1800 - Susannah M. Leahy; Joanne Langstreth; Rik C. Buckworth; Peri Subritzky; Olivia J. Whybird; Sam M. Williams; Lucas I. Sumpter; Jonathan D. Mitchell (Fisheries Oceanography, 2026)
Understanding the effects of environmental conditions on fisheries resources is crucial for guiding the effective assessment and management of fish stocks. Previously assessed as depleted, the narrow‐barred Spanish mackerel fishery on the east coast of Queensland, Australia, is under management intervention to rebuild the stock. In this study, we use long‐term age composition data to reconstruct 24 years of historic year class strength and explore a broad range of potential environmental influences on recruitment variability in the fishery. Year class strength was extremely well captured (76%–84% deviance explained) by generalised additive models containing just four environmental indices. Recurring key environmental indices in top models included environmental conditions prior to spawning (large scouring flood events during the wet season before spawning and cool winter sea surface temperature immediately prior to spawning), during spawning (unseasonal flooding near the spawning grounds), during larval dispersal and proxies for food availability for juvenile Spanish mackerel. These results have since been used to hindcast recruitment variability in the fishery prior to the collection of the age‐composition data to better understand historic fluctuations in the fishery, and can also be incorporated into management strategies for rebuilding the stock.

Drivers of fine-scale space use and grazing patterns of juvenile parrotfish on western Atlantic reefs - David P. Kochan; Melanie M. Esch; Robert Y. Fidler; Matthew D. Mitchell; Manuel González-Rivero; Alastair R. Harborne (Coral Reefs, 2026)

Widespread reproductive deficits in Chesapeake Bay ospreys - Bryan D. Watts; Chance Hines; Mitchell A. Byrd; Reese F. Lukei; Barton J. Paxton; Laura Duval; Keriann E. Spiewak; Greg D. Kearns; Daniel D. Day; Barnett A. Rattner (Frontiers in Marine Science, 2026)
Introduction Ospreys ( Pandion haliaetus ) are well-known sentinels of aquatic ecosystem health and are indicators of both environmental contaminants and fish stocks. The Chesapeake Bay supports one of the largest osprey breeding populations in the world, but recent studies have documented declining reproductive performance and increasing food stress in some portions of the estuary. Methods We monitored osprey nests (N = 571) throughout the Chesapeake Bay during the 2024 breeding season and compared breeding metrics between high-salinity (>10 parts per thousand [ppt]) and low-salinity (<5 ppt) study areas. We also compared contemporary breeding performance within four high-salinity sites to historical data collected during the 1980s. Results Salinity was strongly associated with breeding performance and the likelihood that pairs achieved productivity levels required for population maintenance. All high-salinity study areas functioned as demographic sinks, whereas low-salinity areas functioned as demographic sources. Breeding metrics including the proportion of pairs breeding, clutch size, nesting failure, brood reduction, and nestling loss all suggested greater food stress within high-salinity areas. Temporal comparisons documented substantial declines in reproductive performance between the 1980s and 2024 within high-salinity study sites. High-salinity sites during the 1980s exhibited breeding performance comparable to low-salinity sites in 2024. Discussion Although several factors may influence osprey productivity within the Chesapeake Bay, we suggest that reduced availability of Atlantic menhaden ( Brevoortia tyrannus ) is a primary driver of poor reproductive performance within high-salinity waters.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Crop mixtures: yield responses to climate and management and impacts on seed and soil chemical composition in a Scottish-based study - R. Brooker; R. J. Pakeman; R. L. Hewison; C. Mitchell; A. C. Newton; R. Neilson; S. Raubach; P. D. Shaw; S. Verrall; A. J. Karley (Plant and Soil, 2026)
Introduction Crop mixtures can be an important part of the toolkit for maintaining crop production while addressing the climate and nature crises. However, uncertainties around some issues may prevent their uptake. Research question This study addressed several uncertainties, specifically the response of mixture yields to climate and management, and the impacts of mixed cropping on seed chemical composition, soil carbon and nutrients. Materials and methods We undertook 32 intercropping trials between 2020 and 2022 on both commercial and research farms. These varied in design, management and crop combinations, with mixture choice often determined by farmers. We assessed multiple responses including yield, weed cover, and seed and soil chemical composition. Results and conclusions When compared to monocultures, yield gains from growing a crop mixture were roughly 20% based on Crop Performance Ratio (CPR). We found limited impacts of mixture diversity and composition on seed chemical composition, influences of management on weed control, and enhanced crop mixture performance under cooler conditions with lower rainfall. We also found varying mixture performance depending on mixture composition. Importantly, irrespective of management, climate, and composition effects, crop mixtures always performed at least as well as expectations based on monocultures. Even without further refinement from, for example, targeted breeding, crop mixtures provide reliable crops without yield losses or (for parameters tested) substantial changes in seed chemistry. However, detected reductions in organic matter in upper soil layers indicate a priority for future research is understanding crop mixture impacts on soil carbon dynamics in both shallow and deep soils.

Reconstructing human–animal interactions via multiproxy analysis of dog paleofeces from the medieval Central Balkans - Nemanja Marković; Freya Steinhagen; Elena Marinova; Samantha Brown; Susan M. Mentzer; Christopher E. Miller; Maria A. Spyrou; Víctor Roces; Ella Reiter; Dejan Bulić; Mirjana Roksandić; Piers D. Mitchell; et al. (Archaeological and Anthropological Sciences, 2026)

Warming influences nutrient removal in mesocosms across different substrates - Abagael N. Pruitt; Jennifer L. Tank; Caroline G. T. Anscombe; Mitchell J. Liddick; Elise D. Snyder; Emma M. Thrift‐Cahall; Erik M. Curtis; Anna E. S. Vincent (Limnology and Oceanography, 2026)
Climate change is increasing stream temperatures globally, likely impacting stream ecosystem processes. We conducted a stream warming experiment at the Notre Dame Experimental Mesocosm Facility using N = 24 recirculating mesocosms to examine the effect of warming on biofilm colonization of organic and inorganic substrata and rates of nutrient removal. We conducted an experiment with three temperature treatments (20°C, 23°C, and 26°C) in mesocosms containing either decomposing sugar maple ( Acer saccharum ) leaves or cobble substrate under shaded and unshaded conditions, respectively. We measured biofilm chlorophyll a (Chl a ) on cobble, community respiration on leaf disks, and removal of ammonium (NH 4 + ‐N) and soluble reactive phosphorus weekly for 21 d. Warming did not significantly alter Chl a or community respiration (generalized linear mixed model, p > 0.05). For nutrients, however, warming increased NH 4 + ‐N removal for both leaves and cobble. For cobble, NH 4 + ‐N removal was higher at 26°C (mean = 3.5 h −1 with a 75% credible interval of [3.1, 4.0]) compared to 20°C (2.3 h −1 [1.9, 2.7]; Bayesian regression model). For leaves, NH 4 + ‐N removal was also higher at 26°C (1.1 h −1 [1.0, 1.2]) compared to 20°C (0.5 h −1 [0.4, 0.6]). In contrast, warming only altered soluble reactive phosphorus removal for cobble; removal was higher at 26°C at 1.9 h −1 [1.7, 2.2] compared to 20°C (1.1 h −1 [0.8, 1.3]). Warming did not alter soluble reactive phosphorus removal for leaves. We show that warming‐induced changes in nutrient removal are mediated by substrate, and that NH 4 + ‐N removal may be more sensitive to elevated temperatures than soluble reactive phosphorus removal, with implications for altered nutrient cycling under a warmer future.

Marine invertebrates and fishes exhibit inconsistent body size responses to ocean acidification - Mary E. Hart; Sean D. Connell; Angus Mitchell; Ben P. Harvey; Sylvain Agostini; Joshua M. Heitzman; Ivan Nagelkerken (Limnology and Oceanography, 2026)
Body size is a fundamental characteristic of all living organisms that determines physiological functions and life‐history traits. Ecological theory predicts that ocean acidification can cause body size reductions, confirmed by several studies reporting miniaturization in ectotherms. Based on this prediction, we would expect a broad suite of species to show similar plastic body‐size responses to elevated CO 2 . Using four natural climate change analogues of ocean acidification across the northern and southern hemispheres, we quantified body size alterations across 18 marine invertebrate and fish taxa to test for climate‐driven miniaturization. Only three species consistently showed body‐size reductions under ocean acidification: one urchin and two fish species. In contrast, 15 other species, ranging from highly calcified to non‐calcified, displayed unchanged or increased body sizes or inconsistent miniaturization. If body‐size miniaturization responses were consistently reproducible across taxa we would have observed it more frequently, suggesting that species responses to ocean acidification are more variable than previously thought and likely vary depending on a species' physiology and life history. Thus, rather than entire communities undergoing miniaturization, species are likely to display a spectrum of responses, with some exhibiting size reductions, others demonstrating physiological resistance to elevated CO 2 , and others potentially benefiting from the indirect effects of ocean acidification.

Non-Candida fungal cholecystitis - an uncommon occurrence even in the right host - Mitchell G. Dumais; Mary M. Czech; Mustafa A. Hyder; Rachel R. Lee; Juan C. Gea-Banacloche; Christopher G. Kanakry; Sun A. Kim; Bindu Adhikari; Matthew D. Surette; Adrian M. Zelazny; Amir Seyedmousavi; Jennifer M. Cuellar-Rodriguez (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Invasive fungal infections (IFI) are a significant cause of morbidity and mortality in hematologic malignancy patients and hematopoietic cell transplant (HCT) recipients. Mold cholecystitis has rarely been described. We present a case of disseminated Lomentospora prolificans , that had recrudescence of symptoms with acute cholecystitis. Treatment included a temporary cholecystostomy and administration of the novel antifungal fosmanogepix. At 6 weeks post-HCT, the patient underwent cholecystectomy and completed a course of fosmanogepix, leading to resolution of her infection. Here we review the published literature on non- Candida fungal cholecystitis, underlying risk factors and treatment.

Three-dimensional amplification of storm-driven beach erosion: Implications for setback lines at Narrabeen-Collaroy Beach, Australia - Mitchell D. Harley; Ian R. Coghlan; James T. Carley; David Taylor (Coastal Engineering, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Millennial-scale fire and climate dynamics in the world's largest tropical wetland show emerging fire threat to flooded ecosystems - Bronwen S. Whitney; Danilo M. Neves; Nicholas J.D. Loughlin; Carlos D'Apolito; Carla Coblinski Tavares; Emma P. Hocking; Francis E. Mayle; Mitchell J. Power; Aguinaldo Silva; Mario L. Assine (Global and Planetary Change, 2026)

OnabotulinumtoxinA Alters Pro- and Anti-Inflammatory Dural Macrophage Response to CSD in Female Mice - Aaron J. Schain; Diego Delgado Fajardo; Andrew M. Strassman; Subhash Kulkarni; Ron S. Broide; Amy D. Brideau-Andersen; Aubrey Manack Adams; Mitchell F. Brin; Rami Burstein (Toxicon, 2026)

OnabotulinumtoxinA Inhibits Dysregulation of Descending Pain Modulation Following Mild Traumatic Brain Injury in Mice - Robson C. Lillo Vizin; Caroline M. Kopruszinski; Janice N. Oyarzo; David W. Dodick; Ron S. Broide; Amy D. Brideau-Andersen; Mitchell F. Brin; Trent Anderson; Edita Navratilova; Frank Porreca (Toxicon, 2026)

Pharmacological Differences Between Botulinum Toxin Type A 900 kDa Complex and 150 kDa Neurotoxin Protein - Ron S. Broide; Greg Nicholson; Michelle Cano; Dave Canty; Terry Boodhoo; Amy D. Brideau-Andersen; Mitchell F. Brin (Toxicon, 2026)

Circular metrics as instruments for quantifying sustainability - John D. Atkinson; Thomas Elliot; Mitchell P. Jones; Julian Kirchherr; Ana T. Lima; Mugur Schuppler; Dominik Wiedenhofer (Resources, Conservation and Recycling, 2026)

Evaluation of passive fire protection installation methods: Full-scale LNG fire testing of 3-sided and 4-sided coated structure beams - Mitchell Huffman; Chi-Yang Li; Jazmine Aiya D. Marquez; Zihao Wang; Bryant Hendrickson; Thomas Butts; Filippo Gavelli; Qingsheng Wang (Process Safety and Environmental Protection, 2026)

Pre- and postnatal exposure to PM2.5 and NO2 and blood pressure in children: Results from the ECHO Cohort - Yu Ni; Andrew Law; Xingyu Gao; Adam A. Szpiro; Christine T. Loftus; Miranda Jones; Logan C. Dearborn; Marnie F. Hazlehurst; Allison R. Sherris; Sindana Ilango; Kaja Z. LeWinn; Nicole R. Bush; et al. (Environmental Research, 2026)

Gestational fine particulate matter exposure and perinatal outcomes in the ECHO cohort: Associations across pregnancy windows - Adaeze W. Nzegwu; Aisha S. Dickerson; Kristin Miller; Adam Szpiro; Alison E. Hipwell; Amy J. Elliot; Amy M. Padula; Anne L. Dunlop; Anne P. Starling; Assiamira Ferrara; Carrie V. Breton; Christine T. Loftus; et al. (Environmental Research, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Regional dynamics of agrivoltaics adoption: Stakeholder perceptions and barriers in Maryland, USA - Jennifer D. Morash; Mitchell Pavao-Zuckerman (Energy Policy, 2026)

Marine Heatwaves, Ocean Warming and Acidification Reshape Reef Fish Gut Microbiomes - Angus Mitchell; Chloe Hayes; Callum J. Hudson; Sean D. Connell; Ben P. Harvey; Sylvain Agostini; Jeffrey Jolly; Timothy Ravasi; David J. Booth; Ivan Nagelkerken (Molecular Ecology, 2026)
Extreme climatic events and gradual climate change are increasingly anticipated to interact and reshape ecological communities. However, the combined effects of ocean warming, acidification and marine heatwaves on host‐associated microbial communities and their potential role in host adaptation remain poorly understood. Here, we assessed shifts in gut microbiome communities and their associations with physiological performance in one tropical ( Abudefduf vaigiensis ) and one subtropical ( Microcanthus strigatus ) reef fish species, across three temperate reefs representing natural analogues of climate change: a present‐day baseline (‘cool reef’), a chronically warmed reef (‘warm reef’) and a reef experiencing combined warming and extreme acidification (‘extreme reef’). We also examined gut microbiome changes in A. vaigiensis before and during a severe marine heatwave. A. vaigiensis had lower gut microbiome evenness and diversity at the warm (43% and 44% decrease, respectively) and extreme (38% and 31% decrease) reefs compared to the cool reef, and its gut microbiome community shifted at the extreme reef with a 122% increase in abundance of opportunistic bacteria Vibrio . A. vaigiensis also had lower gut microbiome richness at the warm (42% decrease) and extreme (52% decrease) reefs during the heatwave compared to pre‐heatwave individuals. In contrast, M. strigatus showed higher microbiome evenness (99% increase) and diversity (98% increase) at the warm reef compared to the cool reef; however, these gains were lost at the extreme reef, with microbiome diversity and evenness returning to cool reef levels. Microbiome changes in both species were generally not associated with their physiological performance (protein content, oxidative stress, antioxidant capacity or body condition). Our findings suggest that marine heatwaves, ocean warming and acidification can reshape reef fish gut microbiomes, driving simplification in Abudefduf vaigiensis but distinct restructuring in Microcanthus strigatus . We conclude that climate‐driven microbiome reshuffling may alter host–microbiome relationships and functions in fishes in a future ocean.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Metacommunity structural changes of Antarctic benthic invertebrates over the late Maastrichtian - Tasnuva Ming Khan; Rowan J. Whittle; James D. Witts; Huw J. Griffiths; Andrea Manica; Emily G. Mitchell (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

Range‐extending fish become competitive dominants under ocean warming but not heatwaves or acidification - Angus Mitchell; Ericka O. C. Coni; Sean D. Connell; David J. Booth; Ben P. Harvey; Sylvain Agostini; Timothy Ravasi; Ivan Nagelkerken (Ecology, 2026)
Ocean warming is driving species range extensions into cooler regions. The direct physiological influence of warming on species performance can accelerate such extensions into novel ecosystems; however, indirect effects of invader–resident interactions in cooler regions may counter these positive effects. Here, we examined the foraging performance and densities of competing warm‐water and cool‐water fishes across a latitudinal temperature gradient spanning 1500 km from tropical to temperate reefs subjected to rapid ocean warming in the southern hemisphere, and across natural analogs of temperate, tropicalized, and acidified reef localities in the northern hemisphere, and during a severe marine heatwave at a temperate reef. While current levels of ocean warming have allowed the warm‐water fish to extend their ranges into temperate ecosystems at both hemispheres, their foraging performance was reduced at both the cold‐ and warm‐temperate reefs compared to the (sub)tropical reefs. However, at the (warmer) tropicalized reef, the warm‐water fish had higher foraging performance and maintained densities, even under extreme pH reduction, compared to the temperate reef. In contrast, the cool‐water species struggled at the warmer tropicalized and extreme reefs with reduced foraging performance and lower population densities compared to the temperate reef. Contrastingly, the severe heatwave experienced at the temperate reef did not alter the foraging behaviors of either species. We suggest that ocean warming boosts the foraging performance of the range‐extending warm‐water fish and impairs that of their cool‐water competitor at temperate reefs, irrespective of acidification and heatwaves, leading to a shift in dominance hierarchies on temperate reefs. We conclude that warming‐driven increases in foraging performance of the warm‐water species may alleviate foraging limitations and enhance its establishment at its leading range edges under climate change, to the detriment of its cool‐water competitors.

Tidal marsh species mapping using commercial satellite imagery for enhanced coastal management in Chesapeake Bay - Megan M. Coffer; Rebecca Trinh; Molly Mitchell; Kory Angstadt; David Stanhope; Zhonghui Lv; Karinna Nunez; Nicole D. Bartlett; Daniel Wiltsie; Sully Sullivan; Blake A. Schaeffer (Remote Sensing Applications: Society and Environment, 2026)

Minimizing use of nonhuman primates to inform risk to fertility and of adverse pregnancy outcomes with pharmaceuticals - Christopher J. Bowman; Ann Baker; Diann L. Blanset; Kimberly C. Brannen; Gary J. Chellman; Brian Enright; Wendy Halpern; Bethany R. Hannas; Kazushige Maki; Fumito Mikashima; Shermaine Mitchell-Ryan; Eve Mylchreest; et al. (Regulatory Toxicology and Pharmacology, 2026)

Hybrid modeling for daily streamflow forecasting: A study over the contiguous United States - Fanzhang Zeng; Zhao Zhao; Natalie P. Memarsadeghi; Charles J. McKnight; Xudong Wang; Sarah Miele; Mayank Chadha; Dania Ammar; Yichao Zeng; Magdalena Asborno; Kenneth Mitchell; Guga Gugaratshan; et al. (Journal of Hydrology, 2026)

Hippocampal Bioenergetics and Metabolic Profiling Identifies Fatty Acid Oxidation as a Potential Therapeutic Target in Traumatic Brain Injury - Di Zhou; Mengxuan Shi; Mitchell D. Kilgore; Yuwen Xiu; Yingjie Wang; Danni Wang; Thin Yadanar Sein; Charles Vidoudez; Amin Iskender; Gaby A. Moyano; Lauren M. Dumont; Yinghua Jiang; et al. (Molecular Neurobiology, 2026)
Traumatic brain injury (TBI) causes lasting neurological impairments, particularly learning and memory deficits associated with hippocampal damage. Emerging evidence suggests that hippocampal vulnerability may be linked to bioenergetic dysfunction, though its role remains poorly defined. A deeper understanding of post-TBI metabolic disturbances and their association with pathological outcomes could reveal novel therapeutic targets. In this study, we conducted functional bioenergetic assessments and multi-omics analyses on hippocampal slices using a mouse controlled cortical impact model of TBI. Seahorse analysis revealed a significant reduction in mitochondrial oxidative phosphorylation in dentate gyrus (DG) slices at day 1 (acute phase), which recovered by day 7 (subacute phase) post-TBI. Metabolomic profiling revealed acute impairments in purine nucleotide, glucose, amino acid, and fatty acid metabolism, most of which normalized by day 7. Isotope tracing indicated enhanced octanoate-derived fatty acid oxidation (FAO) in DG slices at day 7 post-TBI. Proteomics confirmed suppressed purine metabolism at day 1 across hippocampal subregions, while FAO remained preserved at day 1 and became significantly elevated by day 7, suggesting a compensatory metabolic adaptation. Administration of sodium octanoate, a medium-chain fatty acid, at 1 h post-TBI enhanced mitochondrial respiration at 24 h, reduced microglial counts at 48 h, and attenuated neurodegeneration by day 3. These findings identify FAO enhancement as a promising metabolic strategy to restore hippocampal bioenergetics and promote neuroprotection following TBI.

The Peripheral Epigenome Predicts White Matter Volume Contingent on Developmental Stage: An ECHO Study - Taena Hanson; Sophie Spencer; Samantha A. Harker; Fatoumata Barry; Jennifer Beauchemin; B. Blair Braden; Phoebe Burton; Viren D’sa; Daphne Koinis-Mitchell; Sarah E. Mennenga; Sean C. L. Deoni; Candace R. Lewis (Molecular Neurobiology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Mapping blue carbon ecosystems from Earth observations at a national scale for Papua New Guinea - Christopher J. Owers; Richard M. Lucas; Carole Planque; Daniel Clewley; Matt Paget; Chloe Fitzpatrick; Annette Burke; Freddie Alei; Mitchell B. Lyons; Andrew D. L. Steven (Frontiers in Marine Science, 2025)
National maps are essential to support the conservation, restoration, and sustainable management of blue carbon ecosystems (BCE). This is particularly important for nations in the Indo-Pacific region, including Papua New Guinea (PNG), that aspire to integrate these ecosystems into their nationally determined contributions (NDCs) for ecosystem accounting. This study focussed on mapping the extent of BCEs in PNG using Earth observation data for the year 2020 and reporting on biomass and carbon storage services. Land cover categories were generated using the Living Earth framework for the 15 coastal provinces of PNG. The total BCE area in PNG (14,353 km²) comprised 30% mangrove, 65% lowland peat swamp forest, 3% saltmarsh, and 2% seagrass. Lowland peat swamp forests contribute the greatest biomass (137.94 ± 67.10 Tg) followed by mangroves (71.79 ± 27.16 Tg), with a total biomass of 212.99 ± 95.89 Tg. Across PNG, a total of 710.46 ± 362.75 Tg C were estimated for belowground carbon of BCEs (reporting to 1 m depth), almost seven times more than that of aboveground carbon (102.14 ± 45.97 Tg C). This study highlights the need for a consistent and standardised framework for mapping BCEs, which can support coordinated management of coastal landscapes across provinces that contribute to national policies and NDC reporting. This case study can be used as a demonstration for other nations where similar opportunities and challenges may exist for mapping BCE using Earth observations, with a framework that can be compared and adapted to user requirements.

Influence of computed tomography X-ray doses on maize root and shoot development in A controlled environment - Libo Zhang; Michael J. Gosney; Sungchan Oh; Chris D. Hoagland; Mitchell R. Tuinstra; Yang Yang (Computers and Electronics in Agriculture, 2025)

Detection of Cryptosporidium spp. and Giardia duodenalis DNA in wild deer in Scotland - Paul M. Bartley; Clare M. Hamilton; Jackie Thomson; Ross Bacchetti; Mairi C. Mitchell; Tom N. McNeilly; Renata Pimentel Bandeira de Melo; Adam D. Hayward; Frank Katzer; Beth Wells (Veterinary Parasitology, 2025)

A New Genus of Anacardiaceae from Madagascar - John D. Mitchell; Douglas C. Daly; Armand Randrianasolo (Brittonia, 2025)

Multi-site Milling Strategy Reveals Significant Variation in Biomass Composition of Switchgrass (Panicum virgatum) Grown at Ten Locations - David J. Thomas; Jason Bonnette; Steven D. Masterson; Robert B. Mitchell; Thomas E. Juenger; Laura E. Bartley (BioEnergy Research, 2025)

A standardized nontargeted metabolomics method for cross-laboratory comparison of food profiles - Melanie T. Odenkirk; Cole Michel; Katrina A. Doenges; Katrina L. Leaptrot; Stacy D. Sherrod; Jody C. May; Margaret L. Read; Jacqueline M. Chaparro; Nathan Montgomery; Sarah Brinkley; Arpana Vaniya; Susan B. Mitchell; et al. (Food Chemistry, 2025)

SLC39A14 is Required for Iron Loading of the Anterior Pituitary of Mice with Genetic Iron Overload - Joseph Olivera; Shintaro Hoyjo; Toshiyuki Fukada; Mitchell D. Knutson (Biological Trace Element Research, 2025)

Predator exposure and gene flow as tools to preserve antipredator traits in havened populations: behavioural observations of quenda - Natasha D. Harrison; Nicola J. Mitchell; Harriet Mills; Anna J.M. Hopkins; Ben L. Phillips (Animal Behaviour, 2025)

A modified-live Mannheimia haemolytica expressing Mycoplasma bovis EFTu and Hsp70 induced systemic and mucosal antibody responses in American bison but failed to fully protect against Mycoplasma bovis challenge. - Bryan S. Kaplan; Rohana P. Dassanayake; Bradley O. Chriswell; William D. Boatwright; Steven C. Olsen; Mitchell V. Palmer; Paola M. Boggiatto; Carly R. Kanipe; Eduardo Casas; Robert E. Briggs; Fred M. Tatum (Veterinary Microbiology, 2025)

Dietetics and Nursing Students Affirmatively Report the Likelihood of Recommending Predominantly Plant-based Diets for Non-communicable Disease Management - P. Dyett; L. Foster-Nicholas; C. Mitchell; V. Jones-Oyefeso; V. Sealey-Tobias; A. Adams-Robinson; P. Valley-Thom; D. Balfour (Journal of the Academy of Nutrition and Dietetics, 2025)

Trends in Fomepizole Use for Acetaminophen Poisoning in the United States; 2013–2024 - Mitchell D’Aloia; Dale Smith; Randy Boley; Emily Schamber; Dillon Thorpe; Trevonne M. Thompson; Neeraj Chhabra (Journal of Medical Toxicology, 2025)
Background Fomepizole has been suggested as adjunctive therapy for severe acetaminophen poisoning though clinical efficacy is unknown. We sought to determine trends in the use of fomepizole for acetaminophen poisoning. Methods This is a cross-sectional analysis of hospitalized patients with acetaminophen poisoning from January 2013 through December 2024, using Epic Cosmos, a research database of 298 million patients nationally. We identified encounters involving acetaminophen poisoning by International Classification of Diseases, version 10 (ICD-10-CM) code. Data extracted included administration of N-acetylcysteine (NAC) and fomepizole, demographic data, and outcomes of death and liver transplantation. Data were analyzed using descriptive statistics to identify trends and multivariable logistic regression to determine associations with death. Results There were 114,111 hospital encounters involving acetaminophen poisoning with 64,957 (56.92%) receiving NAC, and 1,552 (1.36%) receiving fomepizole. In 2013, 0.44% of NAC-treated acetaminophen poisoning cases also received fomepizole. This rose to 6.27% in 2024. From 2013 to 2019, the proportion of NAC-treated acetaminophen cases receiving fomepizole was stable, but from 2019 to 2024, there was a 1029.64% increase in fomepizole use. Regression modeling indicated increased odds for death (OR = 5.88, aOR = 5.32 [95% CI: 4.52, 6.27]) among those who received fomepizole in addition to NAC, indicating increased fomepizole use in patients with severe toxicity. Conclusion Fomepizole use in acetaminophen poisoning has risen dramatically since 2019, particularly among patients at highest risk for death and liver transplantation. It is of critical importance to determine the efficacy of fomepizole for acetaminophen poisoning.

A seasonal aggregation of juvenile scalloped hammerheads Sphyrna lewini along beaches of the G old C oast, A ustralia - Nicolas Lubitz; Kerryn Doupain; Siobhan Houlihan; Jonathan D. Mitchell (Journal of Fish Biology, 2025)
We document a recurring seasonal aggregation of juvenile scalloped hammerhead sharks Sphyrna lewini along the beaches of the Gold Coast, Australia, with notable occurrences at Burleigh Heads and Kirra Reef. The aggregation consists of individuals of varying sizes, which likely suggests the presence of different cohorts, though it remains uncertain whether this area meets the criteria for a nursery habitat. Given the global population declines of S. lewini , its classification as Critically Endangered by the IUCN and its Conservation Dependent status under Australian legislation, we recommend standardised surveys and tracking studies to assess habitat use, seasonality and the potential role of Gold Coast waters as a critical habitat for juvenile S. lewini .

Geographic, Taxonomic and Metric Gaps in Biodiversity Research Limit Evidence‐Based Conservation in Agricultural Landscapes: An Umbrella Review - Jonathan Bonfanti; Joseph Langridge; A. Avadí; N. Casajus; A. Chaudhary; G. Damour; N. Estrada‐Carmona; S. K. Jones; D. Makowski; M. Mitchell; R. Seppelt; Damien Beillouin (Ecology Letters, 2025)
Agriculture is fundamentally dependent on biodiversity, yet unsustainable management practices increasingly threaten various organisms and ecosystem services. Confronting the global crisis of biodiversity loss requires a thorough understanding of the gaps, clusters and biases in existing knowledge across various management practices, spatial scales, and taxonomic groups. We undertook a comprehensive literature review, synthesising secondary data from 200 meta‐analyses on agricultural management impacts on biodiversity in croplands. Our systematic map covers 1885 comparisons (mean effect sizes), from over 9000 primary studies. In the latter, seven high‐income countries prevail (notably the USA, China and Brazil), with particular focus on fertiliser use, phytosanitary interventions and crop diversification. This emphasis on individual practices overshadows research at the farm and landscape levels. In secondary evidence, arthropods and microorganisms are most frequently studied, while annelids, vertebrates and plants are less represented. Evidence predominantly stems from averaged abundance data, revealing substantial gaps in studies on functional and phylogenetic diversity. Our findings highlight the need to analyse combinations of multiple practices to accurately reflect real‐world farming contexts, and covering a wider range of taxa, biodiversity metrics and spatial levels, to enable evidence‐based conservation strategies in agriculture. Given the uneven evidence on agricultural impacts, caution is required when applying meta‐analytical findings to public policies and global assessments.

Animal farming and the oral microbiome in the Agricultural Health Study - Vicky C. Chang; Vaishnavi Purandare; Shilan Li; Gabriella Andreotti; Xing Hua; Yunhu Wan; Casey L. Dagnall; Kristine Jones; Belynda D. Hicks; Amy Hutchinson; Yukiko Yano; Kathryn R. Dalton; et al. (Environmental Research, 2025)

Victor diamonds – replacement of carbon and nitrogen in the central Superior Craton mantle root associated with the Midcontinent Rift event - Luisa D. V. Carvalho; Anetta Banas; Pamela Wescott; Mitchell Galarneau; Kelsey Graversen; Richard Stern; Ingrid Chinn; Heidi E. Höfer; Karlis Muehlenbachs; Matthew Steele-MacInnis; David Fisher; Julie Kong; et al. (Mineralogy and Petrology, 2025)

Eucoleus boehmi in dogs: Anthelmintic treatment challenges and impact on olfactory capacity - Nathan D. Mitchell; Jenna D. Balk; Jake Hughes; Priscila Soto Nauto; Joseph Rossi; Caroline Sobotyk; Robert Valeris-Chacin; Roger Ramirez-Barrios (Veterinary Parasitology, 2025)

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Evaluating five shoreline change models against 40 years of field survey data at an embayed sandy beach - Oxana Repina; Rafael C. Carvalho; Giovanni Coco; José A.Á. Antolínez; Iñaki de Santiago; Mitchell D. Harley; Camilo Jaramillo; Kristen D. Splinter; Sean Vitousek; Colin D. Woodroffe (Coastal Engineering, 2025)

Conceptual model for assessing a science–policy–management framework for threat mitigation - Tom Le Breton; Mitchell Lyons; Bettina Ignacio; Tony D. Auld; Mark Ooi (Conservation Biology, 2025)
Fire regimes are changing globally, leading to an increased need for management interventions to protect human lives and interests, potentially conflicting with biodiversity conservation. We conceptualized 5 major aspects of the process required to address threats to flora and used this conceptual model to examine and identify areas for improvement. We focused on threat identification, policy design, and action implementation. We illustrated the application of the conceptual model through a case study in southeastern Australia, where policies have been designed to prevent hazard reduction burns from exposing threatened flora to high‐frequency fire (HFF). We examined whether threatened species have been accurately identified as threatened by HFF, species were accounted for in key policies, and implementation of the policy reduced the incidence of HFF for target species. Species were mostly identified accurately as being threatened by HFF, and, broadly, the policy effectively minimized the threat from HFF. However, 96 species did not have HFF identified as a threat, and another 36 were missing from the policy entirely. Outcomes regarding the reduction of threat from HFF since policy introduction were species specific, despite an average increase in fire interval of 2 years. Despite the policy, over half (55%) the species studied have been affected by HFF since the policy was introduced. Although relatively minor improvements could optimize threat identification and policy design, the mixed success of action implementation highlights limitations that warrant further investigation. Our conceptual model enabled us to make clear and targeted recommendations for how different aspects of the policy could be improved and where further work is needed. We propose the conceptual model can be useful in a variety of contexts.

Mapping illegal trade routes of live cheetahs from the Horn of Africa to the Arabian Peninsula - Paul H. Evangelista; Nicholas E. Young; Darin K. Schulte; Patricia D. Tricorache; Matthew W. Luizza; Sarah M. Durant; Kelly W. Jones; Nicholas Mitchell; Tomas Maule; Abdullahi H. Ali; Redae T. Tesfai; Peder S. Engelstad (Conservation Biology, 2025)
Less than 7000 cheetahs ( Acinonyx jubatus ) persist in Africa. Although human–wildlife conflict, habitat degradation, and loss of prey are major threats to cheetah populations, illegal trade in live cubs for pets may have the most significant impact on populations in the Horn of Africa. We developed a novel, stepwise decision support tool to predict probable trafficking routes by leveraging the power of distinct modeling approaches. First, we created a cheetah habitat suitability index (HSI) to determine where source cheetah populations may occur. We then created a trafficking network model linking known and predicted cheetah populations with documented destinations in the Arabian Peninsula. A significant area in Eastern Ethiopia and Northern Somalia was estimated to harbor undocumented cheetahs. When these predicted populations were used as a supply source, the trafficking network model showed multiple routes passing through Somaliland and across the Gulf of Aden to Yemen, supporting the notion that undocumented cheetahs may be supplying pet market demands. Though we demonstrate how our decision support tool can inform law enforcement, conservation strategies, and community engagement, we caution that our results are not fully validated due to limited accessibility, alternative trafficking routes, and the cryptic nature of illegal wildlife trade.

Interplay between quantitative trait loci for stem strength and agronomic traits in a wheat doubled-haploid population - J. Allan Feurtado; Letitia M. Da Ros; Shola H. Kareem; Breenah Mulligan; Daiqing Huang; Lanette Ehman; Parul Jain; Leah K. Flatman; Hanna Hovland; Jeff Hovland; Brett Beckie; Richard D. Cuthbert; et al. (Field Crops Research, 2025)

Validation of a new acoustic telemetry transmitter for the study of predation events in small fishes - Mitchell B. Shorgan; Heather Bauer Reid; Silviya V. Ivanova; Aaron T. Fisk; Steven J. Cooke; Graham D. Raby (Journal of Fish Biology, 2025)
Acoustic telemetry has emerged as an important tool for studying the movement and behavior of aquatic animals. Predation‐sensing acoustic transmitters combine the functions of typical acoustic transmitters with the added ability to identify the predation of tagged animals. The objective of this paper was to assess the performance of a newly miniaturized acid‐based predation‐sensing acoustic transmitter (Innovasea V3D; 0.33 g in air). We conducted staged predation events in the laboratory where acoustically tagged rainbow trout ( Oncorhynchus mykiss ) were fed to largemouth bass ( Micropterus nigricans ) at 3.3–7.0, 9.0–10.8, 16.0–20.0, and 22.0–25.8°C. We also conducted false‐positive tests where tagged rainbow trout were held at 10.0 and 16.8°C without the risk of predation. Predation events were successfully identified in 92% of the staged predation trials. Signal lag (i.e., the time required for a predation tag to indicate that predation occurred) ranged from 0.11 to 6.29 days and decreased strongly with increasing water temperature and increased with increasing body mass of the tagged prey. Tag retention in the gut of the predator was much more variable than signal lag and was influenced by water temperature and individual predators but not by prey mass. No false positives were detected after 60 days at either temperature ( n = 27 individuals). Although the relationships between water temperature, signal lag, and retention time are likely species‐specific, the data reported here provide useful information for the use of these transmitters to study predation in wild fishes, especially for temperate, freshwater fish.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Continental‐Scale α ‐ and β ‐Diversity Patterns of Terrestrial Eukaryotic Microbes: Effect of Climate and Microhabitat on Testate Amoeba Assemblages in Eurasian Peatlands - Jiahui Su; Yuri A. Mazei; Andrey N. Tsyganov; Natalia G. Mazei; Victor A. Chernyshov; Alexander A. Komarov; Kirill V. Babeshko; Edward A. D. Mitchell; Satoshi Shimano; Damir A. Saldaev; Basil N. Yakimov (Journal of Biogeography, 2025)
Aim The role of environmental factors that shape the large‐scale distribution of eukaryotic microbes remains understudied. We aimed to disentangle the impacts of latitudinal and longitudinal gradients on the distribution of Sphagnum‐ dwelling testate amoebae in mires and to understand the influence of environmental factors related to both local habitats (hummock—lawn—hollows) and regional climates. Location A range from temperate to subarctic and from the European part to the Far East of Russia (51°–70°N, 32°–158°E). Taxon Testate amoeba (Arcellinida, Euglyphida, and Amphitremida). Methods We analysed the testate amoeba (TA) composition and abundance data from 816 samples collected in 75 peatlands. Linear mixed‐effects models and redundancy analysis were applied to determine the likely environmental drivers of TA α ‐ and β ‐diversity. Results We identified a significant reversed latitudinal gradient in α ‐diversity which negatively correlated with the mean annual temperature. This gradient is microhabitat‐specific, being prominent in lawn and hollow microhabitats, but not in hummocks. Longitude, which corresponds mainly to a gradient of precipitation seasonality, was a significant predictor of TA β ‐diversity, especially in hollows. Main Conclusions Our findings identify climatic factors (e.g., mean annual temperature and precipitation seasonality) as likely shaping the continental‐scale TA α ‐ and β ‐diversity patterns, emphasising the microhabitat‐specific nature of these relationships. The absence of pattern in hummocks is interpreted as evidence for a predominant microhabitat stress (i.e., low moisture and pH) in this habitat.

Distribution and disturbances of ditches across salt marshes of the Northeast U.S. with implications for management and restoration - Erin K. Peck; Julie E. Walker; Katherine V. Ackerman; Joel Carr; Maureen D. Correll; Zafer Defne; Linda A. Deegan; Mitchell J. Eaton; Neil K. Ganju; Mitch Hartley; Catherine Johnson; Jason Mercer; et al. (Journal of Environmental Management, 2025)

Narrow Margins: Aerobic Performance and Temperature Tolerance of Coral Reef Fishes Facing Extreme Thermal Variability - Grace O. Vaughan; Daniel M. Ripley; Matthew D. Mitchell; Dain McParland; Jacob L. Johansen; Holly A. Shiels; John A. Burt (Global Change Biology, 2025)
Climate change is driving rising average sea temperatures and the intensification of thermal variability. Tropical coral reef fishes have evolved under thermally stable conditions to function optimally within a narrow temperature range, with many currently living close to their upper thermal limits. However, recent work has demonstrated that some species possess additional capacity, such as reductions in basal metabolic rates (i.e., ‘plastic floors’), to compensate for the acute effects of thermal challenges when assessed over multigenerational timeframes. In this study, we use the ‘plastic floors and concrete ceilings’ hypothesis to generate and then test predictions regarding the thermal physiology of reef fishes in the world's hottest and most thermally variable coral reef ecosystem (southern Arabian/Persian Gulf). By comparing three species of reef fishes ( Scolopsis ghanam , Ecsenius pulcher and Cheilodipterus novemstriatus ) from the southern Arabian/Persian Gulf, with an annual temperature range of 18.0°C–36.5°C, to conspecifics from nearby but more thermally benign (~21.0°C–32.0°C) reefs in the Gulf of Oman, we find enhanced upper thermal limits and a broadening of the temperature performance curves for aerobic scope in the Arabian/Persian Gulf, but no evidence for changes in basal metabolic rates (‘plastic floors’). Despite these conserved increases in temperature tolerance, the summer thermal safety margins of Arabian/Persian Gulf fishes were 1.47°C lower than those of conspecifics from the Gulf of Oman, demonstrating that while the temperature tolerance of tropical coral reef fishes is somewhat plastic over multigenerational timeframes, its rate of change is likely insufficient to keep pace with the rising average temperatures and growing thermal variability expected under climate change.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

In situ staining with antibodies cross-reactive in pigs, cattle, and white-tailed deer facilitates understanding of biological tissue status and immunopathology - Jayne E. Wiarda; Eraldo L. Zanella; Adrienne L. Shircliff; Eric D. Cassmann; Crystal L. Loving; Alexandra C. Buckley; Mitchell V. Palmer (Veterinary Immunology and Immunopathology, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Assessing the effect of multispecies interactions on precautionary reference points using an ensemble modelling approach: A North Sea case study - Michael A. Spence; James A. Martindale; Khatija Alliji; Hayley J. Bannister; Robert B. Thorpe; Nicola D. Walker; Peter J. Mitchell; Matthew R. Kerr; Paul J. Dolder (Fisheries Research, 2024)

Half a century of citizen science tag-recapture data reveals stock delineation and cross-jurisdictional connectivity of an iconic pelagic fish - Belinda K. Goddard; Tristan A. Guillemin; Hayden T. Schilling; Julian M. Hughes; Stephanie Brodie; Corey P. Green; Robert Harcourt; Charlie Huveneers; Daniel Ierodiaconou; Iain M. Suthers; Matthew D. Taylor; Sean R. Tracey; et al. (Reviews in Fish Biology and Fisheries, 2024)
Tag-recapture programs to monitor the movements of fish populations are among some of the longest-running citizen-science datasets to date. Here, using half a century of yellowtail kingfish ( Seriola lalandi, Carangidae) tag-recapture data collected through citizen-science projects, we report novel insights into population connectivity in Australia and New Zealand (NZ). Despite the importance of kingfish in commercial and recreational fisheries, substantial knowledge gaps about their stock structure and connectivity between jurisdictions hinder current management efforts. Between 1974 and 2022, 63,432 releases and 4636 recaptures (7.3%) of tagged kingfish were collected in Australia and NZ. Most tagged individuals (51.4%) were recaptured within 10 km of their original release location up to 14 years post-release (mean: 225 days), indicating some degree of site fidelity. However, 656 (14.2%) kingfish were recaptured over 100 km from their release location, with one fish travelling at least 2834 km in 702 days. Seasonal variability was evident for releases and recaptures, with more releases occurring in summer and autumn in most jurisdictions. Network analysis of recaptures revealed no connectivity between tagged kingfish from western and eastern Australia, supporting genetic delineation. By contrast, extensive connectivity exists across eastern Australia and NZ, with 87 kingfish moving between five Australian state jurisdictions, 316 individuals travelling across 15 bioregions and six kingfish moving between Australia and NZ. Our findings provide important new insights into the structure and connectivity of the eastern Australia kingfish stock and suggest increased collaboration between state and international fisheries jurisdictions may support improved stock assessment and management.

Next-generation marker-free transplastomic plants: engineering the chloroplast genome without integration of marker genes in Solanum tuberosum (potato) - Alessandro Occhialini; Andrew C. Reed; Stacee A. Harbison; Megan J. Sichterman; Aaron Baumann; Alexander C. Pfotenhauer; Li Li; Gabriella King; Aaron G. Vincent; Ashley D. Wise-Mitchell; C. Neal Stewart; Scott C. Lenaghan (Plant Cell Reports, 2024)

Applying acoustic telemetry, vessel tracking and fisher knowledge to investigate and manage fisher-shark conflict at Lord Howe Island, Australia - Jonathan D. Mitchell; Victoria Camilieri-Asch; Sallyann Gudge; Fabrice R. A. Jaine; Victor M. Peddemors; Tim J. Langlois (Marine Biology, 2024)
Fisher-shark conflict is occurring at Lord Howe Island, Australia due to high levels of Galapagos shark ( Carcharhinus galapagensis ) depredation (where sharks consume hooked fish) and bycatch. Depredation causes costly loss of target catch and fishing gear and increased mortality of target species, and sharks can be injured or killed when bycaught. This study applied acoustic telemetry and vessel tracking from 2018 to 2021 to identify; (1) how the movements of 30 tagged sharks and activity of six fishing vessels overlapped, and (2) where key ‘hotspots’ of overlap occurred. Fisher surveys were also conducted to collect information about mitigating shark interactions. Residency index analysis indicated that three sharks tagged at a fish waste dumping site had markedly higher residency. Core home ranges of sharks overlapped with higher fishing activity at four ‘hotspots’. Statistical modelling indicated positive linear effects of fishing activity and bathymetric complexity on shark detections and tagged sharks were present for 13% of the total time that vessels were fishing close to acoustic receivers. Spatio-temporal overlaps between shark movements and fishing activity could potentially have occurred because sharks learned to associate fishing vessels with food (i.e. hooked fish) and because fishers and sharks utilise highly productive shelf edge areas, however more research is needed to investigate these relationships. Fishers reported that rotating fishing areas and reducing time at each location, fishing deeper than 100 m, and using electric reels and lures instead of bait, reduced bycatch and depredation. The integrated approach used here identified practical methods for reducing fisher-shark conflict, improving socio-economic outcomes for fishers and conservation prospects for this unique shark population.

Functional Traits of the World's Late Quaternary Terrestrial Mammalian Predators - Eamonn I. F. Wooster; Erick J. Lundgren; Mairin Balisi; Rhys T. Lemoine; Christopher J. Sandom; Jens‐Christian Svenning; John Rowan; Chris J. Jolly; Grant D. Linley; Mitchell. A. Cowan; Nick Wright; Dylan Westaway; et al. (Global Ecology and Biogeography, 2024)
Motivation Terrestrial predators play key roles in cycling nutrients, as well as limiting prey populations, and shaping the behaviour of their prey. Prehistoric, historic and ongoing declines of the world's predators have reshaped terrestrial ecosystems and are a topic of conservation concern. However, the availability of ecologically relevant predator functional traits is limited, hampering efforts to understand macroecological changes in this ecologically important functional group. Here, we present CarniTraits , a comprehensive open‐access functional trait database of all late Quaternary (~130,000 ybp) terrestrial mammalian predators (149 species, ≥1 kg body mass, ≥50% vertebrate meat consumption). Main Types of Variables Contained Mammalian terrestrial predator functional traits including body mass, diet, scavenging, locomotion, cooperative hunting, hunting habitat, hunting method, bone consumption, temporal activity patterns, brain mass and encephalisation quotient. Spatial Location and Grain Global. Time Period and Grain Late Quaternary (the last ~130,000 years). Major Taxa and Level of Measurement All late Quaternary terrestrial mammalian predators (149 species, ≥1 kg body mass, ≥50% vertebrate meat consumption). Software Format csv.

Past fire dynamics in sub-Saharan Africa during the last 25,000 years: Climate change and increasing human impacts - Laurent Bremond; Julie C. Aleman; Charly Favier; Olivier Blarquez; Daniele Colombaroli; Simon E. Connor; Carlos E. Cordova; Colin Courtney-Mustaphi; Abraham N. Dabengwa; Graciela Gil-Romera; William D. Gosling; Tamryn Hamilton; et al. (Quaternary International, 2024)

Data-driven modelling of coastal storm erosion for real-time forecasting at a wave-dominated embayed beach - Raimundo Ibaceta; Mitchell D. Harley (Coastal Engineering, 2024)

Trastuzumab deruxtecan (DS-8201a), a HER2-targeting antibody–drug conjugate, demonstrates in vitro and in vivo antitumor activity against primary and metastatic ovarian tumors overexpressing HER2 - Levent Mutlu; Blair McNamara; Stefania Bellone; Diego D. Manavella; Cem Demirkiran; Michelle Greenman; Miguel Skyler Z. Verzosa; Natalia Buza; Pei Hui; Tobias Max Philipp Hartwich; Justin Harold; Yang Yang-Hartwich; et al. (Clinical & Experimental Metastasis, 2024)

Genomic identification of Oryctes rhinoceros nudivirus isolates, a biocontrol agent for coconut rhinoceros beetle - Ela Hiszczynska-Sawicka; Mitchell K. Weston; Aurelie Laugraud; Charles A. Hefer; Jeanne M. E. Jacobs; Sean D. G. Marshall (Archives of Microbiology, 2024)
The coconut rhinoceros beetle ( Oryctes rhinoceros , CRB) is a serious pest of coconut and oil palms. It is native to South and Southeast Asia and was inadvertently introduced to Samoa in 1909. It has invaded many other Pacific countries throughout the last century. Oryctes rhinoceros nudivirus (OrNV), a natural pathogen of CRB in its native range, was successfully introduced as a classical biocontrol agent and has effectively suppressed invasive CRB populations for decades. However, resurgence of CRB has been recorded, with new invasions detected in several Pacific Island Countries and Territories. Additionally, new populations of CRB are emerging in some invaded areas that have a degree of resistance to the virus isolates commonly released for CRB biocontrol. Here, we designed a fast and reliable tool for distinguishing between different OrNV isolates that can help with the selection process to identify effective isolates for management of new CRB invasions. A comparison of 13 gene/gene region sequences within the OrNV genome of 16 OrNV isolates from native and invaded ranges allowed us to identify unique Single Nucleotide Polymorphisms (SNPs). With these SNPs, we developed an assay using multiplex PCR-amplicon-based nanopore sequencing to distinguish between OrNV isolates. We found that as few as four gene fragments were sufficient to identify 15 out of 20 OrNV isolates. This method can be used as a tool to monitor the establishment and distribution of OrNV isolates selected for release as biocontrol agents in CRB-infected areas.

Biofidelity and Limitations of Instrumented Mouthguard Systems for Assessment of Rigid Body Head Kinematics - Mitchell Z. Abrams; Jay Venkatraman; Donald Sherman; Maria Ortiz-Paparoni; Jefferson R. Bercaw; Robert E. MacDonald; Jason Kait; Elizabeth D. Dimbath; Derek Y. Pang; Alexandra Gray; Jason F. Luck; Cynthia A. Bir; et al. (Annals of Biomedical Engineering, 2024)

Life history and early ontogeny determine vertical swimming behaviors in the larvae of Caribbean corals - Benjamin D. Limer; Olivia Payne; Aran Brancato; Molly Mitchell; Caitlyn Abu-Kubie; Joana Figueiredo; Daniel M. Holstein (Journal of Experimental Marine Biology and Ecology, 2024)

A framework for national-scale coastal storm hazards early warning - Ian L. Turner; Christopher K. Leaman; Mitchell D. Harley; Mandi C. Thran; Daniel R. David; Kristen D. Splinter; Nashwan Matheen; Jeff E. Hansen; Michael V.W. Cuttler; Diana J.M. Greenslade; Stefan Zieger; Ryan J. Lowe (Coastal Engineering, 2024)

Development and characterisation of a novel complex triple cell culture model of the human alveolar epithelial barrier - Sarah M. Mitchell; Kirsty Meldrum; Joshua W. P. Bateman; Teresa D. Tetley; Shareen H. Doak; Martin J. D. Clift (In vitro models, 2024)
Owing to increased pressure from ethical groups and the public to avoid unnecessary animal testing, the need for new, responsive and biologically relevant in vitro models has surged. Models of the human alveolar epithelium are of particular interest since thorough investigations into air pollution and the effects of inhaled nanoparticles and e-cigarettes are needed. The lung is a crucial organ of interest due to potential exposures to endogenous material during occupational and ambient settings. Here, an in vitro model of the alveolar barrier has been created in preparation for use in the quasi-air liquid interface (qALI) and (aerosol) air–liquid interface (ALI) exposures. The model consists of an alveolar type 1-like cell line (TT1), an alveolar type 2-like cell line (NCI-H441) and a model of (alveolar) macrophages (dTHP-1). The model formulates a complex, multi-cellular system, cultured at the air–liquid interface, that mimics the apical layer of the alveolar epithelial region in the human lung. Characterisation data has shown that both TT1 and NCI-H441 epithelial cells are able to be cultured together in addition to dTHP-1 cells through imaging (morphology), pro-inflammatory response and viability measurements. This dataset also demonstrates evidence of a reasonable barrier created by the cell culture in comparison to negative controls. Furthermore, it shows that while maintaining a low baseline of (pro)-inflammatory mediator expression during normal conditions, the model is highly responsive to inflammatory stimuli. This model is proposed to be suitable for use in toxicology testing of inhaled exogenous agents.

Bioenergetic mapping of ‘healthy microbiomes’ via compound processing potential imprinted in gut and soil metagenomes - Craig Liddicoat; Robert A. Edwards; Michael Roach; Jake M. Robinson; Kiri Joy Wallace; Andrew D. Barnes; Joel Brame; Anna Heintz-Buschart; Timothy R. Cavagnaro; Elizabeth A. Dinsdale; Michael P. Doane; Nico Eisenhauer; et al. (Science of The Total Environment, 2024)

Letter to the editor regarding “Critical windows of fluoride neurotoxicity in Canadian children” by Farmus and colleagues. Environmental research, 111315. https://doi.org/10.1016/j.envres.2021.111315. No fluoride neurotoxicity in Canadian children - Juliet Guichon; Belinda Nicolau; Mario Brandini; Christian Caron; Ian Mitchell; Violet D'Souza (Environmental Research, 2024)

A Review of Elite Athlete Evidence-Based Knowledge and Preparation for Competing in the Heat - Chris J. Esh; Sarah Carter; Natalia Galan-Lopez; Frederic Garrandes; Stephane Bermon; Paolo Emilio Adami; Sebastien Racinais; Lewis James; Trent Stellingwerff; William M. Adams; Bryna Chrismas; Christopher J. Stevens; et al. (Journal of Science in Sport and Exercise, 2024)
Elite athletes will compete in extreme heat more frequently as global land and sea temperatures increase, alongside more intense, frequent and longer duration heatwaves. Best practices to protect athlete health and performance during competition include heat acclimation/acclimatisation [(HA); i.e., long-term pre-competition preparation] complemented by pre-planned and practised cooling and hydration strategies (i.e., short-term interventions immediately before or during competition). This review explores elite athletes’ current behaviours and practices when preparing for competition in the heat and assesses the level of knowledge that has been exhibited by athletes and their practitioners in this space. Recommendations for future research, discussions of current best practices, and methods to improve translation of research into practice are provided. Available research focuses on small samples of elite endurance athletes during a selection of World Championship/Olympic/Paralympic events (~6% of competing athletes). While generally an increase in the adoption of evidence-based HA is seen chronologically from 2015 onwards, universal adoption is not seen. HA adoption is lowest in those who live/train in cold/temperate environments with cost and access to facilities/equipment being the most commonly reported barriers. Further research is required across the sporting landscape to fully characterise elite athlete behaviours and practices in these spaces. International federations and national governing bodies should continue their efforts to educate athletes and focus on regularly updated and reinvigorated release of evidence-based guidelines (in multiple germane languages) for competing in the heat, to increase the adoption of HA and other heat related best practice.

Parental perceptions of body weight and appetite in infants and toddlers with cystic fibrosis - Sarah Ann Duck; Elena Jansen; Afroditi Papantoni; Aerial Sheltry; Daphne Koinis-Mitchell; Viren D’Sa; Sean Deoni; Timothy H. Moran; Robert L. Findling; Peter J. Mogayzel; Susan Carnell (Appetite, 2024)

Extreme iron cycling in a coastal lake-lagoon system driven by interactions between climate and entrance management - Scott G. Johnston; Thor Aaso; Damien T. Maher; Edward D. Burton; Mitchell Call; Mathew Birch; John Schmidt; Angus Ferguson (Science of The Total Environment, 2024)

3D printed plant-based biodegradable materials as alternative for PVC panels in monitoring coastal marine communities - Maria Rosa; Tristan Ene; Grace Robinson; Mitchell Lockwood; Nicolette Scola; Gerard D. Gadigian; Taegan A. McMahon (Journal of Experimental Marine Biology and Ecology, 2024)

Impacts of planned burning on the fungal diversity and vascular plants in a heathy woodland - Mitchell T. Johnston; Adam D. Miller; Owen J. Holland; Zach Clark; Tricia Wevill (Forest Ecology and Management, 2024)

Food policies for Aboriginal and Torres Strait Islander health (FoodPATH): A systems thinking approach - Jennifer Browne; Troy Walker (Yorta Yorta); Karen Hill (Torres Strait Islander); Fiona Mitchell (Mununjali); Holly Beswick; Stephanie Thow (Pennemuker, Ngāti Porou); Joleen Ryan (Gunditjmara); Simone Sherriff (Wotjobaluk); Amy Rossignoli; Abe Ropitini (Ngāti Kahungunu, Ngāti Maniapoto); Michael Johnstone; Yin Paradies (Wakaya); et al. (Food Policy, 2024)

The relationship between kinematics and fault geometry for surface coseismic ruptures on across-strike faults: New observations of slip vectors and displacements along the Pisia and Skinos faults from the 1981 Eastern Gulf of Corinth, Greece earthquakes - Sam Mitchell; Gerald P. Roberts; Joanna P. Faure Walker; Francesco Iezzi; Claudia Sgambato; Jennifer Robertson; Zoë K. Mildon; Athanassios Ganas; Ioannis D. Papanikolaou; Elias J. Rugen (Journal of Structural Geology, 2024)

The influence of micro-scale thermal habitat on the movements of juvenile white sharks in their Southern California aggregation sites - Emily Spurgeon; Marten L. Thompson; Mitchell D. Alexander; James M. Anderson; Patrick T. Rex; Brian Stirling; Kevin Abbott; Christopher G. Lowe (Frontiers in Marine Science, 2024)
While juvenile white sharks (JWS) can display regional endothermy, the need to maintain internal temperatures within an energetically favorable range likely drives thermoregulatory movements to maximize growth and foraging efficiency. Many JWS from the northeastern Pacific population aggregate seasonally in nearshore nursery habitats throughout the Southern California Bight and historic data show that inter-seasonal movement patterns may be heavily dependent on ambient water temperature. However, the degree to which micro-scale (e.g., ~10 m 2 ) water temperature heterogeneity influences JWS three-dimensional movement within nearshore aggregation sites is unknown. High-resolution temperature and passive acoustic-telemetry geo-positional data were used to quantify how temperature and vertical thermal stratification influenced JWS movement using several modeling approaches. JWS selected for water temperatures between 16 – 22°C and depths shallower than 2 m. Sharks occupied deeper waters during dawn and dusk periods, and their distance from the seafloor and spatial orientation of their depth distribution was significantly related to the thermal structure of the water column across the monitored area. Tagged sharks remained above a 16°C thermal threshold and altered their horizontal and vertical distributions accordingly. While high-resolution movement and environmental data provide improved predictability of micro-scale habitat use and distribution, other variables such as prey distribution, behavior, and competition would further improve habitat use models for this highly mobile species.

The importance of crowdsourced observations for urban climate services - Timothy D. Mitchell; Matthew J. Fry (International Journal of Climatology, 2024)
Crowdsourced observation networks are typically much more dense than those maintained by National Meteorological Services, and sample a much wider range of local climates. This offers an opportunity to build observed climatologies that are more representative of lived experience, particularly in cities. This study provides a worked example to show their potential for improving operational climate services, and to identify the challenges to realizing that potential. To demonstrate the concept, data from personal weather stations, obtained through citizen science, are used to build an observed record of daily maximum temperatures in 2020 in Manchester (UK). This record is compared to the standard baseline used in a current climate service, showing a substantial increase in the estimated heat hazard. If such potential benefits are to be realized in a climate service, it will be necessary to first build an alternative observed baseline of decadal length and at national or international scale. This requires further work to acquire, quality‐control, exposure‐control and map the crowdsourced observations.

The distinctive weathering crust habitat of a High Arctic glacier comprises discrete microbial micro‐habitats - Sara M. E. Rassner; Joseph M. Cook; Andrew C. Mitchell; Ian T. Stevens; Tristram D. L. Irvine‐Fynn; Andrew J. Hodson; Arwyn Edwards (Environmental Microbiology, 2024)
Sunlight penetrates the ice surfaces of glaciers and ice sheets, forming a water‐bearing porous ice matrix known as the weathering crust. This crust is home to a significant microbial community. Despite the potential implications of microbial processes in the weathering crust for glacial melting, biogeochemical cycles, and downstream ecosystems, there have been few explorations of its microbial communities. In our study, we used 16S rRNA gene sequencing and shotgun metagenomics of a Svalbard glacier surface catchment to characterise the microbial communities within the weathering crust, their origins and destinies, and the functional potential of the weathering crust metagenome. Our findings reveal that the bacterial community in the weathering crust is distinct from those in upstream and downstream habitats. However, it comprises two separate micro‐habitats, each with different taxa and functional categories. The interstitial porewater is dominated by Polaromonas , influenced by the transfer of snowmelt, and exported via meltwater channels. In contrast, the ice matrix is dominated by Hymenobacter , and its metagenome exhibits a diverse range of functional adaptations. Given that the global weathering crust area and the subsequent release of microbes from it are strongly responsive to climate projections for the rest of the century, our results underscore the pressing need to integrate the microbiome of the weathering crust with other communities and processes in glacial ecosystems.

Evaluating top‐down, bottom‐up, and environmental drivers of pelagic food web dynamics along an estuarine gradient - Tanya L. Rogers; Samuel M. Bashevkin; Christina E. Burdi; Denise D. Colombano; Peter N. Dudley; Brian Mahardja; Lara Mitchell; Sarah Perry; Parsa Saffarinia (Ecology, 2024)
Identification of the key biotic and abiotic drivers within food webs is important for understanding species abundance changes in ecosystems, particularly across ecotones where there may be strong variation in interaction strengths. Using structural equation models (SEMs) and four decades of integrated data from the San Francisco Estuary, we investigated the relative effects of top‐down, bottom‐up, and environmental drivers on multiple trophic levels of the pelagic food web along an estuarine salinity gradient and at both annual and monthly temporal resolutions. We found that interactions varied across the estuarine gradient and that the detectability of different interactions depended on timescale. For example, for zooplankton and estuarine fishes, bottom‐up effects appeared to be stronger in the freshwater upstream regions, while top‐down effects were stronger in the brackish downstream regions. Some relationships (e.g., bottom‐up effects of phytoplankton on zooplankton) were seen primarily at annual timescales, whereas others (e.g., temperature effects) were only observed at monthly timescales. We also found that the net effect of environmental drivers was similar to or greater than bottom‐up and top‐down effects for all food web components. These findings can help identify which trophic levels or environmental factors could be targeted by management actions to have the greatest impact on estuarine forage fishes and the spatial and temporal scale at which responses might be observed. More broadly, this study highlights how environmental gradients can structure community interactions and how long‐term data sets can be leveraged to generate insights across multiple scales.

Increased incidence of vibriosis in Maryland, U.S.A., 2006–2019 - Michele E. Morgado; Kyle D. Brumfield; Clifford Mitchell; Michelle M. Boyle; Rita R. Colwell; Amy R. Sapkota (Environmental Research, 2024)

Leaf yield and mineral content of mizuna in response to cut-and-come-again harvest, substrate particle size, and fertilizer formulation in a simulated spaceflight environment - Asmaa H. Morsi; Gioia D. Massa; Robert C. Morrow; Raymond M. Wheeler; Mokhles A. Elsysy; Cary A. Mitchell (Life Sciences in Space Research, 2024)

Demographic response of osprey within the lower Chesapeake Bay to fluctuations in menhaden stock - Bryan D. Watts; Christine H. Stinson; Peter K. McLean; K. Andrew Glass; Michael H. Academia; Mitchell A. Byrd (Frontiers in Marine Science, 2024)
Forage fish support the largest fisheries in the world and play a vital role in marine food webs by transferring energy from plankton to consumers within higher trophic levels. Growing commercial demand for these species and concern for the impact of over harvest on predator populations has driven a paradigm shift in management objectives from maximizing economic return to the establishment of ecosystem-based limits on harvest rates. How well current harvest policy supports noncommercial species like piscivorous birds remains poorly understood. We investigated the relationship between osprey breeding performance within the lower Chesapeake Bay and a menhaden stock index during a period (1974-2021) when the menhaden index fluctuated over 35-fold. Reproductive rate (young/pair/year), brood provisioning (fish/10-h) and the proportion of menhaden in the diet all declined during the study period. Indicators of food stress including brood reduction and nest failure increased during the study period. The population transitioned from reproductive surplus (demographic source) to reproductive deficit (demographic sink). A significant relationship between reproductive rate and the menhaden index suggests that osprey population viability requires that the menhaden stock be restored to 1980s levels. Current ecological reference points based on the food requirements of predatory fish are unlikely to protect the osprey population. We suggest the establishment of menhaden or reproductive thresholds designed to allow osprey to meet demographic targets (1.15 young/pair/year).

Corrigendum to “Measurement of Henry's law constants of ethyl nitrate in deionized water, synthetic sea salt solutions, and n-octanol” [Chemosphere 346 (2024) 140482] - Kevin D. Easterbrook; Mitchell A. Vona; Hans D. Osthoff (Chemosphere, 2024)

Measurement of Henry's law constants of ethyl nitrate in deionized water, synthetic sea salt solutions, and n-octanol - Kevin D. Easterbrook; Mitchell A. Vona; Hans D. Osthoff (Chemosphere, 2024)

Mitigating tire wear particles and tire additive chemicals in stormwater with permeable pavements - Chelsea J. Mitchell; Anand D. Jayakaran (Science of The Total Environment, 2024)

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Astaxanthin and meclizine extend lifespan in UM-HET3 male mice; fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate do not significantly affect lifespan in either sex at the doses and schedules used - David E. Harrison; Randy Strong; Peter Reifsnyder; Nadia Rosenthal; Ron Korstanje; Elizabeth Fernandez; Kevin Flurkey; Brett C. Ginsburg; Meredith D. Murrell; Martin A. Javors; Marisa Lopez-Cruzan; James F. Nelson; et al. (GeroScience, 2023)
In genetically heterogeneous (UM-HET3) mice produced by the CByB6F1 × C3D2F1 cross, the Nrf2 activator astaxanthin (Asta) extended the median male lifespan by 12% ( p = 0.003, log-rank test), while meclizine (Mec), an mTORC1 inhibitor, extended the male lifespan by 8% ( p = 0.03). Asta was fed at 1840 ± 520 (9) ppm and Mec at 544 ± 48 (9) ppm, stated as mean ± SE ( n ) of independent diet preparations. Both were started at 12 months of age. The 90th percentile lifespan for both treatments was extended in absolute value by 6% in males, but neither was significant by the Wang–Allison test. Five other new agents were also tested as follows: fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate. None of these increased lifespan significantly at the dose and method of administration tested in either sex. Amounts of dimethyl fumarate in the diet averaged 35% of the target dose, which may explain the absence of lifespan effects. Body weight was not significantly affected in males by any of the test agents. Late life weights were lower in females fed Asta and Mec, but lifespan was not significantly affected in these females. The male-specific lifespan benefits from Asta and Mec may provide insights into sex-specific aspects of aging.

Metabolomes of bumble bees reared in common garden conditions suggest constitutive differences in energy and toxin metabolism across populations - Ellen C. Keaveny; Mitchell R. Helling; Franco Basile; James P. Strange; Jeffrey D. Lozier; Michael E. Dillon (Journal of Insect Physiology, 2023)

Two new genera and a new species of Anacardiaceae from northern South America - John D. Mitchell; Douglas C. Daly; Laura Calvillo-Canadell; Ricardo O. Perdiz (Brittonia, 2023)

Utilising geochemical data for the identification and characterisation of mineral exploration sample media within cover sequence materials - C. J. Tiddy; S. M. Hill; D. Giles; B. G. van der Hoek; V. J. Normington; R. R. Anand; E. Baudet; K. Custance; R. Hill; A. Johnson; S. McLennan; C. Mitchell; et al. (Australian Journal of Earth Sciences, 2023)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

Prediction of the Renal Organic Anion Transporter 1 (OAT1)- Mediated Drug Interactions for LY404039, the Active Metabolite of Pomaglumetad Methionil - Y. Anne Pak; Maria M. Posada; James Bacon; Amanda Long; William Annes; Jennifer Witcher; Malcolm Mitchell; Rommel G. Tirona; Stephen D. Hall; Kathleen M. Hillgren (Pharmaceutical Research, 2023)

Immune cell composition varies by age, sex and exposure to social adversity in free-ranging Rhesus Macaques - Mitchell R. Sanchez Rosado; Nicole Marzan-Rivera; Marina M. Watowich; Andrea D. Negron-Del Valle; Petraleigh Pantoja; Melissa A. Pavez-Fox; Erin R. Siracusa; Eve B. Cooper; Josue E. Negron-Del Valle; Daniel Phillips; Angelina Ruiz-Lambides; Melween I. Martinez; et al. (GeroScience, 2023)

Defensive response of evolutionarily naïve Pinus sylvestris to the mountain pine beetle fungal associate Grosmannia clavigera in comparison to Pinus ponderosa - Kevin D. Chase; Kathryn J. Rynders; Mitchell P. Maddox; Brian H. Aukema (Forest Ecology and Management, 2023)

Extraction and Digitization of ECG Signals from Standard Clinical Portable Document Format Files for the Principal Component Analysis of T-wave Morphology - Michal Schäfer; Max B. Mitchell; Caitlin Brateng; D. Dunbar Ivy; Kendall S. Hunter; Dustin B. Nash; Johannes C. von Alvensleben (Cardiovascular Engineering and Technology, 2023)

Grass variety selection of microbial community composition is associated with differences in soil CO2 emissions - M.E. Giles; S. Caul; D. King; S. Mitchell; A. Sim; R. Neilson; E. Paterson (Applied Soil Ecology, 2023)

Maximizing soil organic carbon stocks under cover cropping: insights from long-term agricultural experiments in North America - Yajun Peng; Elizabeth L. Rieke; Inderjot Chahal; Charlotte E. Norris; Ken Janovicek; Jeffrey P. Mitchell; Kraig L. Roozeboom; Zachary D. Hayden; Jeffrey S. Strock; Stephen Machado; Virginia R. Sykes; Bill Deen; et al. (Agriculture, Ecosystems & Environment, 2023)

Economic and risk analysis of sustainable practice adoption among U.S. corn growers - Fengxia Dong; Paul D. Mitchell (Agricultural Systems, 2023)

Forces, electric fields and currents at the subsolar martian MPB: MAVEN observations and multifluid MHD simulation - G. Boscoboinik; C. Bertucci; D. Gomez; C. Dong; L. Regoli; C. Mazelle; J. Halekas; J. Espley; C.M. Fowler; D. Mitchell; L. Andersson (Icarus, 2023)

Puma predation on Magellanic penguins: An unexpected terrestrial-marine linkage in Patagonia - Mitchell W. Serota; Pablo A.E. Alarcón; Emiliano Donadio; Arthur D. Middleton (Food Webs, 2023)

Systemic inflammation and biological aging in the Health and Retirement Study - Helen C. S. Meier; Colter Mitchell; Thomas Karadimas; Jessica D. Faul (GeroScience, 2023)
Chronic, low-level systemic inflammation associated with aging, or inflammaging, is a risk factor for several chronic diseases and mortality. Using data from the Health and Retirement Study, we generated a continuous latent variable for systemic inflammation from seven measured indicators of inflammation and examined associations with another biomarker of biological aging, DNA methylation age acceleration measured by epigenetic clocks, and 4-year mortality ( N = 3,113). We found that greater systemic inflammation was positively associated with DNA methylation age acceleration for 10 of the 13 epigenetic clocks, after adjustment for sociodemographics and chronic disease risk factors. The latent variable for systemic inflammation was associated with 4-year mortality independent of DNA methylation age acceleration and was a better predictor of 4-year mortality than any of the epigenetic clocks examined, as well as mortality risk factors, including obesity and multimorbidity. Inflammaging and DNA methylation age acceleration may represent different biological processes contributing to mortality risk. Leveraging multiple measured inflammation markers to capture inflammaging is important for biology of aging research.

Visions of the Possible: Student Experiences With Public Policy in Graduate Dietetics Education - Anna Diffenderfer; Lindsay Ganong; D. Coleen Kaiser; J. Mitchell Vaterlaus (Journal of Nutrition Education and Behavior, 2023)

Interannual variability in dominant shoreline behaviour at an embayed beach - Raimundo Ibaceta; Mitchell D. Harley; Ian L. Turner; Kristen D. Splinter (Geomorphology, 2023)

Shear design of RC members strengthened with steel reinforcing bars embedded through section - M. Fiset; J. Bastien; D. Mitchell (Engineering Structures, 2023)

Machine Learning–Based Identification of Target Groups for Thrombectomy in Acute Stroke - Fanny Quandt; Fabian Flottmann; Vince I. Madai; Anna Alegiani; Clemens Küpper; Lars Kellert; Adam Hilbert; Dietmar Frey; Thomas Liebig; Jens Fiehler; Mayank Goyal; Jeffrey L. Saver; et al. (Translational Stroke Research, 2023)
Whether endovascular thrombectomy (EVT) improves functional outcome in patients with large-vessel occlusion (LVO) stroke that do not comply with inclusion criteria of randomized controlled trials (RCTs) but that are considered for EVT in clinical practice is uncertain. We aimed to systematically identify patients with LVO stroke underrepresented in RCTs who might benefit from EVT. Following the premises that (i) patients without reperfusion after EVT represent a non-treated control group and (ii) the level of reperfusion affects outcome in patients with benefit from EVT but not in patients without treatment benefit, we systematically assessed the importance of reperfusion level on functional outcome prediction using machine learning in patients with LVO stroke treated with EVT in clinical practice ( N = 5235, German-Stroke-Registry) and in patients treated with EVT or best medical management from RCTs ( N = 1488, Virtual-International-Stroke-Trials-Archive). The importance of reperfusion level on outcome prediction in an RCT-like real-world cohort equaled the importance of EVT treatment allocation for outcome prediction in RCT data and was higher compared to an unselected real-world population. The importance of reperfusion level was magnified in patient groups underrepresented in RCTs, including patients with lower NIHSS scores (0–10), M2 occlusions, and lower ASPECTS (0–5 and 6–8). Reperfusion level was equally important in patients with vertebrobasilar as with anterior LVO stroke. The importance of reperfusion level for outcome prediction identifies patient target groups who likely benefit from EVT, including vertebrobasilar stroke patients and among patients underrepresented in RCT patients with low NIHSS scores, low ASPECTS, and M2 occlusions.

Shark depredation: future directions in research and management - J. D. Mitchell; J. M. Drymon; J. Vardon; P. G. Coulson; C. A. Simpfendorfer; S. B. Scyphers; S. M. Kajiura; K. Hoel; S. Williams; K. L. Ryan; A. Barnett; M. R. Heupel; et al. (Reviews in Fish Biology and Fisheries, 2023)
Shark depredation is a complex social-ecological issue that affects a range of fisheries worldwide. Increasing concern about the impacts of shark depredation, and how it intersects with the broader context of fisheries management, has driven recent research in this area, especially in Australia and the United States. This review synthesises these recent advances and provides strategic guidance for researchers aiming to characterise the occurrence of depredation, identify the shark species responsible, and test deterrent and management approaches to reduce its impacts. Specifically, the review covers the application of social science approaches, as well as advances in video camera and genetic methods for identifying depredating species. The practicalities and considerations for testing magnetic, electrical, and acoustic deterrent devices are discussed in light of recent research. Key concepts for the management of shark depredation are reviewed, with recommendations made to guide future research and policy development. Specific management responses to address shark depredation are lacking, and this review emphasizes that a “silver bullet” approach for mitigating depredation does not yet exist. Rather, future efforts to manage shark depredation must rely on a diverse range of integrated approaches involving those in the fishery (fishers, scientists and fishery managers), social scientists, educators, and other stakeholders.

Biomass Quality Responses to Selection for Increased Biomass Yield in Perennial Energy Grasses - Michael D. Casler; DoKyoung Lee; Robert B. Mitchell; Kenneth J. Moore; Paul R. Adler; R. Mark Sulc; Keith D. Johnson; Robert L. Kallenbach; Arvid R. Boe; Russell D. Mathison; Kim A. Cassida; Doohong Min; et al. (BioEnergy Research, 2023)

Biomass Production and Nutrient Removal by Perennial Energy Grasses Produced on a Wet Marginal Land - Danielle R. Cooney; Nictor Namoi; Colleen Zumpf; Soo-Hyun Lim; Maria Villamil; Robert Mitchell; D. K. Lee (BioEnergy Research, 2023)
Growing dedicated bioenergy crops on marginal land can provide beneficial outcomes including biomass production and energy, resource management, and ecosystem services. We investigated the effects of harvest timing (peak standing crop [PEAK] or after killing frost [KF]) and nitrogen (N) fertilizer rates (0, 56, and 112 kg N ha −1 ) on yield, nutrient concentrations, and nutrient removal rates of perennial grasses on a wet marginal land. We evaluated three monocultures, including switchgrass ( Panicum virgatum L., SW), Miscanthus x giganteus (MG), prairie cordgrass ( Spartina pectinata Link, PCG), and a polyculture mixture of big bluestem ( Andropogon gerardii Vitman), Indiangrass ( Sorghastrum nutans (L.) Nash), and sideoats grama ( Bouteloua curtipendula Torr., MIX). Increasing the application of N did correlate with increased biomass, concentration, and subsequent removal of nutrients across almost all treatment combinations. In all grass treatments except MG, PEAK harvesting increased yield and nutrient removal. At PEAK harvest, switchgrass is ideal for optimizing both biomass production and nutrient removal. While our results also suggest short-term plasticity for farmers when selecting harvest timing for optimal nutrient removal, KF harvest is recommended to ensure long-term stand longevity and adequate nutrient removal. If the KF harvest is adopted, MG would be the ideal option for optimizing biomass yield potential. Additionally, we found that the yield of polyculture did not vary much with harvest timing, suggesting better yield stability. Future studies should give consideration for long-term evaluation of polyculture mixtures to assess their biomass yields and nutrient removal capacities.

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

Ocean carbon from space: Current status and priorities for the next decade - Robert J.W. Brewin; Shubha Sathyendranath; Gemma Kulk; Marie-Hélène Rio; Javier A. Concha; Thomas G. Bell; Astrid Bracher; Cédric Fichot; Thomas L. Frölicher; Martí Galí; Dennis Arthur Hansell; Tihomir S. Kostadinov; et al. (Earth-Science Reviews, 2023)

Perverse outcomes from fencing fauna: Loss of antipredator traits in a havened mammal population - Natasha D. Harrison; Ben L. Phillips; Nicola J. Mitchell; Julia C. Wayne; Marika A. Maxwell; Colin G. Ward; Adrian F. Wayne (Biological Conservation, 2023)

Biosorption of lanthanum by acidophile Euglena mutabilis biofilms and the role of extracellular polymeric substances - Mitchell T.E. Zak; Vladimiros G. Papangelakis; D. Grant Allen (Algal Research, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Carabid specialists respond differently to nonnative plant invasion in urban forests - J. Christina Mitchell; Vincent D’Amico; Tara L. E. Trammell; Steven D. Frank (Urban Ecosystems, 2023)

Evaluating and improving APSIM's capacity in simulating long-term corn yield response to nitrogen in continuous- and rotated-corn systems - Mitchell E. Baum; John E. Sawyer; Emerson D. Nafziger; Isaiah Huber; Peter J. Thorburn; Michael J. Castellano; Sotirios V. Archontoulis (Agricultural Systems, 2023)

Semi-supervised contrastive learning for remote sensing: identifying ancient urbanization in the south-central Andes - Jiachen Xu; Junlin Guo; James Zimmer-Dauphinee; Quan Liu; Yuxuan Shi; Zuhayr Asad; D. Mitchell Wilkes; Parker VanValkenburgh; Steven A. Wernke; Yuankai Huo (International Journal of Remote Sensing, 2023)

Good Practices for the Laboratory Performance Testing of Aqueous Oral Inhaled Products (OIPs): an Assessment from the International Pharmaceutical Aerosol Consortium on Regulation and Science (IPAC-RS) - Jolyon P. Mitchell; I. Carter; J. D. Christopher; M. Copley; W. H. Doub; A. Goodey; C. J. Gruenloh; B. B. Larson; S. Lyapustina; R. B. Patel; S. W. Stein; J. D. Suman (AAPS PharmSciTech, 2023)

Human impact on deer use is greater than predators and competitors in a multiuse recreation area - Darcy R. Visscher; Philip D. Walker; Mitchell Flowers; Colborne Kemna; Jesse Pattison; Brandon Kushnerick (Animal Behaviour, 2023)

Imaging the magmatic plumbing of the Clear Lake Volcanic Field using 3-D gravity inversions - Michael A. Mitchell; Jared R. Peacock; Seth D. Burgess (Journal of Volcanology and Geothermal Research, 2023)

Biochar and fungi as bioretention amendments for bacteria and PAH removal from stormwater - Chelsea J. Mitchell; Anand D. Jayakaran; Jenifer K. McIntyre (Journal of Environmental Management, 2023)

Dhurrin stability and hydrogen cyanide release in dried sorghum samples - Shelby M. Gruss; Keith D. Johnson; Manoj Ghaste; Joshua R. Widhalm; Sandy K. Johnson; Johnathon D. Holman; Augustine Obour; Robert M. Aiken; Mitchell R. Tuinstra (Field Crops Research, 2023)

Minimal adaptation of the molecular regulators of mitochondrial dynamics in response to unilateral limb immobilisation and retraining in middle-aged men - Chantal A. Pileggi; Christopher P. Hedges; Randall F. D’Souza; Brenan R. Durainayagam; Nina Zeng; Vandre C. Figueiredo; Anthony J. R. Hickey; Cameron J. Mitchell; David Cameron-Smith (European Journal of Applied Physiology, 2023)

Chronic toxicity of three formulations of neonicotinoid insecticides and their mixture on two daphniid species: Daphnia magna and Ceriodaphnia dubia - Claire Duchet; Chelsea J. Mitchell; Jenifer K. McIntyre; John D. Stark (Aquatic Toxicology, 2023)

Exploring avenues for agricultural intensification: A case study for maize-soybean in the Southern US region - Ignacio Massigoge; Ana Carcedo; Andre Froes de Borja Reis; Clay Mitchell; Scott Day; Joaquin Oliverio; Sandra H. Truong; Ryan F. McCormick; Jose Rotundo; Sara Lira; Ignacio Ciampitti; Carlos D. Messina (Agricultural Systems, 2023)

Improving multi-decadal coastal shoreline change predictions by including model parameter non-stationarity - Raimundo Ibaceta; Kristen D. Splinter; Mitchell D. Harley; Ian L. Turner (Frontiers in Marine Science, 2022)
Our ability to predict sandy shoreline evolution resulting from future changes in regional wave climates is critical for the sustainable management of coastlines worldwide. To this end, the present generation of simple and efficient semi-empirical shoreline change models have shown good skill at predicting shoreline changes from seasons up to several years at a number of diverse sites around the world. However, a key limitation of these existing approaches is that they rely on time-invariant model parameters, and assume that beaches will evolve within constrained envelopes of variability based on past observations. This raises an interesting challenge because the expected future variability in key meteocean and hydrodynamic drivers of shoreline change are likely to violate this ‘stationary’ approach to longer-term shoreline change prediction. Using a newly available, multi-decadal (28-year) dataset of satellite-derived shorelines at the Gold Coast, Australia, this contribution presents the first attempt to improve multi-decadal shoreline change predictions by allowing the magnitude of the shoreline model parameters to vary in time. A data assimilation technique (Ensemble Kalman Filter, EnKF) embedded within the well-established ShoreFor shoreline change model is first applied to a 14-year training period of approximately fortnightly shoreline observations, to explore temporal variability in model parameters. Then, the magnitudes of these observed non-stationary parameters are modelled as a function of selected wave climate covariates, representing the underlying seasonal to interannual variability in wave forcing. These modelled time-varying parameters are then incorporated into the shoreline change model and tested over the complete 28-year dataset. This new inclusion of non-stationary model parameters that are directly modelled as a function of the underlying wave forcing and corresponding time scales of beach response, is shown to outperform the multi-decadal predictions obtained by applying the conventional stationary approach (RMSE non-stationary = 11.1 m; RMSE stationary = 254.3 m). Based on these results, it is proposed that a non-stationary approach to shoreline change modelling can reduce the uncertainty associated with the misspecification of physical processes driving shoreline change and should be considered for future shoreline change predictions.

Breeding oat for resistance to the crown rust pathogen Puccinia coronata f. sp. avenae: achievements and prospects - R. F. Park; W. H. P. Boshoff; A. L. Cabral; J. Chong; J. A. Martinelli; M. S. McMullen; J. W. Mitchell Fetch; E. Paczos-Grzęda; E. Prats; J. Roake; S. Sowa; L. Ziems; et al. (Theoretical and Applied Genetics, 2022)
Crown rust, caused by Puccinia coronata f. sp. avenae ( Pca ), is a significant impediment to global oat production. Some 98 alleles at 92 loci conferring resistance to Pca in Avena have been designated; however, allelic relationships and chromosomal locations of many of these are unknown. Long-term monitoring of Pca in Australia, North America and elsewhere has shown that it is highly variable even in the absence of sexual recombination, likely due to large pathogen populations that cycle between wild oat communities and oat crops. Efforts to develop cultivars with genetic resistance to Pca began in the 1950s. Based almost solely on all all-stage resistance, this has had temporary benefits but very limited success. The inability to eradicate wild oats, and their common occurrence in many oat growing regions, means that future strategies to control Pca must be based on the assumption of a large and variable prevailing pathogen population with high evolutionary potential, even if cultivars with durable resistance are deployed and grown widely. The presence of minor gene, additive APR to Pca in hexaploid oat germplasm opens the possibility of pyramiding several such genes to give high levels of resistance. The recent availability of reference genomes for diploid and hexaploid oat will undoubtedly accelerate efforts to discover, characterise and develop high throughput diagnostic markers to introgress and pyramid resistance to Pca in high yielding adapted oat germplasm.

Prediction of a conserved pheromone receptor lineage from antennal transcriptomes of the pine sawyer genus Monochamus (Coleoptera: Cerambycidae) - Robert F. Mitchell; Daniel Doucet; Susan Bowman; Marc C. Bouwer; Jeremy D. Allison (Journal of Comparative Physiology A, 2022)

Data Gathering in UWA Sensor Networks: Practical Considerations and Lessons from Sea Trials - Nils Morozs; Benjamin Sherlock; Benjamin T. Henson; Jeffrey A. Neasham; Paul D. Mitchell; Yuriy Zakharov (Journal of Marine Science and Engineering, 2022)
Underwater acoustic (UWA) network protocol design is a challenging task due to several factors, such as slow propagation of acoustic waves, low frequency bandwidth and high bit error and frame error rates often encountered in real UWA environments. In this paper, we consider the design of a robust and scalable data gathering protocol for UWA sensor networks (UASNs), focusing on practical considerations and lessons learnt from multiple lake and sea trials. A cross-layer protocol is presented that integrates a network discovery process, intelligent routing, scheduling via Transmit Delay Allocation MAC (TDA-MAC) and multi-node Automatic Repeat Request (ARQ), to facilitate reliable data gathering in practical UASN deployments. Furthermore, this paper presents the details of a novel experimental testbed and underwater sensor node prototype that were used for the trials reported in this study. Based on the results of the trials, important conclusions are drawn on the protocol features required to achieve reliable networked communication in realistic UWA environments. The insights gained from the trials are valuable both for further development of the proposed data gathering protocol, and for the wider UWA networking research community concerned with developing practical solutions for real-world UASN deployments.

Microsatellite characterisation of the extinct Sophora toromiro (Fabaceae) and confirmation of the identities of Allan Herbarium specimens and the fabled Christchurch ‘Victoria Park toromiro’ - Peter B. Heenan; Caroline M. Mitchell; Lara D. Shepherd; Gary J. Houliston (New Zealand Journal of Botany, 2022)
We analysed nine microsatellite markers for 260 individuals representing Sophora tomentosa and 15 species from across the geographic range of Sophora sect. Edwardsia . The purpose of the study was to characterise the Sophora species from Pacific Ocean islands and South America and determine their relationships to the eight New Zealand species, with relationships of the extinct Rapa Nui/Easter Island S. toromiro a particular focus. Structure, PCoA and NeighborNet analyses showed S. tomentosa was distinct from species of sect. Edwardsia . Among the species of sect. Edwardsia , S. cassioides , S. howinsula , S. longicarinata , S. prostrata and S. toromiro were genetically distinct as each comprised a high proportion of membership of individuals assigned to them. The remaining species were assigned to four genetic groups, each of which had one species with a high proportion of membership and other species with lower proportions of membership. The S. chrysophylla group also included high proportions of S. macrocarpa , S. denudata and S. raivavaeensis . The S. fulvida , S. godleyi and S. molloyi genetic groups mostly included low proportions of other New Zealand species. In the PCoA, S. toromiro specimens clustered together and were placed at the margin of a large sect. Edwardsia group. Sophora toromiro comprised four specimens representing the Melbourne Botanic Gardens (Australia) genotype and two specimens in the Allan Herbarium (CHR) obtained from cultivated specimens in Valparaíso (Chile) during the early 1970s. One specimen from Valparaíso was originally identified as S. toromiro , while the other was misidentified as Sophora macnabiana (now S. cassioides ). The lack of genetic variation in S. toromiro suggests they were perhaps derived from the last surviving tree on Rapa Nui / Easter Island. A cultivated plant from New Zealand known as the ‘Victoria Park toromiro’ had its identity confirmed as S. godleyi , which is consistent with its morphological identification.

The genetic basis for panicle trait variation in switchgrass (Panicum virgatum) - Li Zhang; Alice MacQueen; Xiaoyu Weng; Kathrine D. Behrman; Jason Bonnette; John L. Reilley; Francis M. Rouquette; Philip A. Fay; Yanqi Wu; Felix B. Fritschi; Robert B. Mitchell; David B. Lowry; et al. (Theoretical and Applied Genetics, 2022)
Key message We investigate the genetic basis of panicle architecture in switchgrass in two mapping populations across a latitudinal gradient, and find many stable, repeatable genetic effects and limited genetic interactions with the environment. Abstract Grass species exhibit large diversity in panicle architecture influenced by genes, the environment, and their interaction. The genetic study of panicle architecture in perennial grasses is limited. In this study, we evaluate the genetic basis of panicle architecture including panicle length, primary branching number, and secondary branching number in an outcrossed switchgrass QTL population grown across ten field sites in the central USA through multi-environment mixed QTL analysis. We also evaluate genetic effects in a diversity panel of switchgrass grown at three of the ten field sites using genome-wide association (GWAS) and multivariate adaptive shrinkage. Furthermore, we search for candidate genes underlying panicle traits in both of these independent mapping populations. Overall, 18 QTL were detected in the QTL mapping population for the three panicle traits, and 146 unlinked genomic regions in the diversity panel affected one or more panicle trait. Twelve of the QTL exhibited consistent effects (i.e., no QTL by environment interactions or no QTL × E), and most (four of six) of the effects with QTL × E exhibited site-specific effects. Most (59.3%) significant partially linked diversity panel SNPs had significant effects in all panicle traits and all field sites and showed pervasive pleiotropy and limited environment interactions. Panicle QTL co-localized with significant SNPs found using GWAS, providing additional power to distinguish between true and false associations in the diversity panel.

Novel Fusarium wilt resistance genes uncovered in natural and cultivated strawberry populations are found on three non-homoeologous chromosomes - Dominique D. A. Pincot; Mitchell J. Feldmann; Michael A. Hardigan; Mishi V. Vachev; Peter M. Henry; Thomas R. Gordon; Marta Bjornson; Alan Rodriguez; Nicolas Cobo; Randi A. Famula; Glenn S. Cole; Gitta L. Coaker; et al. (Theoretical and Applied Genetics, 2022)
Key Message Several Fusarium wilt resistance genes were discovered, genetically and physically mapped, and rapidly deployed via marker-assisted selection to develop cultivars resistant to Fusarium oxysporum f. sp. fragariae , a devastating soil-borne pathogen of strawberry . Abstract Fusarium wilt, a soilborne disease caused by Fusarium oxysporum f. sp. fragariae , poses a significant threat to strawberry ( Fragaria $$×$$ × ananassa ) production in many parts of the world. This pathogen causes wilting, collapse, and death in susceptible genotypes. We previously identified a dominant gene ( FW1 ) on chromosome 2B that confers resistance to race 1 of the pathogen, and hypothesized that gene-for-gene resistance to Fusarium wilt was widespread in strawberry. To explore this, a genetically diverse collection of heirloom and modern cultivars and octoploid ecotypes were screened for resistance to Fusarium wilt races 1 and 2. Here, we show that resistance to both races is widespread in natural and domesticated populations and that resistance to race 1 is conferred by partially to completely dominant alleles among loci ( FW1 , FW2 , FW3 , FW4 , and FW5 ) found on three non-homoeologous chromosomes (1A, 2B, and 6B). The underlying genes have not yet been cloned and functionally characterized; however, plausible candidates were identified that encode pattern recognition receptors or other proteins known to confer gene-for-gene resistance in plants. High-throughput genotyping assays for SNPs in linkage disequilibrium with FW1 - FW5 were developed to facilitate marker-assisted selection and accelerate the development of race 1 resistant cultivars. This study laid the foundation for identifying the genes encoded by FW1-FW5 , in addition to exploring the genetics of resistance to race 2 and other races of the pathogen, as a precaution to averting a Fusarium wilt pandemic.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Rastogi; Sunny Nguyen; et al. (GeroScience, 2022)

Neotropical Anacardiaceae (cashew family) - John D. Mitchell; Susan K. Pell; Julien B. Bachelier; Emily J. Warschefsky; Elizabeth M. Joyce; Laura Calvillo Canadell; Cíntia Luíza da Silva-Luz; Clement Coiffard (Brazilian Journal of Botany, 2022)
Anacardiaceae is an ecologically and economically important plant family of about 200 species in 32 genera in the Neotropics. The family is particularly diverse in leaf architecture and fruit morphology, making it a model family to study the evolution of structural diversity as it correlates with lineage diversification. This fruit diversity is the primary reason 11 of the Neotropical genera are monotypic and that so many genera are recognized in the Anacardiaceae. The economic value of the family is driven by the global markets for cashews, mangoes, and pistachios, but there is great potential value in its medicinal properties. At least 10 Neotropical genera cause contact dermatitis, which is a rich area for research in the family. Here presented is a review of the systematics and structural diversity of the family. Particular attention is given to the morphology, economic botany, paleobotany, ecology, and taxonomy of native and naturalized genera. Keys to Neotropical Anacardiaceae subfamilies and genera are provided along with descriptions of native genera.

Drivers of fine‐scale diurnal space use by a coral‐reef mesopredatory fish - Alastair R. Harborne; David P. Kochan; Melanie M. Esch; Robert Y. Fidler; Matthew D. Mitchell; Drew W. Butkowski; Manuel González‐Rivero (Journal of Fish Biology, 2022)
The habitat preferences of many reef fishes are well established, but the use of space within these habitats by non‐site‐attached species is poorly studied. The authors examined the space use of a functionally important mesopredator, graysby ( Cephalopholis cruentata ), on six patch reefs in the Florida Keys. A 1 m 2 ‐scale grid was constructed on each reef and 16 individual C. cruentata were tracked diurnally in situ to identify space use. At the patch reef scale, larger C. cruentata were more active and had larger observed home ranges, although home ranges were also affected by fish density and the abundances of prey and predators. The total time in each 1 m 2 grid cell was regressed against a range of fine‐scale biotic variables, including multiple variables derived from structure‐from‐motion three‐dimensional digital reconstructions of each reef. Nonetheless, time in grid cells (preferred microhabitats) was only significantly positively correlated with the height of carbonate structures, likely because the cavities they enclose are particularly suitable for predator avoidance, resting and ambushing prey. The ongoing flattening of reefs in the region caused by negative carbonate budgets is thus likely to have significant effects on the abundance and space use of C. cruentata . In addition to examining spatial patterns, we analysed C. cruentata waiting times in each grid cell before moving. These times were best approximated by a truncated power‐law (heavy‐tailed) distribution, indicating a “bursty” pattern of relatively long periods of inactivity interspersed with multiple periods of activity. Such a pattern has previously been identified in a range of temperate ambush predators, and the authors extend this move‐wait behaviour, which may optimize foraging success, to a reef fish for the first time. Understanding how C. cruentata uses space and time is critical to fully identify their functional role and better predict the implications of fishing and loss of reef structure.

Soil protist function varies with elevation in the Swiss Alps - Florent Mazel; Lucie Malard; Hélène Niculita‐Hirzel; Erika Yashiro; Heidi K. Mod; Edward A. D. Mitchell; David Singer; Aline Buri; Eric Pinto; Nicolas Guex; Enrique Lara; Antoine Guisan (Environmental Microbiology, 2022)
Summary Protists are abundant and play key trophic functions in soil. Documenting how their trophic contributions vary across large environmental gradients is essential to understand and predict how biogeochemical cycles will be impacted by global changes. Here, using amplicon sequencing of environmental DNA in open habitat soil from 161 locations spanning 2600 m of elevation in the Swiss Alps (from 400 to 3000 m), we found that, over the whole study area, soils are dominated by consumers, followed by parasites and phototrophs. In contrast, the proportion of these groups in local communities shows large variations in relation to elevation. While there is, on average, three times more consumers than parasites at low elevation (400–1000 m), this ratio increases to 12 at high elevation (2000–3000 m). This suggests that the decrease in protist host biomass and diversity toward mountains tops impact protist functional composition. Furthermore, the taxonomic composition of protists that infect animals was related to elevation while that of protists that infect plants or of protist consumers was related to soil pH. This study provides a first step to document and understand how soil protist functions vary along the elevational gradient.

Natal experience and pre‐breeding environmental conditions affect lay date plasticity in Savannah Sparrows - Joseph B. Burant; Eric W. Heisey; Nathaniel T. Wheelwright; Amy E. M. Newman; Shannon Whelan; Daniel J. Mennill; Stéphanie M. Doucet; Greg W. Mitchell; Bradley K. Woodworth; D. Ryan Norris (Ecology, 2022)
Phenotypic plasticity allows organisms to adjust the timing of life‐history events in response to environmental and demographic conditions. Shifts by individuals in the timing of breeding with respect to variation in age and temperature are well documented in nature, and these changes are known to scale to affect population dynamics. However, relatively little is known about how organisms alter phenology in response to other demographic and environmental factors. We investigated how pre‐breeding temperature, breeding population density, age, and rainfall in the first month of life influenced the timing and plasticity of lay date in a population of Savannah Sparrows ( Passerculus sandwichensis ) monitored over 33 yr (1987–2019). Females that experienced warmer pre‐breeding temperatures tended to lay eggs earlier, as did older females, but breeding population density had no effect on lay date. Natal precipitation interacted with age to influence lay date plasticity, with females that experienced high precipitation levels as nestlings advancing lay dates more strongly over the course of their lives. We also found evidence for varied pace of life; females that experienced high natal precipitation had shorter lifespans and reduced fecundity, but more nesting attempts over their lifetimes. Rainfall during the nestling period increased through time, while population density and fecundity declined, suggesting that increased precipitation on the breeding grounds may be detrimental to breeding females and ultimately the viability of the population as a whole. Our results suggest that females adjust their laying date in response to pre‐breeding temperature, and as they age, while presenting new evidence that environmental conditions during the natal period can affect phenological plasticity and generate downstream, population‐level effects.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Diet of nestling Barn Swallows in an agroecosystem: insights from fecal DNA barcoding and feather stable isotopes (δ13C, δ15N) - Jackson W. Kusack; Greg W. Mitchell; Dean R. Evans; Michael D. Cadman; Jenny L. McCune; Keith A. Hobson (Journal of Ornithology, 2022)

Development of a multi-excitation fluorescence (MEF) imaging method to improve the information content of benthic coral reef surveys - Elena Bollati; Cecilia D’Angelo; David I. Kline; B. Greg Mitchell; Jörg Wiedenmann (Coral Reefs, 2021)
Benthic surveys are a key component of monitoring and conservation efforts for coral reefs worldwide. While traditional image-based surveys rely on manual annotation of photographs to characterise benthic composition, automatic image annotation based on computer vision is becoming increasingly common. However, accurate classification of some benthic groups from reflectance images presents a challenge to local ecologists and computers alike. Most coral reef organisms produce one or a combination of fluorescent pigments, such as Green Fluorescent Protein (GFP)-like proteins found in corals, chlorophyll-a found in all photosynthetic organisms, and phycobiliproteins found in red macroalgae, crustose coralline algae (CCA) and cyanobacteria. Building on the potential of these pigments as a target for automatic image annotation, we developed a novel imaging method based on off-the-shelf components to improve classification of coral and other biotic substrates using a multi-excitation fluorescence (MEF) imaging system. We used RGB cameras to image the fluorescence emission of coral and algal pigments stimulated by narrow-waveband blue and green light, and then combined the information into three-channel pseudocolour images. Using a set of a priori rules defined by the relative pixel intensity produced in different channels, the method achieved successful classification of organisms into three categories based on the dominant fluorescent pigment expressed, facilitating discrimination of traditionally problematic groups. This work provides a conceptual foundation for future technological developments that will improve the cost, accuracy and speed of coral reef surveys.

Standing variation rather than recent adaptive introgression probably underlies differentiation of the texanus subspecies of Helianthus annuus - Gregory L. Owens; Marco Todesco; Natalia Bercovich; Jean‐Sébastien Légaré; Nora Mitchell; Kenneth D. Whitney; Loren H. Rieseberg (Molecular Ecology, 2021)
The origins of geographic races in wide‐ranging species are poorly understood. In Texas, the texanus subspecies of Helianthus annuus has long been thought to have acquired its defining phenotypic traits via introgression from a local congener, H. debilis , but previous tests of this hypothesis were inconclusive. Here, we explore the origins of H. a. texanus using whole genome sequencing data from across the entire range of H. annuus and possible donor species, as well as phenotypic data from a common garden study. We found that although it is morphologically convergent with H. debilis , H. a. texanus has conflicting signals of introgression. Genome wide tests (Patterson's D and TreeMix ) only found evidence of introgression from H. argophyllus (sister species to H. annuus and also sympatric), but not H. debilis , with the exception of one individual of 109 analysed. We further scanned the genome for localized signals of introgression using PCAdmix and found minimal but nonzero introgression from H. debilis and significant introgression from H. argophyllus in some populations. Given the paucity of introgression from H. debilis , we argue that the morphological convergence observed in Texas is probably from standing genetic variation. We also found that genomic differentiation in H. a. texanus is mostly driven by large segregating inversions, several of which have signatures of natural selection based on haplotype frequencies.

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Ragosti; Sunny Nguyen; et al. (GeroScience, 2021)

Bathymetric Data Requirements for Operational Coastal Erosion Forecasting Using XBeach - Nashwan Matheen; Mitchell D. Harley; Ian L. Turner; Kristen D. Splinter; Joshua A. Simmons; Mandi C. Thran (Journal of Marine Science and Engineering, 2021)
There is an increasing interest in the broad-scale implementation of coastal erosion early warning systems (EWS) with the goal of enhancing community preparedness to extreme coastal storm wave events. These emerging systems typically rely on process-based models to predict the storm-induced morphological change. A key challenge with incorporating these models in EWSs is the need for up-to-date nearshore and surf zone bathymetry data, which is difficult to measure routinely, but potentially important for accurate erosion forecasting. This study evaluates the degree to which up-to-date bathymetry is required for accurate coastal erosion predictions using the morphodynamic model XBeach and, subsequently, whether a range of “representative” and/or “synthetic” bathymetries can be used for the bottom boundary, when a survey of the immediate pre-storm bathymetry is not available. Twelve storm events at two contrasting sites were modelled using six different bathymetry scenarios, including the expected “best case” bathymetry surveyed immediately pre-storm. These results indicate that alternative bathymetries can be used to obtain sub-aerial erosion predictions that are similar (and in some cases better) than those resulting from the use of an immediately pre-storm surveyed bathymetry, provided that rigorous model calibration is undertaken prior. This generalized finding is attributed to specific parametrizations in the XBeach model structure that are optimized during the calibration process to match the particular bottom boundary condition used. This study provides practical guidance for the selection of suitable nearshore bathymetry for use in operational coastal erosion EWSs.

Molecular Dynamics Simulations and Experimental Results Provide Insight into Clinical Performance Differences between Sandimmune® and Neoral® Lipid-Based Formulations - Dallas B. Warren; Shadabul Haque; Mitchell P. McInerney; Karen M. Corbett; Endri Kastrati; Leigh Ford; Hywel D. Williams; Vincent Jannin; Hassan Benameur; Christopher J.H. Porter; David K. Chalmers; Colin W. Pouton (Pharmaceutical Research, 2021)

Global connections with some genomic differentiation occur between Indo‐Pacific and Atlantic Ocean wahoo, a large circumtropical pelagic fish - Isabel Haro‐Bilbao; Cynthia Riginos; John D. Baldwin; Mitchell Zischke; Ian R. Tibbetts; Joshua A. Thia (Journal of Biogeography, 2021)
Aim Globally distributed pelagic fishes are typified by very low to negligible genetic differentiation at oceanic scales arising from high gene flow and (or) large population sizes. However, genomic approaches employing thousands of loci to characterise genetic variation can illuminate subtle patterns of genetic structure and facilitate demographic inference, such that effects arising from gene flow and population size can be partially decoupled. We used a population genomics approach to identify putative stocks in a circumtropical pelagic fish, wahoo, and to assess global connectivity in this species. Location Indo‐Pacific and Atlantic Oceans. Taxon Wahoo, Acanthocybium solandri (Cuvier, 1832). Methods Globally distributed wahoo samples from 11 locations (representing a total of 296 individuals) were sequenced using a pool‐seq ezRAD approach to obtain 1289–9825 genome‐wide SNP loci per population pair for analyses of genetic structure at a minor allele frequency (MAF) >0.05. Demographic inference using a diffusion approximation method ( ∂a∂i ) was performed using 11,495–12,812 SNPs per population pair at a MAF >0.02. Results Genetic structure, measured as F ST , was overall low, suggesting very little heterogeneity amongst sample pairs (pairwise F ST ≤ 0.021). However, there was a clear signal of regional genetic structuring between ocean basins. A principal coordinate analysis separated samples from the Indo‐Pacific with those from the Atlantic and an analysis of molecular variance suggested that ~77% of variation in genetic structure was amongst regions. Our demographic analyses found greater support for models including migration over simple models of isolation. Main conclusions Our study provides the most thorough genetic investigation of wahoo to date. We provide evidence for global connectivity of wahoo populations over their evolutionary history, but we also provide the first indication of subtle regional structure between the Indo‐Pacific and Atlantic Oceans, which occurs against a background of high gene flow. The identification of regional stocks will inform new management strategies and guide future investigations in wahoo, an increasingly important species in global fisheries.

Lipophilic Salts and Lipid-Based Formulations: Enhancing the Oral Delivery of Octreotide - Peng Li; Leigh Ford; Shadabul Haque; Mitchell P. McInerney; Hywel D. Williams; Peter J. Scammells; Philip E. Thompson; Vincent Jannin; Christopher J. H. Porter; Hassan Benameur; Colin W. Pouton (Pharmaceutical Research, 2021)

Parasites, niche modification and the host microbiome: A field survey of multiple parasites - Kayleigh R. O’Keeffe; Fletcher W. Halliday; Corbin D. Jones; Ignazio Carbone; Charles E. Mitchell (Molecular Ecology, 2021)
Parasites can affect and be affected by the host's microbiome, with consequences for host susceptibility, parasite transmission, and host and parasite fitness. Yet, two aspects of the relationship between parasite infection and host microbiota remain little understood: the nature of the relationship under field conditions, and how the relationship varies among parasites. To overcome these limitations, we performed a field survey of the within‐leaf fungal community in a tall fescue population. We investigated how diversity and composition of the fungal microbiome associate with natural infection by fungal parasites with different feeding strategies. A parasite's feeding strategy affects both parasite requirements of the host environment and parasite impacts on the host environment. We hypothesized that parasites that more strongly modify niches available within a host will be associated with greater changes in microbiome diversity and composition. Parasites with a feeding strategy that creates necrotic tissue to extract resources (necrotrophs) may not only have different niche requirements, but also act as particularly strong niche modifiers. Barcoded amplicon sequencing of the fungal ITS region revealed that leaf segments symptomatic of necrotrophs had lower fungal diversity and distinct composition compared to segments that were asymptomatic or symptomatic of other parasites. There were no clear differences in fungal diversity or composition between leaf segments that were asymptomatic and segments symptomatic of other parasite feeding strategies. Our results motivate future experimental work to test how the relationship between the microbiome and parasite infection is impacted by parasite feeding strategy and highlight the potential importance of parasite traits.

The mangrove CO 2 pump: Tidally driven pore‐water exchange - Xiaogang Chen; Isaac R. Santos; Mitchell Call; Gloria M. S. Reithmaier; Damien Maher; Ceylena Holloway; Praktan D. Wadnerkar; Paula Gómez‐Álvarez; Christian J. Sanders; Ling Li (Limnology and Oceanography, 2021)
Atmospheric carbon dioxide (CO 2 ) is fixed by mangrove vegetation and stored in its biomass and sediments. Part of the sediment carbon can be exported to coastal waters via tidally driven pore‐water exchange. Here, we quantify pore water‐derived dissolved CO 2 export using in situ, high‐resolution observations of 222 Rn and CO 2 over a spring‐neap tidal cycle in a mangrove‐fringed estuary (Coffs Creek, Australia). 222 Rn‐derived pore‐water exchange rates were 11.5–34.9 cm d −1 (23.0 ± 6.7) over 30 tidal cycles. Pore‐water exchange released CO 2 from intertidal sediment at rates of 61–213 (136 ± 43) mmol m −2 d −1 . This is equivalent to ~ 94% of the total CO 2 input into the estuary and approximately two times of the water‐atmosphere CO 2 emission. These observations reveal that tidal pumping is a major regulator of both mangrove pore‐water exchange and associated dissolved CO 2 export to the ocean. Combining our estimates with literature data, a first‐order global pore water‐derived dissolved CO 2 export from mangroves was estimated to be 83 ± 50 Tg C yr −1 . This is higher than an earlier estimates of global mangrove CO 2 emissions to the atmosphere (34.1 ± 5.4 Tg C yr −1 ) and carbon burial in sediments (18.4–34.4 Tg C yr −1 ), implying that pore water‐derived CO 2 escapes to the atmosphere within and beyond mangrove waters. Overall, CO 2 ‐rich pore water seems to be a widespread, important pathway of CO 2 into mangrove‐dominated estuaries and should be considered in mangrove carbon assessments in the context of global climate change and blue carbon.

Uniparental isodisomy of chromosome 2 causing MRPL44-related multisystem mitochondrial disease - Alejandro Horga; Andreea Manole; Alice L. Mitchell; Enrico Bugiardini; Iain P. Hargreaves; Walied Mowafi; Conceição Bettencourt; Emma L. Blakely; Langping He; James M. Polke; Catherine E. Woodward; Ilaria Dalla Rosa; et al. (Molecular Biology Reports, 2021)

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Fine-scale foraging effort and efficiency of Macaroni penguins is influenced by prey type, patch density and temporal dynamics - G. J. Sutton; C. A. Bost; A. Z. Kouzani; S. D. Adams; K. Mitchell; J. P. Y. Arnould (Marine Biology, 2021)

A systematic approach to assess the environmental impact of emerging technologies: A case study for the GHG footprint of CIGS solar photovoltaic laminate - Mitchell K. van der Hulst; Mark A. J. Huijbregts; Niels van Loon; Mirjam Theelen; Lucinda Kootstra; Joseph D. Bergesen; Mara Hauck (Journal of Industrial Ecology, 2020)
Estimating the environmental impact of emerging technologies at different stages of development is uncertain but necessary to guide investment, research, and development. Here, we propose a systematic procedure to assess the future impacts of emerging technologies. In the technology development stage (technology readiness level < 9), the recommended experience mechanisms to take into account are (a) process changes, (b) size scaling effects, and (c) process synergies. These developments can be based on previous experience with similar technologies or quantified through regression or engineering dimension calculations. In the industrial development phase, (d) industrial learning, based on experience curves or roadmaps, and (e) external developments should be included. External developments, such as changes in the electricity mix can be included with information from integrated assessment models. We show the applicability of our approach with the greenhouse gas (GHG) footprint evaluation for the production of copper indium gallium (di)selenide (CIGS) photovoltaic laminate. We found that the GHG footprint per kilowatt peak of produced CIGS laminate is expected to decrease by 83% going from pilot to mature industrial scale production with the largest decrease being due to expected process changes. The feasibility of applying our approach in practice would greatly benefit from the development of a database containing information on size scaling and experience rates for a wide variety of materials, products, and technologies.

Greater topoclimatic control of above‐ versus below‐ground communities - Heidi K. Mod; Daniel Scherrer; Valeria Di Cola; Olivier Broennimann; Quentin Blandenier; Frank T. Breiner; Aline Buri; Jérôme Goudet; Nicolas Guex; Enrique Lara; Edward A. D. Mitchell; Hélène Niculita‐Hirzel; et al. (Global Change Biology, 2020)
Assessing the degree to which climate explains the spatial distributions of different taxonomic and functional groups is essential for anticipating the effects of climate change on ecosystems. Most effort so far has focused on above‐ground organisms, which offer only a partial view on the response of biodiversity to environmental gradients. Here including both above‐ and below‐ground organisms, we quantified the degree of topoclimatic control on the occurrence patterns of >1,500 taxa and phylotypes along a c. 3,000 m elevation gradient, by fitting species distribution models. Higher model performances for animals and plants than for soil microbes (fungi, bacteria and protists) suggest that the direct influence of topoclimate is stronger on above‐ground species than on below‐ground microorganisms. Accordingly, direct climate change effects are predicted to be stronger for above‐ground than for below‐ground taxa, whereas factors expressing local soil microclimate and geochemistry are likely more important to explain and forecast the occurrence patterns of soil microbiota. Detailed mapping and future scenarios of soil microclimate and microhabitats, together with comparative studies of interacting and ecologically dependent above‐ and below‐ground biota, are thus needed to understand and realistically forecast the future distribution of ecosystems.

Roxadustat (FG-4592) accelerates pulmonary growth, development, and function in a compensatory lung growth model - Victoria H. Ko; Lumeng J. Yu; Duy T. Dao; Xiaoran Li; Jordan D. Secor; Lorenzo Anez-Bustillos; Bennet S. Cho; Amy Pan; Paul D. Mitchell; Hiroko Kishikawa; Mark Puder (Angiogenesis, 2020)

Maleic hydrazide elicits global transcriptomic changes in chemically topped tobacco to influence shoot bud development - Sanjay K. Singh; Mitchell D. Richmond; Robert C. Pearce; William A. Bailey; Xin Hou; Sitakanta Pattanaik; Ling Yuan (Planta, 2020)

Verification of the 2019 GloSea5 Seasonal Tropical Cyclone Landfall Forecast for East China - Joanne Camp; Philip E. Bett; Nicola Golding; Chris D. Hewitt; Timothy D. Mitchell; Adam A. Scaife (Journal of Meteorological Research, 2020)

The Process and Benefits of Developing Prototype Climate Services—Examples in China - Chris D. Hewitt; Nicola Golding; Peiqun Zhang; Tyrone Dunbar; Philip E. Bett; Joanne Camp; Timothy D. Mitchell; Edward Pope (Journal of Meteorological Research, 2020)

Large‐scale prion protein genotyping in Canadian caribou populations and potential impact on chronic wasting disease susceptibility - Maria Immaculata Arifin; Antanas Staskevicius; Su Yeon Shim; Yuan‐Hung Huang; Heather Fenton; Philip D. McLoughlin; Gordon Mitchell; Catherine I Cullingham; Sabine Gilch (Molecular Ecology, 2020)
Polymorphisms within the prion protein gene ( Prnp ) are an intrinsic factor that can modulate chronic wasting disease (CWD) pathogenesis in cervids. Although wild European reindeer ( Rangifer tarandus tarandus ) were infected with CWD, as yet there have been no reports of the disease in North American caribou ( R. tarandus spp.). Previous Prnp genotyping studies on approximately 200 caribou revealed single nucleotide polymorphisms (SNPs) at codons 2 (V/M), 129 (G/S), 138 (S/N), 146 (N/n) and 169 (V/M). The impact of these polymorphisms on CWD transmission is mostly unknown, except for codon 138. Reindeer carrying at least one allele encoding for asparagine (138NN or 138SN) are less susceptible to clinical CWD upon infection by natural routes, with the majority of prions limited to extraneural tissues. We sequenced the Prnp coding region of two caribou subspecies ( n = 986) from British Columbia, Saskatchewan, Yukon, Nunavut and the Northwest Territories, to identify SNPs and their frequencies. Genotype frequencies at codon 138 differed significantly between barren‐ground ( R. t. groenlandicus ) and woodland ( R. t. caribou ) caribou when we excluded the Chinchaga herd ( p Prnp genotypes associated with susceptibility to CWD is important for future wildlife management measures.

Mercury exposure to swallows breeding in Canada inferred from feathers grown on breeding and non-breeding grounds - Kevin J. Kardynal; Timothy D. Jardine; Corrine S. V. Génier; Kaelyn H. Bumelis; Greg W. Mitchell; Marlene Evans; Keith A. Hobson (Ecotoxicology, 2020)

Calibration of a common shortwave multispectral camera system for quantitative agricultural applications - J. Burdette Barker; Wayne E. Woldt; Brian D. Wardlow; Christopher M. U. Neale; Mitchell S. Maguire; Bryan C. Leavitt; Derek M. Heeren (Precision Agriculture, 2020)

Non-consumptive effects in fish predator–prey interactions on coral reefs - Matthew D. Mitchell; Alastair R. Harborne (Coral Reefs, 2020)

MitoQ and CoQ10 supplementation mildly suppresses skeletal muscle mitochondrial hydrogen peroxide levels without impacting mitochondrial function in middle-aged men - Toan Pham; Caitlin L. MacRae; Sophie C. Broome; Randall F. D’souza; Ravi Narang; Hsiang W. Wang; Trevor A. Mori; Anthony J. R. Hickey; Cameron J. Mitchell; Troy L. Merry (European Journal of Applied Physiology, 2020)

Feeding Biomechanics Influences Craniofacial Morphology at the Subspecies Scale among Australian Pademelons (Macropodidae: Thylogale) - D. Rex Mitchell; Emma Sherratt; Gabriele Sansalone; Justin A. Ledogar; Richard J. Flavel; Stephen Wroe (Journal of Mammalian Evolution, 2020)

Using ancient DNA to quantify losses of genetic and species diversity in seabirds: a case study of Pterodroma petrels from a Pacific island - Anicee J. Lombal; Alexander T. Salis; Kieren J. Mitchell; Alan J. D. Tennyson; Lara D. Shepherd; Trevor H. Worthy; Eric J. Woehler; Jeremy J. Austin; Christopher P. Burridge (Biodiversity and Conservation, 2020)

Chromosomal location of the crown rust resistance gene Pc98 in cultivated oat (Avena sativa L.) - Jun Zhao; Aida Z. Kebede; Jim G. Menzies; Edyta Paczos-Grzęda; James Chong; Jennifer W. Mitchell Fetch; Aaron D. Beattie; Yuan-Ying Peng; Curt A. McCartney (Theoretical and Applied Genetics, 2020)

Resilience of pond communities to extreme thermal regime shifts: an alpine–montane reciprocal transplant experiment - Mitchell A. Johnsen; Blake R. Stuparyk; Jenna Cook; Rolf D. Vinebrooke (Aquatic Sciences, 2020)

Soil protist diversity in the Swiss western Alps is better predicted by topo‐climatic than by edaphic variables - Christophe V. W. Seppey; Olivier Broennimann; Aline Buri; Erika Yashiro; Eric Pinto‐Figueroa; David Singer; Quentin Blandenier; Edward A. D. Mitchell; Hélène Niculita‐Hirzel; Antoine Guisan; Enrique Lara (Journal of Biogeography, 2020)
Aim Trends in spatial patterns of diversity in macroscopic organisms can be well predicted from correlative models, using topo‐climatic variables for plants and animals allowing inference over large scales. By contrast, diversity in soil microorganisms is generally considered as mostly driven by edaphic variables and, therefore, difficult to extrapolate on a large spatial scale based on predictive models. Here, we compared the power of topo‐climatic versus edaphic variables for predicting the diversity of various soil protist groups at the regional scale. Location Swiss western Alps. Taxa Full protist community and nine clades belonging respectively to three functional groups: parasites (Apicomplexa, Peronosporomycetes and Phytomyxea), phagotrophs (Sarcomonadea, Tubulinea and Spirotrichea) and phototrophs (Chlorophyta, Trebouxiophyceae and Diatomeae). Methods We extracted soil DNA from 178 sites along a wide range of elevations with a random‐stratified sampling design. We defined protist Operational Taxonomic Units assemblages by metabarcoding of the V4 region of the rRNA small subunit gene. We assessed and modelled the diversity (Shannon index) patterns of all above‐mentioned taxonomic groups based on topo‐climatic (topography, slope southness, slope steepness and average summer temperature) and edaphic (soil temperature, relative humidity, pH, electroconductivity, phosphorus percentage, carbon/nitrogen, loss on ignition and shale percentage) variables in Generalized Additive Models (GAM). Results The respective significance of topo‐climatic and edaphic variables varied among taxonomic and—to a certain extent—functional groups: while many variables explained significantly the diversity of the three phototrophs this was less the case for the three parasites. Topo‐climatic variables had a better predictive power than edaphic variables, yet predictive power varied among taxonomic groups. Main conclusions Topo‐climatic variables (particularly slope steepness and summer temperature if we consider their significance in the GAMs) were, on average, better predictors of protist diversity at the landscape scale than edaphic variables. However, the predictive power of these variables on diversity differed considerably among taxonomic groups; such relationships may be due to direct and/or indirect (e.g. biotic) influences (like with parasitic taxa, where low predictive power is most likely explained by the absence of information on the hosts’ distribution). Future prospects include using such spatial models to predict hotspots of diversity and disease outbreaks.

Environmental PCB forensics: processes and issues - Mitchell D. Erickson (Environmental Science and Pollution Research, 2020)

Nitrogen Demand Associated with Increased Biomass Yield of Switchgrass and Big Bluestem: Implications for Future Breeding Strategies - Michael D. Casler; DoKyoung Lee; Robert B. Mitchell; Paul R. Adler; R. Mark Sulc; Keith D. Johnson; Robert L. Kallenbach; Arvid R. Boe; Russell D. Mathison; Kim A. Cassida; Doohong Min; Kenneth J. Moore (BioEnergy Research, 2020)

Colonies of the fungus Aspergillus niger are highly differentiated to adapt to local carbon source variation - Paul Daly; Mao Peng; Hugh D. Mitchell; Young‐Mo Kim; Charles Ansong; Heather Brewer; Peter de Gijsel; Mary S. Lipton; Lye Meng Markillie; Carrie D. Nicora; Galya Orr; Ad Wiebenga; et al. (Environmental Microbiology, 2020)
Summary Saprobic fungi, such as Aspergillus niger , grow as colonies consisting of a network of branching and fusing hyphae that are often considered to be relatively uniform entities in which nutrients can freely move through the hyphae. In nature, different parts of a colony are often exposed to different nutrients. We have investigated, using a multi‐omics approach, adaptation of A. niger colonies to spatially separated and compositionally different plant biomass substrates. This demonstrated a high level of intra‐colony differentiation, which closely matched the locally available substrate. The part of the colony exposed to pectin‐rich sugar beet pulp and to xylan‐rich wheat bran showed high pectinolytic and high xylanolytic transcript and protein levels respectively. This study therefore exemplifies the high ability of fungal colonies to differentiate and adapt to local conditions, ensuring efficient use of the available nutrients, rather than maintaining a uniform physiology throughout the colony.

Mapping of the stem rust resistance gene Pg13 in cultivated oat - Aida Z. Kebede; Belayneh Admassu-Yimer; Wubishet A. Bekele; Tyler Gordon; J. Michael Bonman; Ebrahiem Babiker; Yue Jin; Sam Gale; Charlene P. Wight; Nicholas A. Tinker; Jim G. Menzies; Aaron D. Beattie; et al. (Theoretical and Applied Genetics, 2020)

Correction to: Neural correlates of reward magnitude and delay during a probabilistic delay discounting task in alcohol use disorder - Laura E. Dennis; Milky Kohno; Holly D. McCready; Daniel L. Schwartz; Britta Schwartz; David Lahna; Bonnie J. Nagel; Suzanne H. Mitchell; William F. Hoffman (Psychopharmacology, 2020)

Neural correlates of reward magnitude and delay during a probabilistic delay discounting task in alcohol use disorder - Laura E. Dennis; Milky Kohno; Holly D. McCready; Daniel L. Schwartz; Britta Schwartz; David Lahna; Bonnie J. Nagel; Suzanne H. Mitchell; William F. Hoffman (Psychopharmacology, 2020)

Concordance of chemically inferred and assayed nutrient limitation of phytoplankton along a depth gradient of alpine lakes in the Canadian Rockies - Jenna Cook; Blake R. Stuparyk; Mitchell A. Johnsen; Rolf D. Vinebrooke (Aquatic Sciences, 2020)

Rosette core fungal resistance in Arabidopsis thaliana - Yanwan Dai; Huw A. Ogilvie; Yuan Liu; Michael Huang; Lye Meng Markillie; Hugh D. Mitchell; Eli J. Borrego; Michael V. Kolomiets; Matthew J. Gaffrey; Galya Orr; E. Wassim Chehab; Wan-Ting Mao; et al. (Planta, 2019)

Relationship between West African ancestry with lung cancer risk and survival in African Americans - Khadijah A. Mitchell; Ebony Shah; Elise D. Bowman; Adriana Zingone; Noah Nichols; Sharon R. Pine; Rick A. Kittles; Bríd M. Ryan (Cancer Causes & Control, 2019)

Different as night and day: Behavioural and life history responses to varied photoperiods in Daphnia magna - Kurt A. Gust; Alan J. Kennedy; Jennifer G. Laird; Mitchell S. Wilbanks; Natalie D. Barker; Xin Guan; Nicolas L. Melby; Lyle D. Burgoon; Michael E. Kjelland; Todd M. Swannack (Molecular Ecology, 2019)
Nearly all animal species have utilized photoperiod to cue seasonal behaviours and life history traits. We investigated photoperiod responses in keystone species, Daphnia magna , to identify molecular processes underlying ecologically important behaviours and traits using functional transcriptomic analyses. Daphnia magna were photoperiod‐entrained immediately posthatch to a standard control photoperiod of 16 light/ 8 dark hours (16L:8D) relative to shorter (4L:20D, 8L:16D, 12L:12L) and longer (20L:4D) day length photoperiods. Short‐day photoperiods induced significantly increased light‐avoidance behaviours relative to controls. Correspondingly, significant differential transcript expression for genes involved in glutamate signalling was observed, a critical signalling pathway in arthropod light‐avoidance behaviour. Additionally, period circadian protein and proteins coding F‐box/LRR‐repeat domains were differentially expressed which are recognized to establish circadian rhythms in arthropods. Indicators of metabolic rate increased in short‐day photoperiods which corresponded with broadscale changes in transcriptional expression across system‐level energy metabolism pathways. The most striking observations included significantly decreased neonate production at the shortest day length photoperiod (4L:20D) and significantly increased male production across short‐day and equinox photoperiods (4L:20D, 8L:16D and 12L:12D). Transcriptional expression consistent with putative mechanisms of male production was observed including photoperiod‐dependent expression of transformer‐2 sex‐determining protein and small nuclear ribonucleoprotein particles (snRNPs) which control splice variant expression for genes like transformer. Finally, increased transcriptional expression of glutamate has also been shown to induce male production in Daphnia pulex via photoperiod‐sensitive mechanisms. Overall, photoperiod entrainment affected molecular pathways that underpin critical behavioural and life history traits in D. magna providing fundamental insights into biological responses to this primary environmental cue.

Ingestion and Absorption of Eucalypt Monoterpenes in the Specialist Feeder, the Koala (Phascolarctos cinereus) - Caroline Marschner; Mark B. Krockenberger; Damien P. Higgins; Christopher Mitchell; Ben D. Moore (Journal of Chemical Ecology, 2019)

Acaricidal efficacy of Calotropis procera (Asclepiadaceae) and Taraxacum officinale (Asteraceae) against Rhipicephalus microplus from Mardan, Pakistan - Adil Khan; Nasreen Nasreen; Sadaf Niaz; Sultan Ayaz; Huma Naeem; Ijaz Muhammad; Fazal Said; Robert D. Mitchell; Adalberto A. Pérez de León; Snehil Gupta; Sachin Kumar (Experimental and Applied Acarology, 2019)

The Effects of Selenomethionine on the Escape Behaviours of Fathead Minnows - Philip J. Anderson; Matthew D. Mitchell; Katherine J. Fedoroff; Douglas P. Chivers; Maud C. O. Ferrari (Archives of Environmental Contamination and Toxicology, 2019)

Dispersal limitations and historical factors determine the biogeography of specialized terrestrial protists - David Singer; Edward A. D. Mitchell; Richard J. Payne; Quentin Blandenier; Clément Duckert; Leonardo D. Fernández; Bertrand Fournier; Cristián E. Hernández; Gustaf Granath; Håkan Rydin; Luca Bragazza; Natalia G. Koronatova; et al. (Molecular Ecology, 2019)
Recent studies show that soil eukaryotic diversity is immense and dominated by micro‐organisms. However, it is unclear to what extent the processes that shape the distribution of diversity in plants and animals also apply to micro‐organisms. Major diversification events in multicellular organisms have often been attributed to long‐term climatic and geological processes, but the impact of such processes on protist diversity has received much less attention as their distribution has often been believed to be largely cosmopolitan. Here, we quantified phylogeographical patterns in Hyalosphenia papilio , a large testate amoeba restricted to Holarctic Sphagnum ‐dominated peatlands, to test if the current distribution of its genetic diversity can be explained by historical factors or by the current distribution of suitable habitats. Phylogenetic diversity was higher in Western North America, corresponding to the inferred geographical origin of the H. papilio complex, and was lower in Eurasia despite extensive suitable habitats. These results suggest that patterns of phylogenetic diversity and distribution can be explained by the history of Holarctic Sphagnum peatland range expansions and contractions in response to Quaternary glaciations that promoted cladogenetic range evolution, rather than the contemporary distribution of suitable habitats. Species distributions were positively correlated with climatic niche breadth, suggesting that climatic tolerance is key to dispersal ability in H. papilio . This implies that, at least for large and specialized terrestrial micro‐organisms, propagule dispersal is slow enough that historical processes may contribute to their diversification and phylogeographical patterns and may partly explain their very high overall diversity.

Deeply conserved susceptibility in a multi‐host, multi‐parasite system - Lisa N. Barrow; Sabrina M. McNew; Nora Mitchell; Spencer C. Galen; Holly L. Lutz; Heather Skeen; Thomas Valqui; Jason D. Weckstein; Christopher C. Witt (Ecology Letters, 2019)
Variation in susceptibility is ubiquitous in multi‐host, multi‐parasite assemblages, and can have profound implications for ecology and evolution in these systems. The extent to which susceptibility to parasites is phylogenetically conserved among hosts can be revealed by analysing diverse regional communities. We screened for haemosporidian parasites in 3983 birds representing 40 families and 523 species, spanning ~ 4500 m elevation in the tropical Andes. To quantify the influence of host phylogeny on infection status, we applied Bayesian phylogenetic multilevel models that included a suite of environmental, spatial, temporal, life history and ecological predictors. We found evidence of deeply conserved susceptibility across the avian tree; host phylogeny explained substantial variation in infection status, and results were robust to phylogenetic uncertainty. Our study suggests that susceptibility is governed, in part, by conserved, latent aspects of anti‐parasite defence. This demonstrates the importance of deep phylogeny for understanding present‐day ecological interactions.

Exposure to antibiotics in the first 24 months of life and neurocognitive outcomes at 11 years of age - R. F. Slykerman; C. Coomarasamy; K. Wickens; J. M. D. Thompson; T. V. Stanley; C. Barthow; J. Kang; J. Crane; E. A. Mitchell (Psychopharmacology, 2019)

Characterization of Male-Produced Aggregation Pheromone of the Bean Flower Thrips Megalurothrips sjostedti (Thysanoptera: Thripidae) - Saliou Niassy; Amanuel Tamiru; James G. C. Hamilton; William D. J. Kirk; Roland Mumm; Cassie Sims; Willem Jan de Kogel; Sunday Ekesi; Nguya K. Maniania; Krishnakumari Bandi; Fraser Mitchell; Sevgan Subramanian (Journal of Chemical Ecology, 2019)

Warm-Season Grass Monocultures and Mixtures for Sustainable Bioenergy Feedstock Production in the Midwest, USA - Moon-Sub Lee; Rob Mitchell; Emily Heaton; Colleen Zumpf; D. K. Lee (BioEnergy Research, 2019)

Development of Near-Infrared Reflectance Spectroscopy (NIRS) Calibrations for Traits Related to Ethanol Conversion from Genetically Variable Napier Grass (Pennisetum purpureum Schum.) - William F. Anderson; Bruce S. Dien; Steven D. Masterson; Robert B. Mitchell (BioEnergy Research, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Less is more: lemurs (Eulemur spp.) may benefit from loss of trichromatic vision - Rachel L. Jacobs; Carrie C. Veilleux; Edward E. Louis; James P. Herrera; Chihiro Hiramatsu; David C. Frankel; Mitchell T. Irwin; Amanda D. Melin; Brenda J. Bradley (Behavioral Ecology and Sociobiology, 2019)

Shark depredation in commercial and recreational fisheries - J. D. Mitchell; D. L. McLean; S. P. Collin; T. J. Langlois (Reviews in Fish Biology and Fisheries, 2018)

Fruit Morphology and Anatomy of the Spondioid Anacardiaceae - Fabiany Herrera; John D. Mitchell; Susan K. Pell; Margaret E. Collinson; Douglas C. Daly; Steven R. Manchester (The Botanical Review, 2018)

Heparin impairs angiogenic signaling and compensatory lung growth after left pneumonectomy - Duy T. Dao; Lorenzo Anez-Bustillos; Jared Ourieff; Amy Pan; Paul D. Mitchell; Hiroko Kishikawa; Gillian L. Fell; Meredith A. Baker; Randolph S. Watnick; Hong Chen; Thomas E. Hamilton; Michael S. Rogers; et al. (Angiogenesis, 2018)

Engaging stakeholders in research to address water–energy–food (WEF) nexus challenges - C. Hoolohan; A. Larkin; C. McLachlan; R. Falconer; I. Soutar; J. Suckling; L. Varga; I. Haltas; A. Druckman; D. Lumbroso; M. Scott; D. Gilmour; et al. (Sustainability Science, 2018)

New records of the rare North American endemic Chara brittonii (Characeae), with comments on its distribution - Kenneth G. Karol; Mitchell S. Alix; Robin W. Scribailo; Paul M. Skawinski; Robin S. Sleith; Joseph A. Sardina; John D. Hall (Brittonia, 2018)

Interdisciplinary Oncology Education: a National Survey of Trainees and Program Directors in the United States - Adil S. Akthar; Christopher D. Hellekson; Sabha Ganai; Olwen M. Hahn; Ronald J. Maggiore; Ezra E. Cohen; Mitchell C. Posner; Steven J. Chmura; Andrew R. Howard; Daniel W. Golden (Journal of Cancer Education, 2018)

The putative leucine sensor Sestrin2 is hyperphosphorylated by acute resistance exercise but not protein ingestion in human skeletal muscle - Nina Zeng; Randall F. D’Souza; Brie Sorrenson; Troy L. Merry; Matthew P. G. Barnett; Cameron J. Mitchell; David Cameron-Smith (European Journal of Applied Physiology, 2018)

Aroclor misidentification in environmental samples: how do we communicate more effectively between the laboratory and the data user? - Mitchell D. Erickson (Environmental Science and Pollution Research, 2018)

An update in international trends in incidence rates of thyroid cancer, 1973–2007 - Benjamin C. James; Janeil M. Mitchell; Heedo D. Jeon; Nektarios Vasilottos; Raymon H. Grogan; Briseis Aschebrook-Kilfoy (Cancer Causes & Control, 2018)

Environmental filtering and phylogenetic clustering correlate with the distribution patterns of cryptic protist species - David Singer; Anush Kosakyan; Christophe V. W. Seppey; Amandine Pillonel; Leonardo D. Fernández; Diego Fontaneto; Edward A. D. Mitchell; Enrique Lara (Ecology, 2018)
The community composition of any group of organisms should theoretically be determined by a combination of assembly processes including resource partitioning, competition, environmental filtering, and phylogenetic legacy. Environmental DNA studies have revealed a huge diversity of protists in all environments, raising questions about the ecological significance of such diversity and the degree to which they obey to the same rules as macroscopic organisms. The fast‐growing cultivable protist species on which hypotheses are usually experimentally tested represent only a minority of the protist diversity. Addressing these questions for the lesser known majority can only be inferred through observational studies. We conducted an environmental DNA survey of the genus Nebela , a group of closely related testate (shelled) amoeba species, in different habitats within Sphagnum ‐dominated peatlands. Identification based on the mitochondrial cytochrome c oxidase 1 gene, allowed species‐level resolution as well as phylogenetic reconstruction. Community composition varied strongly across habitats and associated environmental gradients. Species showed little overlap in their realized niche, suggesting resource partitioning, and a strong influence of environmental filtering driving community composition. Furthermore, phylogenetic clustering was observed in the most nitrogen‐poor samples, supporting phylogenetic inheritance of adaptations in the group of N. guttata . This study showed that the studied free‐living unicellular eukaryotes follow to community assembly rules similar to those known to determine plant and animal communities; the same may be true for much of the huge functional and taxonomic diversity of protists.

Tipping point in plant–fungal interactions under severe drought causes abrupt rise in peatland ecosystem respiration - Vincent E. J. Jassey; Monika K. Reczuga; Małgorzata Zielińska; Sandra Słowińska; Bjorn J. M. Robroek; Pierre Mariotte; Christophe V. W. Seppey; Enrique Lara; Jan Barabach; Michał Słowiński; Luca Bragazza; Bogdan H. Chojnicki; et al. (Global Change Biology, 2018)
Ecosystems are increasingly prone to climate extremes, such as drought, with long‐lasting effects on both plant and soil communities and, subsequently, on carbon (C) cycling. However, recent studies underlined the strong variability in ecosystem's response to droughts, raising the issue of nonlinear responses in plant and soil communities. The conundrum is what causes ecosystems to shift in response to drought. Here, we investigated the response of plant and soil fungi to drought of different intensities using a water table gradient in peatlands—a major C sink ecosystem. Using moving window structural equation models, we show that substantial changes in ecosystem respiration, plant and soil fungal communities occurred when the water level fell below a tipping point of −24 cm. As a corollary, ecosystem respiration was the greatest when graminoids and saprotrophic fungi became prevalent as a response to the extreme drought. Graminoids indirectly influenced fungal functional composition and soil enzyme activities through their direct effect on dissolved organic matter quality, while saprotrophic fungi directly influenced soil enzyme activities. In turn, increasing enzyme activities promoted ecosystem respiration. We show that functional transitions in ecosystem respiration critically depend on the degree of response of graminoids and saprotrophic fungi to drought. Our results represent a major advance in understanding the nonlinear nature of ecosystem properties to drought and pave the way towards a truly mechanistic understanding of the effects of drought on ecosystem processes.

Piscine myocarditis virus detected in corkwing wrasse ( Symphodus melops ) and ballan wrasse ( Labrus bergylta ) - F Scholz; N M Ruane; T Morrissey; M Marcos‐López; S Mitchell; I O'Connor; L Mirimin; E MacCarthy; H D Rodger (Journal of Fish Diseases, 2018)

Screening of new British thraustochytrids isolates for docosahexaenoic acid (DHA) production - Loris Fossier Marchan; Kim J. Lee Chang; Peter D. Nichols; Jane L. Polglase; Wilfrid J. Mitchell; Tony Gutierrez (Journal of Applied Phycology, 2017)

(2E,6Z,9Z)-2,6,9-Pentadecatrienal as a Male-Produced Aggregation-Sex Pheromone of the Cerambycid Beetle Elaphidion mucronatum - Jocelyn G. Millar; Robert F. Mitchell; Linnea R. Meier; Todd D. Johnson; Judith A. Mongold-Diers; Lawrence M. Hanks (Journal of Chemical Ecology, 2017)

Notes on Astronium Jacq. (Anacardiaceae), including a dwarf new species from the Brazilian Shield - John D. Mitchell; Douglas C. Daly (Brittonia, 2017)

Genetic diversity and nitrogen fixation of mesorhizobia symbionts of New Zealand endemic Sophora species - Tuan Dung Nguyen; Peter B. Heenan; Sofie E. De Meyer; Trevor K. James; Wen‐Ming Chen; James D. Morton; Mitchell Andrews (New Zealand Journal of Botany, 2017)
Forty‐four rhizobial isolates from New Zealand endemic Sophora species growing in natural conditions were characterised and the effectiveness of selected isolates with regard to growth and N 2 fixation of different Sophora species was tested. Sequences for the housekeeping genes (concatenated recA , gln11 and rpoB ) of the isolates were diverse but sequences for their symbiosis genes ( nifH and nodC ) were similar. Generally, isolates from the same field site showed similar housekeeping gene sequences. All isolates were Mesorhizobium . Twenty‐six of the isolates aligned with Mesorhizobium species previously isolated from New Zealand native Sophora on the basis of their housekeeping gene sequences, but 18 isolates separated into two groups and a pair of isolates clearly separated from all Mesorhizobium type strains. DNA–DNA hybridisations indicated that isolates in the two groups could belong to two novel Mesorhizobium species. Rhizobial isolates with different housekeeping gene sequences (but similar symbiosis gene sequences) gave similar increases in dry weight and total N content of four Sophora species under glasshouse conditions.

Simultaneous vegetation classification and mapping at large spatial scales - Mitchell B. Lyons; Scott D. Foster; David A. Keith (Journal of Biogeography, 2017)
Aim Multivariate mixture models offer the ability to streamline the typically multi‐stage process of vegetation classification and mapping into a single, simultaneous analytical step. Our aim is to demonstrate the model's utility over large and diverse areas, with comparison to existing classification and mapping conventions. Location New South Wales, Australia. Methods We demonstrate a statistical model that uses both multivariate species data and environmental covariate data to simultaneously classify observations into groups and predict those groups out into environmental and geographical space. We used two large data sets to demonstrate the method: an ~810,000 km 2 area with 4,715 sites and 488 species and a ~220,000 km 2 area with 5,183 sites and 446 species. A range of topographic, terrain, climate and soil predictors were used as environmental variables, including future projected climate variables. Models can be fit with the R package “ RCP mod.” Results The method results in probabilistic memberships to vegetation assemblages, for both the classification and map. There was general agreement between our approach and existing vegetation classification conventions, but we explore some notable differences. We were able to examine the environmental gradients that define the predicted vegetation distributions, as well as make predictions about how the distribution of species assemblages might shift as a result of climate change. Main conclusions Our approach tightens the link between description of biodiversity patterns and their depiction in space, by considering both biotic and spatially explicit abiotic information simultaneously. The method allows uncertainty to be quantified objectively across a consistent set of groups for both vegetation classification and mapping, which is rarely the case in traditional multi‐stage approaches. A simultaneous modelling approach increases capacity to make predictions into varying spatial, temporal and environmental dimensions, providing new ecological insights and increasing capacity for evidence‐based decision making.

Enhanced conscious processing and blindsight-like detection of fear-conditioned stimuli under continuous flash suppression - Joana B. Vieira; Sophia Wen; Lindsay D. Oliver; Derek G. V. Mitchell (Experimental Brain Research, 2017)

Piscirickettsia salmonis infection in cultured lumpfish ( Cyclopterus lumpus L.) - M Marcos‐López; N M Ruane; F Scholz; M Bolton‐Warberg; S O Mitchell; S Murphy O'Sullivan; A Irwin Moore; H D Rodger (Journal of Fish Diseases, 2017)
A Piscirickettsia salmonis infection was diagnosed in lumpfish ( Cyclopterus lumpus L.) juveniles held in a marine research facility on the west coast of Ireland. The main clinical signs and pathology included marked ascites, severe multifocal liver necrosis and severe diffuse inflammation and necrosis of the exocrine pancreas and peri‐pancreatic adipose tissue. Numerous Piscirickettsia ‐like organisms were observed by histopathology in the affected organs, and the bacterial species was characterized by molecular analysis. Sequencing of the partial 16S rDNA gene and internal transcribed spacer region showed the lumpfish sequences to be closely related to previously identified Atlantic salmon ( Salmo salar L.) sequences from Ireland. To the authors’ knowledge, this is the first detection of P. salmonis in lumpfish worldwide. The infection is considered potentially significant in terms of lumpfish health and biosecurity.

Elevated phosphorus: dynamics during four years of green roof development - Mark E. Mitchell; Stephen F. Matter; Richard D. Durtsche; Ishi Buffam (Urban Ecosystems, 2017)

A system to identify inhibitors of mTOR signaling using high-resolution growth analysis in Saccharomyces cerevisiae - Mitchell B. Lee; Daniel T. Carr; Michael G. Kiflezghi; Yan Ting Zhao; Deborah B. Kim; Socheata Thon; Margarete D. Moore; Mary Ann K. Li; Matt Kaeberlein (GeroScience, 2017)

First record of Tetramicra brevifilum in lumpfish ( Cyclopterus lumpus, L.) - F Scholz; E Fringuelli; M Bolton‐Warberg; M Marcos‐López; S Mitchell; P Prodhol; D Moffet; P Savage; S Murphy O'Sullivan; I O′Connor; E McCarthy; H D Rodger (Journal of Fish Diseases, 2017)
A microsporidian species with 98.3–98.4% nucleotide identity to Tetramicra brevifilum ( Journal of Fish Diseases , 3 , 1980, 495) was diagnosed in lumpfish ( Cyclopterus lumpus , L.) broodstock held at a breeding and rearing facility in western Ireland. The fish were wild‐caught from the west coast of Ireland, and the first case was diagnosed one year after capture. Clinical signs included severe bloating, lethargy, exophthalmos, anorexia, white patches on the cornea and externally visible parasitic cysts on skin and fins. Necropsy revealed severe ascites, white nodules and vacuoles in all the internal organs and partial liquefaction of the skeletal muscle. On histological examination, microsporidian xenomas were observed in all internal organs, the skin, skeletal muscle, gills and the eyes. The microsporidian species was identified by molecular analysis and transmission electron microscopy. This is the first record of T. brevifilum infecting lumpfish, and the disease is considered to be of potential significance to the rising aquaculture industry of this species.

Estimating groundwater inflow and leakage outflow for an intermontane lake with a structurally complex geology: Georgetown Lake in Montana, USA - Glenn D. Shaw; Katie L. Mitchell; Christopher H. Gammons (Hydrogeology Journal, 2017)

Odorant receptors and antennal lobe morphology offer a new approach to understanding olfaction in the Asian longhorned beetle - Robert F. Mitchell; Loyal P. Hall; Peter F. Reagel; Duane D. McKenna; Thomas C. Baker; John G. Hildebrand (Journal of Comparative Physiology A, 2017)

Analysis of enteroendocrine cell populations in the human colon - Patricia Martins; Josiane Fakhry; Enio Chaves de Oliveira; Billie Hunne; Linda J. Fothergill; Mitchell Ringuet; Débora d’Ávila Reis; Jens F. Rehfeld; Brid Callaghan; John B. Furness (Cell and Tissue Research, 2017)

Variations in carbon dioxide fluxes within a city landscape: Identifying a vehicular influence - Shannon M. Buckley; Myron J. Mitchell; Patrick J. McHale; Geoffrey D. Millard (Urban Ecosystems, 2016)

Fracked ecology: Response of aquatic trophic structure and mercury biomagnification dynamics in the Marcellus Shale Formation - Christopher James Grant; Allison K. Lutz; Aaron D. Kulig; Mitchell R. Stanton (Ecotoxicology, 2016)

Diet cues alter the development of predator recognition templates in tadpoles - Matthew D. Mitchell; Maud C. O. Ferrari; Tyrone Lucon-Xiccato; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2016)

Water–energy balance, past ecological perturbations and evolutionary constraints shape the latitudinal diversity gradient of soil testate amoebae in south‐western South America - Leonardo D. Fernández; Bertrand Fournier; Reinaldo Rivera; Enrique Lara; Edward A. D. Mitchell; Cristián E. Hernández (Global Ecology and Biogeography, 2016)
Aim To assess the largely neglected patterns and causes of latitudinal diversity gradients in soil protists, using South American testate amoebae as model organisms. Location South‐western South America (SSA). Methods We assessed the relationship among richness, latitude and predictions of eight ecological hypotheses in SSA, a region characterized by harsh abiotic conditions northward and southward from mid‐latitudes. We also examined the patterns of latitudinal variation in species range sizes, species composition and phylogenetic relatedness among species to assess whether the responses of species to current climate rely on evolutionary constraints. Results Richness followed a unimodal trend with abrupt declines northward and southward from mid‐latitudes. This trend was mostly explained by water–energy balance. To our knowledge, this mechanism has never been reported for soil microorganisms before. Species range sizes were larger northward and southward from mid‐latitudes, a pattern which we have called the ‘two‐way Rapoport effect’. Species composition was due to turnover at mid‐latitudes and to nestedness towards low and high latitudes. Species at mid‐latitudes tended to be less related to each other than those at low and high latitudes, supporting the existence of evolutionary constraints to water–energy availability. Main conclusions The unimodal response of species diversity to water and energy availability stems from a combination of the ancestral adaptation of testate amoebae to warm, humid climates and past climate changes that set up permanent harsh abiotic conditions northward and southward from mid‐latitudes. Given that other soil microorganisms also depend on water and energy to survive and reproduce, we predict that the unimodal response to water–energy balance observed will also be valid for a large number of microbial groups in SSA. While this diversity trend may not hold true for testate amoebae from other regions, we predict that their evolutionary constraints to water–energy availability will always produce strong relationships among richness, water and energy at large spatial‐scales.

FG-3019, a Human Monoclonal Antibody Recognizing Connective Tissue Growth Factor, is Subject to Target-Mediated Drug Disposition - Mitchell C. Brenner; Wojciech Krzyzanski; James Z. Chou; Pierre E. Signore; Cyra K. Fung; David Guzman; Dongxia Li; Weihua Zhang; David R. Olsen; Viet-Tam L. Nguyen; Carolyn W. Koo; Mark D. Sternlicht; et al. (Pharmaceutical Research, 2016)

Differential migration and the link between winter latitude, timing of migration, and breeding in a songbird - Bradley K. Woodworth; Amy E. M. Newman; Sheela P. Turbek; Bryant C. Dossman; Keith A. Hobson; Leonard I. Wassenaar; Greg W. Mitchell; Nathaniel T. Wheelwright; D. Ryan Norris (Oecologia, 2016)

Recognition of faces and names: multimodal physiological correlates of memory and executive function - Meghan B. Mitchell; Steven D. Shirk; Donald G. McLaren; Jessica S. Dodd; Ali Ezzati; Brandon A. Ally; Alireza Atri (Brain Imaging and Behavior, 2016)

Dedicated Herbaceous Biomass Feedstock Genetics and Development - W. F. Anderson; G. Sarath; S. Edme; M. D. Casler; R. B. Mitchell; C. M. Tobias; A. L. Hale; S. E. Sattler; J. E. Knoll (BioEnergy Research, 2016)

A legacy of human‐induced ecosystem changes: spatial processes drive the taxonomic and functional diversities of testate amoebae in Sphagnum peatlands of the Galápagos - Bertrand Fournier; Emily E. D. Coffey; W. O. van der Knaap; Leonardo D. Fernández; Anatoly Bobrov; Edward A. D. Mitchell (Journal of Biogeography, 2016)
Aim Our aims were to compare the composition of testate amoeba ( TA ) communities from Santa Cruz Island, Galápagos Archipelago, which are likely in existence only as a result of anthropogenic habitat transformation, with similar naturally occurring communities from northern and southern continental peatlands. Additionally, we aimed at assessing the importance of niche‐based and dispersal‐based processes in determining community composition and taxonomic and functional diversity. Location The humid highlands of the central island of Santa Cruz, Galápagos Archipelago. Methods We survey the alpha, beta and gamma taxonomic and functional diversities of TA , and the changes in functional traits along a gradient of wet to dry habitats. We compare the TA community composition, abundance and frequency recorded in the insular peatlands with that recorded in continental peatlands of Northern and Southern Hemispheres. We use generalized linear models to determine how environmental conditions influence taxonomic and functional diversity as well as the mean values of functional traits within communities. We finally apply variance partitioning to assess the relative importance of niche‐ and dispersal‐based processes in determining community composition. Results TA communities in Santa Cruz Island were different from their Northern Hemisphere and South American counterparts with most genera considered as characteristic for Northern Hemisphere and South American Sphagnum peatlands missing or very rare in the Galápagos. Functional traits were most correlated with elevation and site topography and alpha functional diversity to the type of material sampled and site topography. Community composition was more strongly correlated with spatial variables than with environmental ones. Main conclusions TA communities of the Sphagnum peatlands of Santa Cruz Island and the mechanisms shaping these communities contrast with Northern Hemisphere and South American peatlands. Soil moisture was not a strong predictor of community composition most likely because rainfall and clouds provide sufficient moisture. Dispersal limitation was more important than environmental filtering because of the isolation of the insular peatlands from continental ones and the young ecological history of these ecosystems.

Soil microorganisms behave like macroscopic organisms: patterns in the global distribution of soil euglyphid testate amoebae - Enrique Lara; Ludovic Roussel‐Delif; Bertrand Fournier; David M. Wilkinson; Edward A. D. Mitchell (Journal of Biogeography, 2016)
Aim Patterns of α‐ and β‐diversity of soil protist communities and the factors that shape them remain largely unknown. We undertook a world‐wide survey of forest litter to investigate the patterns of diversity in a group of testate amoebae. We aimed to assess: (1) whether there is a latitudinal gradient in α‐diversity, and (2) whether β‐diversity was correlated solely with environmental factors commonly used in soil biology research or if it was also independently explained by geographical barriers. Location World‐wide. Methods We studied the diversity of Euglyphida, a common group of testate amoebae, in 35 samples of forest litter and moss samples from a global survey, using small subunit rRNA gene sequences. We assessed the relationship between sample α‐diversity and latitude using generalized additive models ( GAM ). Furthermore, we determined the relationships between community composition and geographical models (distance‐based Moran's Eigenvector Maps – db‐ MEM ) using Generalized UniFrac distances ( GU niFrac). We also investigated the relationship between individual measured soil parameters, WorldClim data and diversity (alpha plus beta) using both raw data and synthetic variables obtained through principal components analysis. Results We recorded 245 phylotypes belonging to 6 out of 7 known Euglyphida families, plus four novel deep clades. Euglyphid α‐diversity was positively correlated with temperature and negatively with latitude and litter C/N ratio. Euglyphida community structure was correlated with the spatial eigenvector Db‐ MEM 31, independently of all measured environmental variables. Db‐ MEM 31 corresponds to a natural barrier constituted by the Northern Hemisphere desert belt. Beta diversity was correlated with other environmental variables, such as pH , isothermality and temperature in the coldest month of the year. Main conclusions Soil euglyphid α‐diversity displays a latitudinal gradient, and β‐diversity is not only correlated with climatic and physicochemical parameters but also with geographical barriers. Such patterns of diversity were until recently believed to be characteristic only for macroscopic organisms.

Sharing the load: a survey of parasitism in the invasive freshwater pulmonate, Physa acuta (Hygrophila: Physidae) and sympatric native snail populations - D. Rex Mitchell; Tommy L. F. Leung (Hydrobiologia, 2016)

A major QTL corresponding to the Rk locus for resistance to root-knot nematodes in cowpea (Vigna unguiculata L. Walp.) - Bao-Lam Huynh; William C. Matthews; Jeffrey D. Ehlers; Mitchell R. Lucas; Jansen R. P. Santos; Arsenio Ndeve; Timothy J. Close; Philip A. Roberts (Theoretical and Applied Genetics, 2016)

Network analysis of human fMRI data suggests modular restructuring after simulated acquired brain injury - E. Ruiz Vargas; D. G. V. Mitchell; S. G. Greening; L. M. Wahl (Medical & Biological Engineering & Computing, 2016)

Pathology and mortality associated with the mauve stinger jellyfish P elagia noctiluca in farmed A tlantic salmon S almo salar L. - M Marcos‐López; S O Mitchell; H D Rodger (Journal of Fish Diseases, 2016)

Exploratory study for identifying systemic biomarkers that correlate with pain response in patients with intervertebral disc disorders - K. T. Weber; Shina Satoh; D. Olivier Alipui; Justin Virojanapa; Mitchell Levine; Cristina Sison; Shaheda Quraishi; Ona Bloom; Nadeen O. Chahine (Immunologic Research, 2015)
Molecular events that drive disc damage and low back pain (LBP) may precede clinical manifestation of disease onset and can cause detrimental long-term effects such as disability. Biomarkers serve as objective molecular indicators of pathological processes. The goal of this study is to identify systemic biochemical factors as predictors of response to treatment of LBP with epidural steroid injection (ESI). Since inflammation plays a pivotal role in LBP, this pilot study investigates the effect of ESI on systemic levels of 48 inflammatory biochemical factors (cytokines, chemokines, and growth factors) and examines the relationship between biochemical factor levels and pain or disability in patients with disc herniation (DH), or other diagnoses (Other Dx) leading to low back pain, which included spinal stenosis (SS) and degenerative disc disease (DDD). Study participants ( n = 16) were recruited from a back pain management practice. Pain numerical rating score (NRS), Oswestry Disability Index (ODI), and blood samples were collected pre- and at 7 to 10 days post-treatment. Blood samples were assayed for inflammatory mediators using commercial multiplex assays. Mediator levels were compared pre- and post-treatment to investigate the potential correlations between clinical and biochemical outcomes. Our results indicate that a single ESI significantly decreased systemic levels of SCGF-β and IL-2. Improvement in pain in all subjects was correlated with changes in chemokines (MCP-1, MIG), hematopoietic progenitor factors (SCGF-β), and factors that participate in angiogenesis/fibrosis (HGF), nociception (SCF, IFN-α2), and inflammation (IL-6, IL-10, IL-18, TRAIL). Levels of biochemical mediators varied based on diagnosis of LBP, and changes in pain responses and systemic mediators from pre- to post-treatment were dependent on the diagnosis cohort. In the DH cohort, levels of IL-17 and VEGF significantly decreased post-treatment. In the Other Dx cohort, levels of IL-2Rα, IL-3, and SCGF-β significantly decreased post-treatment. In order to determine whether mediator changes were related to pain, correlations between change in pain scores and change in mediator levels were performed. Subjects with DH demonstrated a profile signature that implicated hematopoiesis factors (SCGF-β, GM-CSF) in pain response, while subjects with Other Dx demonstrated a biomarker profile that implicated chemokines (MCP-1, MIG) and angiogenic factors (HGF, VEGF) in pain response. Our findings provide evidence that systemic biochemical factors in patients with LBP vary by diagnosis, and pain response to treatment is associated with a unique profile of biochemical responses in each diagnosis group. Future hypothesis-based studies with larger subject cohorts are warranted to confirm the findings of this pilot exploratory study.

Environment Has Little Effect on Biomass Biochemical Composition of Miscanthus × giganteus Across Soil Types, Nitrogen Fertilization, and Times of Harvest - Rebecca A. Arundale; Stefan Bauer; Fernanda B. Haffner; Valerie D. Mitchell; Thomas B. Voigt; Stephen P. Long (BioEnergy Research, 2015)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Acute response to cluster sets in trained and untrained men - Jonathan M. Oliver; Andreas Kreutzer; Shane Jenke; Melody D. Phillips; Joel B. Mitchell; Margaret T. Jones (European Journal of Applied Physiology, 2015)

Pack hunting by minute soil testate amoebae: nematode hell is a naturalist's paradise - Edward A. D. Mitchell (Environmental Microbiology, 2015)

Psychopharmacological characterisation of the successive negative contrast effect in rats - C. E. Phelps; E. N. Mitchell; D. J. Nutt; H. M. Marston; E. S. J. Robinson (Psychopharmacology, 2015)

SNP development in North American burying beetles (Coleoptera: Silphidae): a tool to inform conservation decisions - Derek D. Houston; Kevin S. Mitchell; Jared W. Clouse; Peter J. Maughan; J. Curtis Creighton; Ashlee N. Smith; Seth M. Bybee; Mark C. Belk (Conservation Genetics Resources, 2015)

Contemporary evolution of resistance at the major insecticide target site gene Ace‐1 by mutation and copy number variation in the malaria mosquito Anopheles gambiae - David Weetman; Sara N. Mitchell; Craig S. Wilding; Daniel P. Birks; Alexander E. Yawson; John Essandoh; Henry D. Mawejje; Luc S. Djogbenou; Keith Steen; Emily J. Rippon; Christopher S. Clarkson; Stuart G. Field; et al. (Molecular Ecology, 2015)
Functionally constrained genes are ideal insecticide targets because disruption is often fatal, and resistance mutations are typically costly. Synaptic acetylcholinesterase ( AC hE) is an essential neurotransmission enzyme targeted by insecticides used increasingly in malaria control. In Anopheles and Culex mosquitoes, a glycine–serine substitution at codon 119 of the Ace‐1 gene confers both resistance and fitness costs, especially for 119S/S homozygotes. G119S in Anopheles gambiae from Accra (Ghana) is strongly associated with resistance, and, despite expectations of cost, resistant 119S alleles are increasing significantly in frequency. Sequencing of Accra females detected only a single Ace‐1 119S haplotype, whereas 119G diversity was high overall but very low at non‐synonymous sites, evidence of strong purifying selection driven by functional constraint. Flanking microsatellites showed reduced diversity, elevated linkage disequilibrium and high differentiation of 119S, relative to 119G homozygotes across up to two megabases of the genome. Yet these signals of selection were inconsistent and sometimes weak tens of kilobases from Ace‐1 . This unexpected finding is attributable to apparently ubiquitous amplification of 119S alleles as part of a large copy number variant ( CNV ) far exceeding the size of the Ace‐1 gene, whereas 119G alleles were unduplicated. Ace‐1 CNV was detectable in archived samples collected when the 119S allele was rare in Ghana. Multicopy amplification of resistant alleles has not been observed previously and is likely to underpin the recent increase in 119S frequency. The large CNV compromised localization of the strong selective sweep around Ace‐1 , emphasizing the need to integrate CNV analysis into genome scans for selection.

Spatial soil heterogeneity has a greater effect on symbiotic arbuscular mycorrhizal fungal communities and plant growth than genetic modification with B acillus thuringiensis toxin genes - Tanya E. Cheeke; Ursel M. Schütte; Chris M. Hemmerich; Mitchell B. Cruzan; Todd N. Rosenstiel; James D. Bever (Molecular Ecology, 2015)
Maize, genetically modified with the insect toxin genes of B acillus thuringiensis ( Bt ) , is widely cultivated, yet its impacts on soil organisms are poorly understood. Arbuscular mycorrhizal fungi ( AMF ) form symbiotic associations with plant roots and may be uniquely sensitive to genetic changes within a plant host. In this field study, the effects of nine different lines of B t maize and their corresponding non‐ B t parental isolines were evaluated on AMF colonization and community diversity in plant roots. Plants were harvested 60 days after sowing, and data were collected on plant growth and per cent AMF colonization of roots. AMF community composition in roots was assessed using 454 pyrosequencing of the 28 S r RNA genes, and spatial variation in mycorrhizal communities within replicated experimental field plots was examined. Growth responses, per cent AMF colonization of roots and AMF community diversity in roots did not differ between B t and non‐ B t maize, but root and shoot biomass and per cent colonization by arbuscules varied by maize cultivar. Plot identity had the most significant effect on plant growth, AMF colonization and AMF community composition in roots, indicating spatial heterogeneity in the field. Mycorrhizal fungal communities in maize roots were autocorrelated within approximately 1 m, but at greater distances, AMF community composition of roots differed between plants. Our findings indicate that spatial variation and heterogeneity in the field has a greater effect on the structure of AMF communities than host plant cultivar or modification by B t toxin genes.

Living on the continental shelf edge: habitat use of juvenile shortfin makos Isurus oxyrinchus in the Great Australian Bight, southern Australia - Paul J. Rogers; Charlie Huveneers; Brad Page; Simon D. Goldsworthy; Micheal Coyne; Andrew D. Lowther; James G. Mitchell; Laurent Seuront (Fisheries Oceanography, 2015)
We used satellite telemetry data to investigate the movement patterns and habitat use of juvenile shortfin makos Isurus oxyrinchus (Lamnidae) tagged in the Great Australian Bight, southern Australia. Tracking durations ranged from 49–672 days and six deployments were > 1 year. During winter and spring, some shortfin makos migrated to the tropical NE Indian Ocean and Coral Sea, and the Subtropical Front region. One shortfin mako undertook an extended migration of 25 550 km across the Indian Ocean. Areas characterized by sea‐mounts in the NE Indian Ocean, the oceanic Subtropical Front region, and the continental shelf edge (200‐m depth) and slope canyons were visited by several sharks. Juvenile shortfin makos used the outer continental shelf, the shelf edge, the slope and oceanic waters during migrations and mostly exhibited fidelity in the mid‐outer shelf, the shelf edge and slope habitats characterized by high bathymetric relief and oceanographic frontal gradients. Our findings highlighted that the continental shelf and slope and associated submarine canyons of the Great Australian Bight represent ecologically important habitats for juvenile shortfin makos. The findings of this study will be pertinent during future management processes for this highly migratory species in this Southern Hemisphere region.

Association between tobacco use and the upper gastrointestinal microbiome among Chinese men - Emily Vogtmann; Roberto Flores; Guoqin Yu; Neal D. Freedman; Jianxin Shi; Mitchell H. Gail; Bruce A. Dye; Guo-Qing Wang; Vanja Klepac-Ceraj; Bruce J. Paster; Wen-Qiang Wei; Hui-Qin Guo; et al. (Cancer Causes & Control, 2015)

Genetic analysis and molecular mapping of a seedling crown rust resistance gene in oat - Belaghihalli N. Gnanesh; Curt A. McCartney; Peter E. Eckstein; Jennifer W. Mitchell Fetch; Jim G. Menzies; Aaron D. Beattie (Theoretical and Applied Genetics, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Population density of Dall’s sheep in Alaska: effects of predator harvest? - Carl D. Mitchell; Roy Chaney; Ken Aho; John G. Kie; R. Terry Bowyer (Mammal Research, 2015)

Conclusions of the Worldwide Integrated Assessment on the risks of neonicotinoids and fipronil to biodiversity and ecosystem functioning - J. P. van der Sluijs; V. Amaral-Rogers; L. P. Belzunces; M. F. I. J. Bijleveld van Lexmond; J-M. Bonmatin; M. Chagnon; C. A. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; et al. (Environmental Science and Pollution Research, 2015)

Systemic insecticides (neonicotinoids and fipronil): trends, uses, mode of action and metabolites - N. Simon-Delso; V. Amaral-Rogers; L. P. Belzunces; J. M. Bonmatin; M. Chagnon; C. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; D. P. Kreutzweiser; et al. (Environmental Science and Pollution Research, 2015)

Environmental fate and exposure; neonicotinoids and fipronil - J.-M. Bonmatin; C. Giorio; V. Girolami; D. Goulson; D. P. Kreutzweiser; C. Krupke; M. Liess; E. Long; M. Marzaro; E. A. D. Mitchell; D. A. Noome; N. Simon-Delso; et al. (Environmental Science and Pollution Research, 2015)

Plant diversity predicts beta but not alpha diversity of soil microbes across grasslands worldwide - Suzanne M. Prober; Jonathan W. Leff; Scott T. Bates; Elizabeth T. Borer; Jennifer Firn; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Elsa E. Cleland; Nicole M. DeCrappeo; et al. (Ecology Letters, 2015)
Aboveground–belowground interactions exert critical controls on the composition and function of terrestrial ecosystems, yet the fundamental relationships between plant diversity and soil microbial diversity remain elusive. Theory predicts predominantly positive associations but tests within single sites have shown variable relationships, and associations between plant and microbial diversity across broad spatial scales remain largely unexplored. We compared the diversity of plant, bacterial, archaeal and fungal communities in one hundred and forty‐five 1 m 2 plots across 25 temperate grassland sites from four continents. Across sites, the plant alpha diversity patterns were poorly related to those observed for any soil microbial group. However, plant beta diversity (compositional dissimilarity between sites) was significantly correlated with the beta diversity of bacterial and fungal communities, even after controlling for environmental factors. Thus, across a global range of temperate grasslands, plant diversity can predict patterns in the composition of soil microbial communities, but not patterns in alpha diversity.

Shoreline rotation and response to nourishment of a gravel embayed beach using a low-cost video monitoring technique: San Michele-Sassi Neri, Central Italy - Mitchell D. Harley; Umberto Andriolo; Clara Armaroli; Paolo Ciavola (Journal of Coastal Conservation, 2014)

Spring ice formation on goose neck collars: effects on body condition and survival in Greenland white-fronted geese Anser albifrons flavirostris - Anthony D. Fox; Alyn J. Walsh; Mitch D. Weegman; Stuart Bearhop; Carl Mitchell (European Journal of Wildlife Research, 2014)

Switchgrass Response to Nitrogen Fertilizer Across Diverse Environments in the USA: a Regional Feedstock Partnership Report - C. O. Hong; V. N. Owens; D. Bransby; R. Farris; J. Fike; E. Heaton; S. Kim; H. Mayton; R. Mitchell; D. Viands (BioEnergy Research, 2014)

Quantifying the impact of environmental variables upon catch per unit effort of the blue shark Prionace glauca in the western English Channel - J. D. Mitchell; K. J. Collins; P. I. Miller; L. A. Suberg (Journal of Fish Biology, 2014)
The effect of environmental variables on blue shark Prionace glauca catch per unit effort ( CPUE ) in a recreational fishery in the western English Channel, between June and September 1998–2011, was quantified using generalized additive models ( GAMs ). Sea surface temperature ( SST ) explained 1·4% of GAM deviance, and highest CPUE occurred at 16·7° C, reflecting the optimal thermal preferences of this species. Surface chlorophyll a concentration ( CHL ) significantly affected CPUE and caused 27·5% of GAM deviance. Additionally, increasing CHL led to rising CPUE , probably due to higher productivity supporting greater prey biomass. The density of shelf‐sea tidal mixing fronts explained 5% of GAM deviance, but was non‐significant, with increasing front density negatively affecting CPUE. Time‐lagged frontal density significantly affected CPUE, however, causing 12·6% of the deviance in a second GAM and displayed a positive correlation. This outcome suggested a delay between the evolution of frontal features and the subsequent accumulation of productivity and attraction of higher trophic level predators, such as P. glauca .

Comprehensive Analysis of Monomeric Phenolics in Dilute Acid Plant Hydrolysates - Valerie D. Mitchell; Caroline M. Taylor; Stefan Bauer (BioEnergy Research, 2014)

Secondary cell wall composition and candidate gene expression in developing willow (Salix purpurea) stems - Yongfang Wan; Cristina Gritsch; Theodora Tryfona; Mike J. Ray; Ambrose Andongabo; Keywan Hassani-Pak; Huw D. Jones; Paul Dupree; Angela Karp; Peter R. Shewry; Rowan A. C. Mitchell (Planta, 2014)

Wnt5a, TLR2 and TLR4 are elevated in advanced human atherosclerotic lesions - Ramiro Malgor; Pooja M. Bhatt; Beth A. Connolly; Denise L. Jacoby; Kyle J. Feldmann; Mitchell J. Silver; Masato Nakazawa; Kelly D. McCall; Douglas J. Goetz (Inflammation Research, 2014)

When depth is no refuge: cumulative thermal stress increases with depth in Bocas del Toro, Panama - B. P. Neal; C. Condit; G. Liu; S. dos Santos; M. Kahru; B. G. Mitchell; D. I. Kline (Coral Reefs, 2014)

Seasonal Changes in Shoot and Root Nitrogen Distribution in Switchgrass (Panicum virgatum) - Sandra Wayman; Richard D. Bowden; Robert B. Mitchell (BioEnergy Research, 2014)

Impaired learning of predators and lower prey survival under elevated CO 2 : a consequence of neurotransmitter interference - Douglas P. Chivers; Mark I. McCormick; Göran E. Nilsson; Philip L. Munday; Sue‐Ann Watson; Mark G. Meekan; Matthew D. Mitchell; Katherine C. Corkill; Maud C. O. Ferrari (Global Change Biology, 2014)
Ocean acidification is one of the most pressing environmental concerns of our time, and not surprisingly, we have seen a recent explosion of research into the physiological impacts and ecological consequences of changes in ocean chemistry. We are gaining considerable insights from this work, but further advances require greater integration across disciplines. Here, we showed that projected near‐future CO 2 levels impaired the ability of damselfish to learn the identity of predators. These effects stem from impaired neurotransmitter function; impaired learning under elevated CO 2 was reversed when fish were treated with gabazine, an antagonist of the GABA ‐A receptor – a major inhibitory neurotransmitter receptor in the brain of vertebrates. The effects of CO 2 on learning and the link to neurotransmitter interference were manifested as major differences in survival for fish released into the wild. Lower survival under elevated CO 2 , as a result of impaired learning, could have a major influence on population recruitment.

6-Pentyl-2H-pyran-2-one: A Potent Peach-Derived Kairomone for New Zealand Flower Thrips, Thrips obscuratus - A. M. El-Sayed; V. J. Mitchell; D. M. Suckling (Journal of Chemical Ecology, 2014)

Isolation of human lymphatic malformation endothelial cells, their in vitro characterization and in vivo survival in a mouse xenograft model - Zerina Lokmic; Geraldine M. Mitchell; Nicholas Koh Wee Chong; Jacqueline Bastiaanse; Yi-Wen Gerrand; Yiping Zeng; Elizabeth D. Williams; Anthony J. Penington (Angiogenesis, 2014)

Land‐sharing versus land‐sparing logging: reconciling timber extraction with biodiversity conservation - David P. Edwards; James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; David J. R. Andrews; Mia A. Derhé; Teegan D. S. Docherty; Wayne W. Hsu; Simon L. Mitchell; Takahiro Ota; Leah J. Williams; et al. (Global Change Biology, 2014)
Selective logging is a major driver of rainforest degradation across the tropics. Two competing logging strategies are proposed to meet timber demands with the least impact on biodiversity: land sharing, which combines timber extraction with biodiversity protection across the concession; and land sparing, in which higher intensity logging is combined with the protection of intact primary forest reserves. We evaluate these strategies by comparing the abundances and species richness of birds, dung beetles and ants in Borneo, using a protocol that allows us to control for both timber yield and net profit across strategies. Within each taxonomic group, more species had higher abundances with land‐sparing than land‐sharing logging, and this translated into significantly higher species richness within land‐sparing concessions. Our results are similar when focusing only on species found in primary forest and restricted in range to Sundaland, and they are independent of the scale of sampling. For each taxonomic group, land‐sparing logging was the most promising strategy for maximizing the biological value of logging operations.

The incidence of PALB2 c.3113G>A in women with a strong family history of breast and ovarian cancer attending familial cancer centres in Australia - Zhi L. Teo; Sarah D. Sawyer; Paul A. James; Gillian Mitchell; Alison H. Trainer; Geoffrey J. Lindeman; Kylie Shackleton; Linda Cicciarelli; Melissa C. Southey (Familial Cancer, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Disturbance and the role of refuges in mediterranean climate streams - Belinda J. Robson; Edwin T. Chester; Bradley D. Mitchell; Ty G. Matthews (Hydrobiologia, 2013)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Ecology of testate amoebae in peatlands of central China and development of a transfer function for paleohydrological reconstruction - Yangmin Qin; Edward A. D. Mitchell; Mariusz Lamentowicz; Richard J. Payne; Enrique Lara; Yansheng Gu; Xianyu Huang; Hongmei Wang (Journal of Paleolimnology, 2013)

Holarctic phylogeography of the testate amoeba H yalosphenia papilio (Amoebozoa: Arcellinida) reveals extensive genetic diversity explained more by environment than dispersal limitation - Thierry J. Heger; Edward A. D. Mitchell; Brian S. Leander (Molecular Ecology, 2013)
Although free‐living protists play essential roles in aquatic and soil ecology, little is known about their diversity and phylogeography, especially in terrestrial ecosystems. We used mitochondrial cytochrome c oxidase subunit 1 (COI) gene sequences to investigate the genetic diversity and phylogeography of the testate amoeba morphospecies Hyalosphenia papilio in 42 Sphagnum (moss) ‐ dominated peatlands in North America, Europe and Asia. Based on ≥1% sequence divergence threshold, our results from single‐cell PCRs of 301 individuals revealed 12 different genetic lineages and both the general mixed Yule‐coalescent (GMYC) model and the automatic barcode gap discovery (ABGD) methods largely support the hypothesis that these 12 H. papilio lineages correspond to evolutionary independent units (i.e. cryptic species). Our data also showed a high degree of genetic heterogeneity within different geographical regions. Furthermore, we used variation partitioning based on partial redundancy analyses ( pRDA ) to evaluate the contributions of climate and dispersal limitations on the distribution patterns of the different genetic lineages. The largest fraction of the variation in genetic lineage distribution was attributed to purely climatic factors (21%), followed by the joint effect of spatial and bioclimatic factors (13%), and a purely spatial effect (3%). Therefore, these data suggest that the distribution patterns of H. papilio genetic lineages in the Northern Hemisphere are more influenced by climatic conditions than by dispersal limitations.

Trophic Flexibility and the Persistence of Understory Birds in Intensively Logged Rainforest - DAVID P. EDWARDS; PAUL WOODCOCK; ROB J. NEWTON; FELICITY A. EDWARDS; DAVID J. R. ANDREWS; TEEGAN D. S. DOCHERTY; SIMON L. MITCHELL; TAKAHIRO OTA; SUZAN BENEDICK; SIMON H. BOTTRELL; KEITH C. HAMER (Conservation Biology, 2013)
Effects of logging on species composition in tropical rainforests are well known but may fail to reveal key changes in species interactions. We used nitrogen stable‐isotope analysis of 73 species of understory birds to quantify trophic responses to repeated intensive logging of rainforest in northern Borneo and to test 4 hypotheses: logging has significant effects on trophic positions and trophic‐niche widths of species, and the persistence of species in degraded forest is related to their trophic positions and trophic‐niche widths in primary forest. Species fed from higher up the food chain and had narrower trophic‐niche widths in degraded forest. Species with narrow trophic‐niche widths in primary forest were less likely to persist after logging, a result that indicates a higher vulnerability of dietary specialists to local extinction following habitat disturbance. Persistence of species in degraded forest was not related to a species’ trophic position. These results indicate changes in trophic organization that were not apparent from changes in species composition and highlight the importance of focusing on trophic flexibility over the prevailing emphasis on membership of static feeding guilds. Our results thus support the notion that alterations to trophic organization and interactions within tropical forests may be a pervasive and functionally important hidden effect of forest degradation. Flexibilidad Trófica y la Persistencia de Aves de Sotobosque en un Bosque Lluvioso Talado Intensivamente

The Feasibility of Producing Adequate Feedstock for Year-Round Cellulosic Ethanol Production in an Intensive Agricultural Fuelshed - Daniel R. Uden; Rob B. Mitchell; Craig R. Allen; Qingfeng Guan; Tim D. McCoy (BioEnergy Research, 2013)

Using fisheries by‐catch data to predict octocoral habitat suitability around South Georgia - Michelle L. Taylor; Chris Yesson; David J. Agnew; Rebecca E. Mitchell; Alex D. Rogers (Journal of Biogeography, 2013)
Aim For many deep‐sea fisheries, there is an urgent management requirement for information on the presence of vulnerable marine ecosystems ( VME s). Gathering deep‐sea data using conventional techniques can be expensive and time‐consuming. One way to provide a relatively rapid assessment of VME presence is to use data from fisheries by‐catch and historical scientific observations. Our aim was to predict suitable habitat for octocorals around South Georgia and to estimate the extent to which octocoral habitat is currently protected by fisheries management measures. In addition, we attempted to determine the types of terrain in which octocorals and fishing activities occur. Location South Georgia, sub‐Antarctic. Methods A terrain map of South Georgia was created using Benthic Terrain Modeler ( BTM ). Georeferenced octocoral data were combined with environmental layers to create an octocoral habitat suitability map using ecological niche factor analysis ( ENFA ). Results Most octocoral by‐catch samples originated from narrow crest (an area representing shelf break and moraines) and steep (continental) slope terrains. Calcite saturation state and apparent oxygen utilization ( AOU ) were the most influential environmental parameters in determining highly suitable octocoral habitat. The ENFA model highlighted shelf‐break areas to be highly suitable habitat for octocorals and that 38% of this habitat around South Georgia lies within areas currently protected by fisheries management; a further 20% is below the 2000‐m fishing depth, meaning effectively that 58% of predicted highly suitable octocoral habitat is currently protected. Although these results indicate protection levels for octocoral habitat well above international standards/targets, the fishery remains active within a relatively concentrated shelf area at 700–2000 m, potentially having a large impact on the 42% of highly suitable octocoral habitat predicted to lie at these depths. Main conclusions This research demonstrates the potential for using fisheries by‐catch data to create habitat suitability maps that can inform fisheries management and future research.

Ontogenetic differences in chemical alarm cue production determine antipredator responses and learned predator recognition - Matthew D. Mitchell; Mark I. McCormick (Behavioral Ecology and Sociobiology, 2013)

Differential patterns of mono- and sesquiterpenes with leaf ontogeny influence pharmaceutical oil yield in Eucalyptus polybractea R.T. Baker - Jason Q. D. Goodger; Madeline C. Mitchell; Ian E. Woodrow (Trees, 2013)

Relationships between testate amoeba communities and water quality in Lake Donghu, a large alkaline lake in Wuhan, China - Yangmin Qin; Bertrand Fournier; Enrique Lara; Yansheng Gu; Hongmei Wang; Yongde Cui; Xiaoke Zhang; Edward A. D. Mitchell (Frontiers of Earth Science, 2013)

Chemistry and Microbial Functional Diversity Differences in Biofuel Crop and Grassland Soils in Multiple Geographies - Lidia S. Watrud; Jay R. Reichman; Michael A. Bollman; Bonnie M. Smith; E. Henry Lee; Julie D. Jastrow; Michael D. Casler; Harold P. Collins; Steven Fransen; Robert B. Mitchell; Vance N. Owens; Brent Bean; et al. (BioEnergy Research, 2013)

The Effect of Nonideal Cascade Impactor Stage Collection Efficiency Curves on the Interpretation of the Size of Inhaler-Generated Aerosols - D. L. Roberts; J. P. Mitchell (AAPS PharmSciTech, 2013)

Pharmacokinetic interaction studies of co-administration of ticagrelor and atorvastatin or simvastatin in healthy volunteers - Renli Teng; Patrick D. Mitchell; Kathleen A. Butler (European Journal of Clinical Pharmacology, 2013)

Rate of onset of inhibition of gut-wall and hepatic CYP3A by clarithromycin - Sara K. Quinney; Srikar R. Malireddy; Raj Vuppalanchi; Mitchell A. Hamman; Naga Chalasani; J. Christopher Gorski; Stephen D. Hall (European Journal of Clinical Pharmacology, 2013)

Remucal et al. Respond: - Jonathan M. Remucal; Jason D. McGee; Matthew M. Fehrenbacher; Constance Best; Robert J. Mitchell (Journal of Forestry, 2013)

Good Cascade Impactor Practice (GCIP) and Considerations for “In-Use” Specifications - S. C. Nichols; J. P. Mitchell; C. M. Shelton; D. L. Roberts (AAPS PharmSciTech, 2013)

Broad‐scale movements and pelagic habitat of the dusky shark C archarhinus obscurus off S outhern A ustralia determined using pop‐up satellite archival tags - Paul J. Rogers; Charlie Huveneers; Simon D. Goldsworthy; James G. Mitchell; Laurent Seuront (Fisheries Oceanography, 2013)
We investigated the broad‐scale movements and pelagic habitats of large juvenile dusky sharks ( Carcharhinus obscurus ) off Southern Australia. Pop‐up satellite archival tags ( PSAT s) were deployed on three large juvenile dusky sharks (∼2.2–2.6 m total length) for 6 months in Spencer Gulf during 2010. Tagged dusky sharks all migrated westward and across the Great Australian Bight ( GAB ) during autumn to offshore shelf waters off Western Australia. Estimated minimum distances travelled ranged from 1760 to 2736 km. Depths occupied by tagged dusky sharks ranged from the surface to 355 m. The most common thermal ranges occupied were 19–22°C. Broad‐scale movements of large juvenile dusky sharks across the continental shelves combined with periods of residency in semi‐protected gulf waters indicated that a multi‐jurisdictional management approach may be appropriate for this species.

Cuticular hydrocarbons as a basis for chemosensory self‐referencing in crickets: a potentially universal mechanism facilitating polyandry in insects - Carie B. Weddle; Sandra Steiger; Christopher G. Hamaker; Geoffrey D. Ower; Christopher Mitchell; Scott K. Sakaluk; John Hunt (Ecology Letters, 2013)
Females of many species obtain benefits by mating polyandrously, and often prefer novel males over previous mates. However, how do females recognise previous mates, particularly in the face of cognitive constraints? Female crickets appear to have evolved a simple but effective solution: females imbue males with their own cuticular hydrocarbons ( CHC s) at mating and utilise chemosensory self‐referencing to recognise recent mates. Female CHC profiles exhibited significant additive genetic variation, demonstrating that genetically unique chemical cues are available to support chemosensory self‐referencing. CHC profiles of males became more similar to those of females after mating, indicating physical transfer of CHC s between individuals during copulation. Experimental perfuming of males with female CHC s resulted in a female aversion to males bearing chemical cues similar to their own. Chemosensory self‐referencing, therefore, could be a widespread mechanism by which females increase the diversity of their mating partners.

Factors modulating cottongrass seedling growth stimulation to enhanced nitrogen and carbon dioxide: compensatory tradeoffs in leaf dynamics and allocation to meet potassium-limited growth - Andy Siegenthaler; Alexandre Buttler; Philippe Grosvernier; Jean-Michel Gobat; Mats B. Nilsson; Edward A. D. Mitchell (Oecologia, 2013)

Compositional variations and morphological evolution in platinum beach placers, southern New Zealand - D. Craw; M. Mitchell; R. McCann; A. Reay (Mineralium Deposita, 2013)

Current state of knowledge regarding the world’s wetlands and their future under global climate change: a synthesis - Wolfgang J. Junk; Shuqing An; C. M. Finlayson; Brij Gopal; Jan Květ; Stephen A. Mitchell; William J. Mitsch; Richard D. Robarts (Aquatic Sciences, 2013)

A weight-of-evidence review of colorectal cancer in pesticide applicators: the agricultural health study and other epidemiologic studies - Dominik D. Alexander; Douglas L. Weed; Pamela J. Mink; Meghan E. Mitchell (International Archives of Occupational and Environmental Health, 2012)

Seaweed Allelopathy Against Coral: Surface Distribution of a Seaweed Secondary Metabolite by Imaging Mass Spectrometry - Tiffany D. Andras; Troy S. Alexander; Asiri Gahlena; R. Mitchell Parry; Facundo M. Fernandez; Julia Kubanek; May D. Wang; Mark E. Hay (Journal of Chemical Ecology, 2012)

Development of a novel histopathological gill scoring protocol for assessment of gill health during a longitudinal study in marine-farmed Atlantic salmon (Salmo salar) - Susan O. Mitchell; Emily J. Baxter; Celia Holland; Hamish D. Rodger (Aquaculture International, 2012)

Securing the Demographic and Genetic Future of Tuatara through Assisted Colonization - KIMBERLY A. MILLER; HILARY C. MILLER; JENNIFER A. MOORE; NICOLA J. MITCHELL; ALISON CREE; FRED W. ALLENDORF; STEPHEN D. SARRE; SUSAN N. KEALL; NICOLA J. NELSON (Conservation Biology, 2012)
Climate change poses a particular threat to species with fragmented distributions and little or no capacity to migrate. Assisted colonization, moving species into regions where they have not previously occurred, aims to establish populations where they are expected to survive as climatic envelopes shift. However, adaptation to the source environment may affect whether species successfully establish in new regions. Assisted colonization has spurred debate among conservation biologists and ecologists over whether the potential benefits to the threatened species outweigh the potential disruption to recipient communities. In our opinion, the debate has been distracted by controversial examples, rather than cases where assisted colonization may be a viable strategy. We present a strategic plan for the assisted migration of tuatara ( Sphenodon punctatus ), an endemic New Zealand reptile. The plan includes use of extant populations as reference points for comparisons with assisted‐colonization populations with respect to demography, phenotypic plasticity, and phenology; optimization of genetic variation; research to fill knowledge gaps; consideration of host and recipient communities; and inclusion of stakeholders in the planning stage. When strategically planned and monitored, assisted colonization could meet conservation and research goals and ultimately result in the establishment of long‐term sustainable populations capable of persisting during rapid changes in climate.

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Evaluation of a digital microfluidic real-time PCR platform to detect DNA of Candida albicans in blood - W. A. Schell; J. L. Benton; P. B. Smith; M. Poore; J. L. Rouse; D. J. Boles; M. D. Johnson; B. D. Alexander; V. K. Pamula; A. E. Eckhardt; M. G. Pollack; D. K. Benjamin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

2,3-Hexanediols as Sex Attractants and a Female-produced Sex Pheromone for Cerambycid Beetles in the Prionine Genus Tragosoma - Ann M. Ray; James D. Barbour; J. Steven McElfresh; Jardel A. Moreira; Ian Swift; Ian M. Wright; Alenka Žunič; Robert F. Mitchell; Elizabeth E. Graham; Ronald L. Alten; Jocelyn G. Millar; Lawrence M. Hanks (Journal of Chemical Ecology, 2012)

The first report of Spondias native to Madagascar: Spondias tefyi, sp. nov. (Anacardiaceae) - John D. Mitchell; Douglas C. Daly; Armand Randrianasolo (Brittonia, 2012)

Physiologic implications of metal-ion transport by ZIP14 and ZIP8 - Supak Jenkitkasemwong; Chia-Yu Wang; Bryan Mackenzie; Mitchell D. Knutson (BioMetals, 2012)

The effect of experimental warming and precipitation change on proteolytic enzyme activity: positive feedbacks to nitrogen availability are not universal - Edward R. Brzostek; John M. Blair; Jeffrey S. Dukes; Serita D. Frey; Sarah E. Hobbie; Jerry M. Melillo; Robert J. Mitchell; Elise Pendall; Peter B. Reich; Gaius R. Shaver; Artur Stefanski; Mark G. Tjoelker; et al. (Global Change Biology, 2012)
Nitrogen regulates the E arth's climate system by constraining the terrestrial sink for atmospheric CO 2 . Proteolytic enzymes are a principal driver of the within‐system cycle of soil nitrogen, yet there is little to no understanding of their response to climate change. Here, we use a single methodology to investigate potential proteolytic enzyme activity in soils from 16 global change experiments. We show that regardless of geographical location or experimental manipulation (i.e., temperature, precipitation, or both), all sites plotted along a single line relating the response ratio of potential proteolytic activity to soil moisture deficit, the difference between precipitation and evapotranspiration. In particular, warming and reductions in precipitation stimulated potential proteolytic activity in mesic sites – temperate and boreal forests, arctic tundra – whereas these manipulations suppressed potential activity in dry grasslands. This study provides a foundation for a simple representation of the impacts of climate change on a central component of the nitrogen cycle.

Peracetic acid is effective for controlling fungus on channel catfish eggs - D L Straus; T Meinelt; B D Farmer; A J Mitchell (Journal of Fish Diseases, 2012)
Peracetic acid (PAA) is a relatively new compound suggested for use to treat pathogens in aquaculture. It is approved for use in Europe, but not in the United States. This study determined the effectiveness of PAA for fungus control on channel catfish, Ictalurus punctatus (Rafinesque), eggs. The study consisted of five PAA concentrations (2.5, 5, 10, 15 and 20 mg L −1 ) and an untreated control in a flow‐through system. A single spawn was used for each replication ( N = 4). Eggs were treated twice daily until the embryos developed eyes. When hatching was complete for all viable eggs, fry were counted to determine the percent survival in each treatment. Fungal growth was severe in the untreated controls resulting in 11% survival. Treatments of 2.5, 5 and 10 mg L −1 PAA were significantly different from the controls ( P 0.05). The highest percent survival of hatched fry was with 5 mg L −1 PAA administered twice daily; the 2.5 mg L −1 PAA treatment had slightly less survival, but gives a higher margin of safety in case of treatment error. Very little fungus was present in treatments receiving 2.5 mg L −1 PAA or higher, and concentrations of 15 and 20 mg L −1 PAA were toxic to the eggs. The mean survivals in the 0, 2.5, 5, 10, 15 and 20 mg L −1 PAA treatments were 11%, 60%, 63%, 62%, 32% and 0%, respectively. Therefore, PAA may be a compound that merits further investigations regarding its use in U.S. aquaculture.

Evaluation of methods for achieving stable INR in healthy subjects during a multiple-dose warfarin study - Jill C. Chappell; Gemma Dickinson; Malcolm I. Mitchell; Harry Haber; Yan Jin; Evelyn D. Lobo (European Journal of Clinical Pharmacology, 2012)

Explaining the variation in the soil microbial community: do vegetation composition and soil chemistry explain the same or different parts of the microbial variation? - Ruth Joy Mitchell; Alison J. Hester; Colin D. Campbell; Stephen J. Chapman; Clare M. Cameron; Richard L. Hewison; Jackie M. Potts (Plant and Soil, 2012)

Genetically Engineered Mesenchymal Stem Cells as a Proposed Therapeutic for Huntington’s Disease - Scott D. Olson; Kari Pollock; Amal Kambal; Whitney Cary; Gaela-Marie Mitchell; Jeremy Tempkin; Heather Stewart; Jeannine McGee; Gerhard Bauer; Hyun Sook Kim; Teresa Tempkin; Vicki Wheelock; et al. (Molecular Neurobiology, 2012)

Effect of dietary iron deficiency and overload on the expression of ZIP metal-ion transporters in rat liver - Hyeyoung Nam; Mitchell D. Knutson (BioMetals, 2012)

Elevated skeletal muscle apoptotic signaling following glutathione depletion - Aaron D. Dam; Andrew S. Mitchell; James W. E. Rush; Joe Quadrilatero (Apoptosis, 2012)

Modelling the effect of size on the aerial dispersal of microorganisms - David M. Wilkinson; Symeon Koumoutsaris; Edward A. D. Mitchell; Isabelle Bey (Journal of Biogeography, 2012)
Aim We investigate the long‐standing question of whether the small size of microbes allows most microbial species to colonize all suitable sites around the globe or whether their ranges are limited by opportunities for dispersal. In this study we use a modelling approach to investigate the effect of size on the probability of between‐continent dispersal using virtual microorganisms in a global model of the Earth’s atmosphere. Location Global. Methods We use a computer model of global atmospheric circulation to investigate the effect of microbe size (effective diameters of 9, 20, 40 and 60 μm) on the probability of aerial dispersal. Results We found that for smaller microbes, once airborne, dispersal is remarkably successful over a 1‐year period. The most striking results are the extensive within‐hemisphere distribution of virtual microbes of 9 and 20 μm diameter and the lack of dispersal between the Northern and Southern Hemispheres during the year‐long time‐scale of our simulations. Main conclusions Above a diameter of 20 μm wind dispersal of virtual microbes between continents becomes increasingly unlikely, and it does not occur at all (within our simulated 1‐year period) for those of 60 μm diameter. Within our simulation, the success of small microbes in long‐distance dispersal is due both to their greater abundance and to their longer time in the atmosphere – once airborne – compared with larger microbes.

Transient changes in transpiration, and stem and soil CO2 efflux in longleaf pine (Pinus palustris Mill.) following fire-induced leaf area reduction - Barton D. Clinton; Chris A. Maier; Chelcy R. Ford; Robert J. Mitchell (Trees, 2011)

Euleria (Anacardiaceae) is Picrasma (Simaroubaceae): The genus Picrasma in Cuba - Wm. Wayt Thomas; John D. Mitchell; Susan Pell; Alfredo Noa Monzón (Brittonia, 2011)

Non-infectious gill disorders of marine salmonid fish - Hamish D. Rodger; Louise Henry; Susan O. Mitchell (Reviews in Fish Biology and Fisheries, 2011)

A new species of Comocladia (Anacardiaceae) from Belize and Guatemala - Daniel E. Atha; John D. Mitchell; Susan K. Pell; Francine R. Camacho (Brittonia, 2011)

Structured decision making as a proactive approach to dealing with sea level rise in Florida - Julien Martin; Paul L. Fackler; James D. Nichols; Bruce C. Lubow; Mitchell J. Eaton; Michael C. Runge; Bradley M. Stith; Catherine A. Langtimm (Climatic Change, 2011)

Enzymatic digestion in stomachless fishes: how a simple gut accommodates both herbivory and carnivory - Ryan D. Day; Donovan P. German; Jennifer M. Manjakasy; Ingrid Farr; Mitchell Jay Hansen; Ian R. Tibbetts (Journal of Comparative Physiology B, 2011)

Resistance of red mangrove (Rhizophora mangle L.) seedlings to deflection and extraction - Sophie D. Boizard; Stephen J. Mitchell (Trees, 2011)

Quantifying Actual and Theoretical Ethanol Yields for Switchgrass Strains Using NIRS Analyses - Kenneth P. Vogel; Bruce S. Dien; Hans G. Jung; Michael D. Casler; Steven D. Masterson; Robert B. Mitchell (BioEnergy Research, 2011)

Exercise-associated hyponatremia: the influence of pre-exercise carbohydrate status combined with high volume fluid intake on sodium concentrations and fluid balance - Kimberly A. Hubing; John T. Bassett; Laura R. Quigg; Melody D. Phillips; James J. Barbee; Joel B. Mitchell (European Journal of Applied Physiology, 2011)

Evaluation of radiative transfer models in atmospheric profiling with broadband infrared radiance measurements - Xin Jin; Jun Li; Timothy J. Schmit; Mitchell D. Goldberg (International Journal of Remote Sensing, 2011)

Applications of polychlorinated biphenyls - Mitchell D. Erickson; Robert G. Kaley (Environmental Science and Pollution Research, 2011)

Seroprevalence of seasonal and pandemic influenza A viruses in domestic cats - Jonathan A. McCullers; Lee-Ann Van De Velde; Ronald D. Schultz; Cristen G. Mitchell; C. R. Halford; Kelli L. Boyd; Stacey Schultz-Cherry (Archives of Virology, 2011)

Increased relative abundance of an invasive competitor for pollination, Lythrum salicaria, reduces seed number in Mimulus ringens - Rebecca J. Flanagan; Randall J. Mitchell; Jeffrey D. Karron (Oecologia, 2010)

Plant nitrogen and phosphorus limitation in 98 North American grassland soils - Joseph Mitchell Craine; Randall D. Jackson (Plant and Soil, 2010)

Response of testate amoeba assemblages to environmental and climatic changes during the Lateglacial–Holocene transition at Lake Lautrey (Jura Mountains, eastern France) - Adeline A. J. Wall; Michel Magny; Edward A. D. Mitchell; Boris Vannière; Daniel Gilbert (Journal of Quaternary Science, 2010)
We tested the response of lacustrine testate amoebae (thecamoebians) to climate and environmental changes for the Lateglacial–Holocene transition. The palaeoenvironmental history of the study site (Lake Lautrey, Jura Mountains, eastern France) was previously established based on high‐resolution multi‐proxy studies of the same core. The present study is characterised by a high taxonomic resolution (54 taxa), inclusion of small species (down to 25 µm) and high total counts (>500 individuals per sample on average). Changes in the composition of testate amoeba assemblages (dominant species and assemblage structure), as well as in the accumulation rate (tests cm −2 a −1 ), corresponded to major climatic phases (i.e. Oldest Dryas, Bølling–Allerød Interstadial, Younger Dryas, Preboreal) as well as changes in organic matter inputs. Furthermore, decreases in the accumulation rate characterised minor short‐lived cooling events, such as Older Dryas event or Gerzensee oscillation. However, the Preboreal oscillation, which was well registered by other proxies at Lake Lautrey, could not be recognised in the testate amoeba record. This work demonstrates that lacustrine testate amoebae can be used for palaeoclimatic and palaeoecological reconstructions. Nevertheless, a better understanding of the relation between climate, organic matter and lacustrine testate amoebae requires further high‐resolution studies based on multi‐proxy approaches and the development of appropriate modern analogues. Copyright © 2010 John Wiley & Sons, Ltd.

Temporal and spatial changes in cell wall composition in developing grains of wheat cv. Hereward - G. A. Toole; G. Le Gall; I. J. Colquhoun; C. Nemeth; L. Saulnier; A. Lovegrove; T. Pellny; M. D. Wilkinson; J. Freeman; R. A. C. Mitchell; E. N. C. Mills; P. R. Shewry (Planta, 2010)

Is vegetation composition or soil chemistry the best predictor of the soil microbial community? - Ruth J. Mitchell; Alison J. Hester; Colin D. Campbell; Stephen J. Chapman; Clare M. Cameron; Richard L. Hewison; Jackie M. Potts (Plant and Soil, 2010)

Species-specific effects of polyploidisation and plant traits of Centaurea maculosa and Senecio inaequidens on rhizosphere microorganisms - Aurélie Thébault; Beat Frey; Edward A. D. Mitchell; Alexandre Buttler (Oecologia, 2010)

Body mass index, effect modifiers, and risk of pancreatic cancer: a pooled study of seven prospective cohorts - Li Jiao; Amy Berrington de Gonzalez; Patricia Hartge; Ruth M. Pfeiffer; Yikyung Park; D. Michal Freedman; Mitchell H. Gail; Michael C. R. Alavanja; Demetrius Albanes; Laura E. Beane Freeman; Wong-Ho Chow; Wen-Yi Huang; et al. (Cancer Causes & Control, 2010)

Epitheliocystis in Atlantic salmon, Salmo salar L., farmed in fresh water in Ireland is associated with ‘ Candidatus Clavochlamydia salmonicola’ infection - S O Mitchell; T Steinum; H Rodger; C Holland; K Falk; D J Colquhoun (Journal of Fish Diseases, 2010)
Intracellular inclusions containing chlamydia‐like organisms are frequently observed in the gill epithelial cells of Atlantic salmon, Salmo salar L., cultured in fresh water in Ireland. In this study, the causative agent was identified in four separate freshwater sites, using 16s rRNA sequencing, as ‘ Candidatus Clavochlamydia salmonicola’. Histopathology and real‐time (RT) PCR were used to further assess infections. The prevalence of infection ranged from 75–100% between sites and infection intensity was highly variable. No significant lesions were associated with these infections. As a diagnostic tool, RT‐PCR proved marginally more sensitive than histopathology. The fate of ‘ Candidatus Clavochlamydia salmonicola’ in Atlantic salmon post‐seawater transfer was investigated in a 12‐week marine longitudinal study. Both RT‐PCR and histopathological examination indicate that the organism disappears from the gills 4–6 weeks post‐transfer.

Interannual variability and controls of the Sydney wave climate - Mitchell D. Harley; Ian L. Turner; Andrew D. Short; Roshanka Ranasinghe (International Journal of Climatology, 2010)
A multi‐decadal beach survey dataset at a coastal embayment in Sydney, Australia, identifies erosion/accretion cycles coinciding with phase shifts in the El Niño/Southern Oscillation (ENSO). In an attempt to explain the processes governing these cycles, this study explores the interannual variability and controls of the Sydney wave climate using ECMWF ERA‐40 and corrected ERA‐40 (C‐ERA‐40) reanalysis data. Comparisons with wave measurements collected by the Sydney waverider buoy show that these datasets represent the Sydney wave climate reasonably well, although westerly waves are significantly over‐predicted. Removing these values strengthens correlations between predicted and measured wave heights. A summary of the Sydney wave climate from 1957 to 2002 is presented, which highlights the high degree of variability in storm events. Controls of interannual variability are investigated by comparing values in Sydney with regional mean sea level pressure anomalies, the Southern Oscillation Index (SOI) and the Southern Annular Mode (SAM). Austral summer wave heights over this 45‐year period increase/decrease with positive/negative phases of the SOI and the SAM. An inverse relationship is found between wave directions and the SOI for the austral autumn and spring; and between wave directions and the SAM for the austral winter. Variability of storm events in Sydney is significantly correlated with the SOI, but not the SAM. In particular, La Niña phases are generally associated with longer duration, higher‐energy events from a more easterly direction when compared to those during El Niño phases. Copyright © 2009 Royal Meteorological Society

Factors Influencing Fish Distributions in Shallow Lakes in Prairie and Prairie-Parkland Regions of Minnesota, USA - Brian R. Herwig; Kyle D. Zimmer; Mark A. Hanson; Melissa L. Konsti; Jerry A. Younk; Robert W. Wright; Sean R. Vaughn; Mitchell D. Haustein (Wetlands, 2010)

A. L. Young, The history, use, disposition and environmental fate of Agent Orange - Mitchell D. Erickson (Environmental Science and Pollution Research, 2010)

Testate amoeba analysis of lake sediments: impact of filter size and total count on estimates of density, species richness and assemblage structure - A. A. J. Wall; D. Gilbert; M. Magny; E. A. D. Mitchell (Journal of Paleolimnology, 2010)

The cag PAI is intact and functional but HP0521 varies significantly in Helicobacter pylori isolates from Malaysia and Singapore - H.-M. A. Schmidt; S. Andres; C. Nilsson; Z. Kovach; N. O. Kaakoush; L. Engstrand; K.-L. Goh; K. M. Fock; D. Forman; H. Mitchell (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

A near‐annual palaeohydrological study based on testate amoebae from a sub‐alpine mire: surface wetness and the role of climate during the instrumental period - Mariusz Lamentowicz; Willem Van Der Knaap; Łukasz Lamentowicz; Jacqueline F. N. Van Leeuwen; Edward A. D. Mitchell; Tomasz Goslar; Christian Kamenik (Journal of Quaternary Science, 2010)
We present the first testate amoeba‐based palaeohydrological reconstruction from the Swiss Alps, and the first depth to the water table (DWT) calibration dataset for this region. Compared to existing models, our new calibration dataset performs well (RMSEP = 4.88), despite the length of the water table gradient covered (53 cm). The present‐day topography and vegetation of the study mire Mauntschas suggest that it is partly ombrotrophic (large Sphagnum fuscum hummocks, one of which was the coring site) but mostly under the minerotrophic influence of springs in the mire and runoff from the surrounding area. Ombrotrophic Sphagnum fuscum hummocks developed at the sampling site only during the last 50 years, when testate amoebae indicate a shift towards dry and/or acid conditions. Prior to AD 1950 the water table was much higher, suggesting that the influence of the mineral‐rich water prevented the development of ombrotrophic hummocks. The reconstructed DWT correlated with Pinus cembra pollen accumulation rates, suggesting that testate amoebae living on the mire and P. cembra growing outside of it partly respond to the same factor(s). Finally, temperature trends from the nearby meteorological station paralleled trends in reconstructed DWT. However, contrary to other studies made on raised bogs of northwestern Europe, the highest correlation was observed for winter temperature, despite the fact that testate amoebae would more logically respond to moisture conditions during the growing season. The observed correlation with winter temperature might reflect a control of winter severity on surface moisture during at least the first part of the growing season, through snow melt and soil frost phenomena influencing run‐off. More ecohydrological work on sub‐alpine mires is needed to understand the relationships between climate, testate amoebae and peatland development. Copyright © 2009 John Wiley & Sons, Ltd.

How many is enough? Determining optimal count totals for ecological and palaeoecological studies of testate amoebae - Richard J. Payne; Edward A. D. Mitchell (Journal of Paleolimnology, 2009)

Glucokinase regulatory protein gene polymorphism affects postprandial lipemic response in a dietary intervention study - Haiqing Shen; Toni I. Pollin; Coleen M. Damcott; John C. McLenithan; Braxton D. Mitchell; Alan R. Shuldiner (Human Genetics, 2009)

Demography and population viability of polar bears in the Gulf of Boothia, Nunavut - Mitchell K. Taylor; Jeff Laake; Philip D. McLoughlin; H. Dean Cluff; François Messier (Marine Mammal Science, 2009)
We estimated demographic parameters and harvest risks for polar bears ( Ursus maritimus ) inhabiting the Gulf of Boothia, Nunavut, from 1976 to 2000. We computed survival and abundance from capture–recapture and recovery data (630 marks) using a Burnham joint live–dead model implemented in program MARK. Annual mean total survival (including harvest) was 0.889 ± 0.179 (x̄± 1 SE) for cubs, 0.883 ± 0.087 for subadults (ages 1–4), 0.919 ± 0.044 for adult females, and 0.917 ± 0.041 for adult males. Abundance in the last 3 yr of study was 1,592 ± 361 bears. Mean size of newborn litters was 1.648 ± 0.098 cubs. By age 7, 0.97 ± 0.30 of available females were producing litters. Harvest averaged 38.4 ± 4.2 bears/year in the last 5 yr of study; however, the 2002–2007 kill averaged 56.4 bears/yr. We used a harvested Population Viability Analysis (PVA) to examine impacts of increasing rates of harvest. We estimated the current population growth rate, λ H , to be 1.025 ± 0.032. Although this suggests the population is growing, progressive environmental changes may require more frequent population inventory studies to maintain the same levels of harvest risk.

Biofuels, Bioenergy, and Bioproducts from Sustainable Agricultural and Forest Crops - Michael D. Casler; Rob Mitchell; Jim Richardson; Ronald S. Zalesny (BioEnergy Research, 2009)

The curse of taxonomic uncertainty in biogeographical studies of free‐living terrestrial protists: a case study of testate amoebae from Amsterdam Island - T. J. Heger; E. A. D. Mitchell; P. Ledeganck; S. Vincke; B. Van de Vijver; L. Beyens (Journal of Biogeography, 2009)
Aim A current debate in microbial biogeography contrasts two views concerning the distribution of free‐living microorganisms. The first view assumes a ubiquitous distribution, while the second assumes that at least some species have limited geographical distributions. We tested for limited geographical distributions by identifying testate amoebae morphospecies from an extremely remote oceanic island where the potential for endemism is high. Location Amsterdam Island, Indian Ocean. Methods Sixty moss and water samples collected from the top of the volcano to the lowland were investigated for their testate amoeba content. Due to taxonomic uncertainties among the Argynnia ( Nebela ) dentistoma species complex (including A. antarctica ), we also performed light and scanning electron microscopy investigations on the shell ultrastructure and biometric analyses on several specimens of this taxon. Results We identified a total of 43 testate amoeba taxa belonging to 15 genera. Only four testate amoeba taxa had previously been recorded on this island. Testate amoeba communities of Amsterdam Island are dominated by cosmopolitan ubiquitous euglyphid taxa such as Trinema lineare , Assulina muscorum and Corythion dubium . The length and width ranges for Argynnia dentistoma on Amsterdam Island overlap with other records of this species and of A. antarctica , suggesting that A. antarctica is not a distinct taxon. Main conclusions Although Amsterdam Island is among the most remote islands in the world, an extensive inventory of testate amoeba morphospecies provided no clear evidence for endemism. On the one hand, our detailed morphometric analysis of the A. dentistoma complex revealed that A. antarctica , a morphospecies previously suggested to display endemism, cannot be confidently distinguished from the cosmopolitan morphospecies A. dentistoma . On the other hand, five morphotaxa could not be identified with certainty and might represent new species, potentially with limited distribution. These examples illustrate how taxonomic uncertainties undermine biogeographical studies of testate amoebae. In order to allow better interpretation of morphology‐based testate amoeba distribution data, an assessment of genetic diversity among and within morphotaxa in relation to geographical distance for some common testate amoebae should be given high priority.

Attraction of New Zealand Flower Thrips, Thrips obscuratus, to cis-Jasmone, a Volatile Identified from Japanese Honeysuckle Flowers - A. M. El-Sayed; V. J. Mitchell; G. F. McLaren; L. M. Manning; B. Bunn; D. M. Suckling (Journal of Chemical Ecology, 2009)

Possible impacts of anthropogenic and natural aerosols on Australian climate: a review - Leon D. Rotstayn; Melita D. Keywood; Bruce W. Forgan; Albert J. Gabric; Ian E. Galbally; John L. Gras; Ashok K. Luhar; Grant H. McTainsh; Ross M. Mitchell; Stuart A. Young (International Journal of Climatology, 2009)
A review is presented of the aerosol–climate interaction with specific focus on the Australian region. The uncertainties associated with this interaction are much larger than those associated with greenhouse gases or other forcing agents, and are currently a major obstacle in climate‐change research. However, new research suggests that aerosol effects are of comparable importance to greenhouse gases as a driver of recent climate trends in the Southern Hemisphere, including Australia. A significant new result from climate modelling is that anthropogenic aerosol over Asia affects meridional temperature gradients and atmospheric circulation, and may have caused an increase in rainfall over north‐western Australia. Global ocean circulation provides another mechanism whereby aerosol changes in the Northern Hemisphere can affect climate in the Southern Hemisphere, suggesting an urgent need for further targeted studies using coupled ocean‐atmosphere global climate models. To better model climate variability and climate change in the Australian region, more research is needed into the sources of aerosol and their precursors, their atmospheric distributions and transformations, and how to incorporate these processes robustly in global climate models (GCMs). The following priorities are suggested for further research in Australia linking aerosol observations and modelling: natural aerosol over the Southern Ocean, tropical biomass‐burning aerosol in Indonesia and Australia, secondary organic aerosol (SOA) from volatile organic compounds (VOCs), wind‐blown dust and modulation of rainfall by anthropogenic aerosol. Copyright © 2008 Royal Meteorological Society

Phylogenetic relationships of Geranium species indigenous to New Zealand - A. D. Mitchell; P. B. Heenan; A. M. Paterson (New Zealand Journal of Botany, 2009)
New Zealand species of Geranium are shown to be closely related, forming a monophyletic group. Relationships inferred from Bayesian and NeighborNet analyses of internal and external transcribed spacer sequences generally agreed and were congruent with those inferred from study of morphological characters. Two groups of species (G. brevicaule and G. retrorsum groups) are well supported based on morphology and DNA sequence data. A third group, referred to as the G. microphyllum group, is recognised based on morphology but is only partially supported by the DNA sequence data. The DNA sequence and morphological variability in each of the G. brevicaule, G. microphyllum , and G. retrorsum groups support the recognition of additional taxonomic entities from New Zealand, but further study is required to address these issues. Furthermore, additional sampling of Australian and South American species of Geranium must be carried out before a taxonomic re‐evaluation can be made of sections Andina and Chilensia .

Energetics and development of incipient colonies of the harvester termite, Trinervitermes trinervoides (Sjöstedt) (Termitidae, Nasutitermitinae) - R. A. Adam; J. D. Mitchell (Insectes Sociaux, 2009)

Evaluation of potassium permanganate against an experimental subacute infection of Flavobacterium columnare in channel catfish, Ictalurus punctatus (Rafinesque) - A M Darwish; A J Mitchell; D L Straus (Journal of Fish Diseases, 2009)
An experiment was performed to evaluate the efficacy of potassium permanganate (KMnO 4 ) as a prophylactic and therapeutic treatment of an experimental subacute infection of Flavobacterium columnare in channel catfish, Ictalurus punctatus . Fish were cutaneously abraded and divided into five treatment groups: (i) challenged by waterborne exposure to F. columnare and not treated with KMnO 4 (positive control), (ii) challenged and simultaneously treated with KMnO 4, (iii) challenged and treated with KMnO 4 at 1, 6 and 9 days post‐challenge, (iv) not challenged and treated with KMnO 4 at 1, 6 and 9 days post‐challenge (first negative control) and (v) not challenged and not treated (second negative control). The dosing of KMnO 4 was 2.0 mg L −1 above the potassium permanganate demand for 2 h duration. The survival of the group challenged and simultaneously treated with KMnO 4 (99%) was significantly higher than the positive control (78%) and was not significantly different from the negative control groups. The challenged fish treated with KMnO 4 post‐challenge had 7% higher survival than the positive control (85% compared with 78%), but that difference was not statistically significant. The results demonstrate that KMnO 4 has a clear prophylactic value but probably a marginal therapeutic value once the infection has established.

Risk Management in the Pharmaceutical Product Development Process - Matthew H. Hulbert; Liam C. Feely; Eugene L. Inman; Alton D. Johnson; Albert S. Kearney; James Michaels; Michael Mitchell; Elena Zour (Journal of Pharmaceutical Innovation, 2008)

Potential implications of differential preservation of testate amoeba shells for paleoenvironmental reconstruction in peatlands - Edward A. D. Mitchell; Richard J. Payne; Mariusz Lamentowicz (Journal of Paleolimnology, 2008)

Testate amoebae analysis in ecological and paleoecological studies of wetlands: past, present and future - Edward A. D. Mitchell; Daniel J. Charman; Barry G. Warner (Biodiversity and Conservation, 2008)

Regional-scale models for relating land cover to basin surface-water quality using remotely sensed data in a GIS - V. L. Versace; D. Ierodiaconou; F. Stagnitti; A. J. Hamilton; M. T. Walter; B. Mitchell; A.-M. Boland (Environmental Monitoring and Assessment, 2008)

Increased efficacy of μ-opioid agonist-induced antinociception by metabotropic glutamate receptor antagonists in C57BL/6 mice: comparison with (−)-6-phosphonomethyl-deca-hydroisoquinoline-3-carboxylic acid (LY235959) - Bradford D. Fischer; Laurence L. Miller; Fredrick E. Henry; Mitchell J. Picker; Linda A. Dykstra (Psychopharmacology, 2008)

The Use of Routine Process Capability for the Determination of Process Parameter Criticality in Small-molecule API Synthesis - Kevin D. Seibert; Shanthi Sethuraman; Jerry D. Mitchell; Kristi L. Griffiths; Bernard McGarvey (Journal of Pharmaceutical Innovation, 2008)

Biosynthesis of Dibenzyl Trisulfide (DTS) from somatic embryos and rhizogenous/embryogenic callus derived from Guinea hen weed (Petiveria alliacea L.) leaf explants - S. A. Webster; S. A. Mitchell; W. A. Gallimore; L. A. D. Williams; M. H. Ahmad (In Vitro Cellular & Developmental Biology - Plant, 2008)

Population parameters and harvest risks for polar bears (Ursus maritimus) of Kane Basin, Canada and Greenland - Mitchell K. Taylor; Jeff Laake; Philip D. McLoughlin; H. Dean Cluff; Erik W. Born; Aqqalu Rosing-Asvid; François Messier (Polar Biology, 2008)

A powder neutron diffraction study of the crystal structure of the fluoroperovskite NaMgF3 (neighborite) from 300 to 3.6 K - Roger H. Mitchell; Malcolm Alexander; Lachlan M. D. Cranswick; Ian P. Swainson (Physics and Chemistry of Minerals, 2007)

Iron limitation across chlorophyll gradients in the southern Drake Passage: Phytoplankton responses to iron addition and photosynthetic indicators of iron stress - Brian M. Hopkinson; B. Greg Mitchell; Rick A. Reynolds; Haili Wang; Karen E. Selph; Christopher I. Measures; Christopher D. Hewes; Osmund Holm-Hansen; Katherine A. Barbeau (Limnology and Oceanography, 2007)
Processes influencing phytoplankton bloom development in the southern Drake Passage were studied using shipboard iron‐enrichment incubations conducted across a surface chlorophyll gradient near the Antarctic Peninsula, in a region of water mass mixing. Iron incubation assays showed that Antarctic Circumpolar Current (ACC) waters were severely iron limited, while shelf waters with high ambient iron concentrations (1–2 nmol L −1 ) were iron replete, demonstrating that mixing of the two water masses is a plausible mechanism for generation of the high phytoplankton biomass observed downstream of the Antarctic Peninsula. In downstream highchlorophyll mixed waters, phytoplankton growth rates were also iron limited, although responses to iron addition were generally more moderate as compared to ACC waters. Synthesizing results from all experiments, significant correlations were found between the initial measurements of Photosystem II (PSII) parameters ( F v :F m , σ PSII , and p ) and the subsequent responses of these waters to iron addition. These correlations indicate that PSII parameters can be used to assess the degree of iron stress experienced in these waters and likely in other regions where photoinhibition and nitrogen stress are not confounding factors.

Influence of fresh water discharge on nutrient distribution in a macrotidal lagoon, West Sussex, UK - S. B. Mitchell; A. Theodoridou; D. J. Pope (Hydrobiologia, 2007)

Scale-specific correlations between habitat heterogeneity and soil fauna diversity along a landscape structure gradient - Adam J. Vanbergen; Allan D. Watt; Ruth Mitchell; Anne-Marie Truscott; Stephen C. F. Palmer; Eva Ivits; Paul Eggleton; T. Hefin Jones; José Paulo Sousa (Oecologia, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Urban Influences on Stream Chemistry and Biology in the Big Brushy Creek Watershed, South Carolina - Gregory P. Lewis; Jennifer D. Mitchell; C. Brannon Andersen; Dennis C. Haney; Min-Ken Liao; Kenneth A. Sargent (Water, Air, & Soil Pollution, 2007)

Nitrogen decreases and precipitation increases ectomycorrhizal extramatrical mycelia production in a longleaf pine forest - Stephanie E. Sims; Joseph J. Hendricks; Robert J. Mitchell; Kevin A. Kuehn; Stephen D. Pecot (Mycorrhiza, 2007)

Stereo cloud‐top heights and cloud fraction retrieval from ATSR‐2 - J.‐P. Muller; M.‐A. Denis; R. D. Dundas; K. L. Mitchell; C. Naud; H. Mannstein (International Journal of Remote Sensing, 2007)

Natural variation and conservation of Lepidium sisymbrioides Hook, f. and L. solandri Kirk (Brassicaceae) in South Island, New Zealand, based on morphological and DNA sequence data - P. B. Heenan; A. D. Mitchell; P. A. McLenachan; P. J. Lockhart; P. J. de Lange (New Zealand Journal of Botany, 2007)
The South Island, New Zealand, endemics Lepidium sisymbrioides and L. solandri are accepted at species rank. L. solandri Kirk is reinstated and includes L. matau Petrie in synonymy, and L. kawarau is reduced to synonymy of L. sisymbrioides . Twenty‐nine floral and vegetative morphological characters were measured and used for analyses of character variation and principal components analysis. Leaf characters proved to be the most useful in distinguishing between L. sisymbrioides and L. solandri , with 12 of the 15 leaf characters having significantly different means. Only 7 of the 14 floral characters included in the study have significantly different means. In comparison to L. solandri, L. sisymbrioides has longer and narrower terminal and primary pinnae and cauline leaves, more secondary pinnae and cauline leaf lobes, less hairy sepals and ovaries, narrower ovaries, and shorter filaments. L. sisymbrioides occurs on rock outcrops in the upper Manuherikia, Waitaki, and Kawarau river valleys. L. solandri grows mainly on alluvium and outwash gravels in semi‐arid parts of inland Canterbury and Central Otago. DNA sequence data from ITS, ETS, and trnL‐trnF markers were used to examine phylogenetic patterns in L. sisymbrioides and L. solandri , and the related species L. kirkii, L. naufragorum , and L. tenuicaule . There is substantial variation in these markers in L. sisymbrioides and L. solandri , and this is considered to be due to introgression from other species of Lepidium , such as L. kirkii and L. tenuicaule . Much of the variation in the ETS sequences occurs in samples of L. sisymbrioides and L. solandri from the Manuherikia River valley, and this can be attributed to geneflow with the sympatric L. kirkii . Lepidium sisymbrioides and L. solandri are considered to be “Acutely Threatened, Nationally Endangered” using the New Zealand threatened plant classification criteria. In this assessment both species are considered to be data poor. Further field survey for new populations is required.

Phylogeny of Bonatea (Orchidaceae: Habenariinae) based on molecular and morphological data - M. E. Ponsie; A. Mitchell; T. J. Edwards; S. D. Johnson (Plant Systematics and Evolution, 2007)

Neutron diffraction determination of the cell dimensions and thermal expansion of the fluoroperovskite KMgF3 from 293 to 3.6 K - Roger H. Mitchell; Lachlan M. D. Cranswick; Ian Swainson (Physics and Chemistry of Minerals, 2006)

Currents, Eddies, and a "Fish Story" in the Southwestern Japan/East Sea - D. Randolph Watts; Mark Wimbush; Karen Tracey; William Teague; Jae-Hun Park; Douglas Mitchell; Jong-Hwan Yoon; Moon-Sik Suk; Kyung-Il Chang (Oceanography, 2006)

Association of a polymorphism in the betacellulin gene with type 1 diabetes mellitus in two populations - Kristi D. Silver; Victoria L. Magnuson; Magdalena Tolea; Jian Wang; William A. Hagopian; Braxton D. Mitchell (Journal of Molecular Medicine, 2006)

Biotic interactions and plant invasions - Charles E. Mitchell; Anurag A. Agrawal; James D. Bever; Gregory S. Gilbert; Ruth A. Hufbauer; John N. Klironomos; John L. Maron; William F. Morris; Ingrid M. Parker; Alison G. Power; Eric W. Seabloom; Mark E. Torchin; et al. (Ecology Letters, 2006)
Introduced plant populations lose interactions with enemies, mutualists and competitors from their native ranges, and gain interactions with new species, under new abiotic conditions. From a biogeographical perspective, differences in the assemblage of interacting species, as well as in abiotic conditions, may explain the demographic success of the introduced plant populations relative to conspecifics in their native range. Within invaded communities, the new interactions and conditions experienced by the invader may influence both its demographic success and its effects on native biodiversity. Here, we examine indirect effects involving enemies, mutualists and competitors of introduced plants, and effects of abiotic conditions on biotic interactions. We then synthesize ideas building on Darwin's idea that the kinds of new interactions gained by an introduced population will depend on its relatedness to native populations. This yields a heuristic framework to explain how biotic interactions and abiotic conditions influence invader success. We conclude that species introductions generally alter plants’ interactions with enemies, mutualists and competitors, and that there is increasing evidence that these altered interactions jointly influence the success of introduced populations.

Evaluation of a component of the cloud response to climate change in an intercomparison of climate models - K. D. Williams; M. A. Ringer; C. A. Senior; M. J. Webb; B. J. McAvaney; N. Andronova; S. Bony; J. -L. Dufresne; S. Emori; R. Gudgel; T. Knutson; B. Li; et al. (Climate Dynamics, 2006)

Contrasting stream water NO 3 − and Ca 2+ in two nearly adjacent catchments: the role of soil Ca and forest vegetation - SHEILA F. CHRISTOPHER; BLAIR D. PAGE; JOHN L. CAMPBELL; MYRON J. MITCHELL (Global Change Biology, 2006)
Two nearly adjacent subcatchments, located in the Adirondack Mountains of New York State, US, with similar atmospheric inputs of N (0.6 kmol ha −1 yr −1 ), but markedly different stream water solute concentrations, provided a unique opportunity to evaluate the mechanisms causing this variation. Subcatchment 14 (S14) had much greater stream water Ca 2+ and NO 3 − concentrations (851 and 73 μmol c L −1 , respectively) than Subcatchment 15 (S15) (427 and 26 μmol c L −1 , respectively). To elucidate factors affecting the variability in stream water concentrations, soil and forest floor samples from each subcatchment were analyzed for total elemental cations and extractable N species. Mineral soil samples were also analyzed for exchangeable cations. Tree species composition was characterized in each subcatchment and potential differences in land use history and hydrology were also assessed. Compared with S15, soils in S14 had significantly higher total elemental Ca 2+ in the forest floor (380 vs. 84 μmol g −1 ), Bs horizon (e.g. 1361 vs. 576 μmol g −1 ) and C horizon (1340 vs. 717 μmol g −1 ). Exchangeable Ca 2+ was also significantly higher in the mineral soil (64 μmol g −1 in S14 vs. 8 μmol g −1 in S15). Extractable NO 3 − was higher in S14 compared with S15 in both the forest floor (0.1 vs. 0.01 μmol g −1 ) and Bs horizon (0.2 vs. 0.07 μmol g −1 ) while extractable NH 4 + was higher in S14 vs. S15 in the forest floor (7 vs. 5 μmol g −1 ). The total basal area of ‘base‐rich indicator’ tree species (e.g. sugar maple, American basswood, eastern hophornbeam) was significantly greater in S14 compared with S15, which had species characteristic of sites with lower base concentrations (e.g. American beech and eastern white pine). The disparity in stream water Ca 2+ and NO 3 − , concentrations and fluxes between S14 and S15 were explained by differences in tree species composition and soil properties rather than differences in land use or hydrology. The marked difference in soil Ca 2+ concentrations in S14 vs. S15 corresponded to the higher stream water Ca 2+ and the larger contribution of base‐rich tree species to the overstory biomass in S14. Soil under such species is associated with higher net mineralization and nitrification and likely contributed to the higher NO 3 − concentrations in the drainage waters of S14 vs. S15. Studies investigating differences in spatial and temporal patterns of the effects of chronic N deposition on surface water chemistry need to account for changes in tree species composition and how vegetation composition is influenced by soil properties, as well as climatic and biotic changes.

Explicit and parameterized episodes of warm-season precipitation over the continental United States - Changhai Liu; Mitchell W. Moncrieff; John D. Tuttle; Richard E. Carbone (Advances in Atmospheric Sciences, 2006)

Towards evaluating cloud response to climate change using clustering technique identification of cloud regimes - Keith D. Williams; Catherine A. Senior; Anthony Slingo; John F. B. Mitchell (Climate Dynamics, 2005)

An improved method of constructing a database of monthly climate observations and associated high-resolution grids - Timothy D. Mitchell; Philip D. Jones (International Journal of Climatology, 2005)

PUP PRODUCTION AND POPULATION TRENDS OF THE AUSTRALIAN FUR SEAL (ARCTOCEPHALUS PUSILLUS DORIFERUS) - Roger Kirkwood; Rosemary Gales; Aleks Terauds; John P. Y. Arnould; David Pemberton; Peter D. Shaughnessy; Anthony T. Mitchell; John Gibbens (Marine Mammal Science, 2005)

The effects of diazepam on human self-aggressive behavior - Mitchell E. Berman; Gabriele D. Jones; Michael S. McCloskey (Psychopharmacology, 2005)

Oligogenic combinations associated with breast cancer risk in women under 53years of age - Christopher E. Aston; David A. Ralph; Dominique P. Lalo; Sharmila Manjeshwar; Bobby A. Gramling; Daniele C. DeFreese; Amy D. West; Dannielle E. Branam; Linda F. Thompson; Melissa A. Craft; Debra S. Mitchell; Craig D. Shimasaki; et al. (Human Genetics, 2005)

Decadal Current Variations in the Southwestern Japan/East Sea - William J. Teague; Gregg A. Jacobs; Douglas A. Mitchell; Mark Wimbush; D. Randolph Watts (Journal of Oceanography, 2004)

Limited effects of Antarctic ozone depletion on sea urchin development - D. Karentz; I. Bosch; D.M. Mitchell (Marine Biology, 2004)

Antidepressant-like effects of the nociceptin/orphanin FQ receptor antagonist UFP-101: new evidence from rats and mice - E. C. Gavioli; C. W. Vaughan; G. Marzola; R. Guerrini; V. A. Mitchell; S. Zucchini; T. C. M. De Lima; G. A. Rae; S. Salvadori; D. Regoli; G. Calo’ (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Arthropodium bifurcatum (Asparagaceae), a new species from northern New Zealand - P. B. Heenan; A. D. Mitchell; P. J. de Lange (New Zealand Journal of Botany, 2004)
Anthropodium bifurcatum is a new species described from northern New Zealand, being currently known from a number of mainland sites as well as offshore islands, including the Poor Knights Islands and Three Kings Islands. It is segregated from A. cirratum and distinguished from that species by its thicker and upright leaves with a fleshy white midrib, abaxial surface of the leaves with irregular protrusions, bifurcate flower bracts, and larger fruit. Amplified Fragment Length Polymorphism DNA data are congruent with morphology in supporting the revised classification. A. bifurcatum is considered to have a conservation status of “Gradual Decline” using the New Zealand Threat Classification System.

Microsatellite identification and characterization in peanut (A. hypogaea L.) - M. E. Ferguson; M. D. Burow; S. R. Schulze; P. J. Bramel; A. H. Paterson; S. Kresovich; S. Mitchell (Theoretical and Applied Genetics, 2004)

Fine Root Carbon Allocation and Fates in Longleaf Pine Forests - Durwin C. Carter; Joseph J. Hendricks; Robert J. Mitchell; Stephen D. Pecot (Forest Science, 2004)
The patterns and mechanistic controls of fine root production and mortality in a 19-year-old longleaf pine (Pinus palustris Miller) plantation were assessed using minirhizotrons in a complete factorial design experiment that manipulated root carbon source and sink strengths. Carbon source strength to roots was manipulated through foliar scorching, carbon sink strength in roots was altered via nitrogen fertilization, and carbon transfer from roots to the soil organic matter pool was impacted using a general soil pesticide to distinguish between root mortality via herbivory and senescence. Fertilization significantly increased fine root nitrogen concentrations and mortality rates in the nonscorched plots across the last four sample intervals. Scorching significantly reduced fine root biomass. The influence of soil herbivores on fine root carbon allocation and fates could not be assessed in this study because the soil pesticide had no measurable effect on herbivorous nematode and insect larvae populations. The results of this study suggest that nitrogen increases fine root mortality via an increase in fine root carbon sink strength rather than a decrease in carbon allocation to fine roots. These findings support the constant allocation hypothesis regarding nitrogen controls on fine root carbon allocation and transfers in forest ecosystems. FOR. SCI. 50(2):177–187.

Genome mosaicism is conserved but not unique in Pseudomonas aeruginosa isolates from the airways of young children with cystic fibrosis - Robert K. Ernst; David A. D′Argenio; Jeffrey K. Ichikawa; M. Gita Bangera; Sara Selgrade; Jane L. Burns; Peter Hiatt; Karen McCoy; Mitchell Brittnacher; Arnold Kas; David H. Spencer; Maynard V. Olson; et al. (Environmental Microbiology, 2003)
Summary Pseudomonas aeruginosa strains from the chronic lung infections of cystic fibrosis (CF) patients are phenotypically and genotypically diverse. Using strain PAO1 whole genome DNA microarrays, we assessed the genomic variation in P. aeruginosa strains isolated from young children with CF (6 months to 8 years of age) as well as from the environment. Eighty‐nine to 97% of the PAO1 open reading frames were detected in 20 strains by microarray analysis, while subsets of 38 gene islands were absent or divergent. No specific pattern of genome mosaicism defined strains associated with CF. Many mosaic regions were distinguished by their low G + C content; their inclusion of phage related or pyocin genes; or by their linkage to a vgr gene or a tRNA gene. Microarray and phenotypic analysis of sequential isolates from individual patients revealed two deletions of greater than 100 kbp formed during evolution in the lung. The gene loss in these sequential isolates raises the possibility that acquisition of pyomelanin production and loss of pyoverdin uptake each may be of adaptive significance. Further characterization of P. aeruginosa diversity within the airways of individual CF patients may reveal common adaptations, perhaps mediated by gene loss, that suggest new opportunities for therapy.

Phylogeny, biogeography and adaptive radiation of Pachycladon (Brassicaceae) in the mountains of South Island, New Zealand - P. B. Heenan; A. D. Mitchell (Journal of Biogeography, 2003)
Aim To report analyses and propose hypotheses of adaptive radiation that explain distributional patterns of the alpine genus Pachycladon Hook.f. – a morphologically diverse genus from New Zealand closely related to Arabidopsis thaliana . Location South Island, New Zealand. Methods Morphological and nrDNA ITS sequence phylogenies were generated for Pachycladon . An analysis is presented of species distributional patterns and attributes. Results Phylogenetic analyses of morphological characters and nrDNA ITS sequence data were found to be congruent in supporting three New Zealand clades for Pachycladon . Monophyletic groups identified within the genus are geographically distinct and are associated with different geological parent materials. Distribution maps, latitude and altitude range, and data on geological parent material are presented for the nine named and one unnamed species of Pachycladon from New Zealand. Main conclusions (a) Panbiogeographic hypotheses accounting for the origin and present‐day distribution of Pachycladon in New Zealand are not supported. (b) Species diversity and distributions of Pachycladon are explained by a Late Tertiary–Quaternary adaptive radiation associated with increasing specialization to geological substrates. Pachycladon cheesemanii Heenan & A.D.Mitch. is morphologically similar to the closest overseas relatives. It is a geological generalist and has wide latitudinal and altitudinal ranges, and we suggest it resembles the ancestral form of the genus in New Zealand. Pachycladon novae‐zelandiae (Hook.f.) Hook.f. and P. wallii (Carse) Heenan & A.D.Mitch. are a southern South Island group that predominantly occurs on Haast Schist, are polycarpic, have lobed leaves, and lateral inflorescences. Pachycladon enysii (Cheeseman) Heenan & A.D.Mitch., P. fastigiata (Hook.f.) Heenan & A.D.Mitch., and P. stellata (Allan) Heenan & A.D.Mitch. are restricted to greywacke in the eastern South Island, and are facultatively monocarpic, have serrate leaves, and stout terminal inflorescenes. (c) Present distributions of Pachycladon species may relate to Pleistocene climate change. Pachycladon enysii reaches the highest altitude of New Zealand species of Pachycladon and is most common in the Southern Alps in Canterbury. We propose that this species survived on nunataks at the height of the last glaciation. In contrast, P. fastigiata grows at a lower altitude and is absent from the high mountains of the Southern Alps. We suggest it was extirpated from this area during the last glaciation.

Light Transmittance Estimates in a Longleaf Pine Woodland - Michael A. Battaglia; Robert J. Mitchell; Paul P. Mou; Stephen D. Pecot (Forest Science, 2003)
While the importance of canopy structure in open woodlands and savannas on regulating the flow of energy and matter is well known, few studies have investigated how variation in overstory abundance influences canopy light transmission and the extent that estimates vary in their ability to characterize the light environment in these ecosystems. Canopy light transmittance (% photosynthetic photon flux density, or %PPFD) was measured with gallium arsenide phosphide (GaAsP) photodiodes and was monitored throughout the growing season in an open-canopy longleaf pine (Pinus palustris Mill.) woodland across an overstory abundance gradient. Several estimates of canopy light transmittance were also measured, including 10 minute averages of %PPFD under clear and overcast sky conditions during summer, fall, and winter, as well as light estimates derived from hemispherical photographs (gap fraction, GF: gap light index, GLI; and weighted canopy openness, WCO). Linear and curvilinear regression were used to analyze the relationship between (1) light measurements and canopy structure and (2) light estimates and growing-season % PPFD measured by light diodes. Of all light measurements in this study, ten-minute average % PPFD measurements during clear days were the most variable: only a small proportion in the 10-minute average of light reaching the understory was correlated to either overstory structure or growing-season canopy transmittance. While measures on overcast days improved the correlations, they tended to overestimate transmittance. Gap fraction (GF) and gap light index (GLI) were strongly correlated with % PPFD and overstory structure, and the relationship between GLI and % PPFD was improved by using a direct light setting of 60%. In addition to strong correlation, hemispherical photographic estimates of light fell along a 1:1 line with % growing-season PPFD; thus, estimates were relatively unbiased. Measures of light in this ecosystem need to incorporate the large spatial and temporal variation in light transmittance that is characteristic of this ecosystem if investigators are to understand the relationship between open-canopy woodlands and their light environments.

Pattern Scaling: An Examination of the Accuracy of the Technique for Describing Future Climates - Timothy D. Mitchell (Climatic Change, 2003)

New records of Australian Myxomycota - R. McHugh; S. L. Stephenson; D. W. Mitchell; M. H. Brims (New Zealand Journal of Botany, 2003)
Twenty‐eight species of myxomycetes and other related organisms not previously known to occur in Australia are reported along with 78 new state records. Records were obtained from collections made in the field and from moist chamber cultures prepared with samples of various types of organic material known to support the growth of myxomycetes. The majority of these samples consisted of bark from living trees and shrubs but some samples of litter, both ground and aerial, and dung also were collected. Physarum crateriforme var. columellatum comb. et stat. nov. is proposed as a new name. The number of species recorded from the continent now stands at 177, which represents approximately 20% of the total number of world species.

Common actions of adenosine receptor agonists in modulating human trabecular meshwork cell transport - J. C. Fleischhauer; C. H. Mitchell; W. D. Stamer; M. O. Karl; K. Peterson-Yantorno; M. M. Civan (The Journal of Membrane Biology, 2003)

Anthropogenic climate change for 1860 to 2100 simulated with the HadCM3 model under updated emissions scenarios - T. C. Johns; J. M. Gregory; W. J. Ingram; C. E. Johnson; A. Jones; J. A. Lowe; J. F. B. Mitchell; D. L. Roberts; D. M. H. Sexton; D. S. Stevenson; S. F. B. Tett; M. J. Woodage (Climate Dynamics, 2003)

Surprisingly minor influence of TRAV11 (Vα14) polymorphism on NK T-receptor mCD1/α-galactosylceramide binding kinetics - Bee-Cheng Sim; Kaisa Holmberg; Stephane Sidobre; Olga Naidenko; Nathalie Niederberger; Shane D. Marine; Mitchell Kronenberg; Nicholas R. J. Gascoigne (Immunogenetics, 2003)

Characterisation of the expression of a novel constitutive maize promoter in transgenic wheat and maize - S. Rasco-Gaunt; D. Liu; C. Li; A. Doherty; K. Hagemann; A. Riley; T. Thompson; C. Brunkan; M. Mitchell; K. Lowe; E. Krebbers; P. Lazzeri; et al. (Plant Cell Reports, 2003)

Molecular systematics of the New Zealand Pachycladon (Brassicaceae) complex: Generic circumscription and relationships to Arabidopsis sens. lat. and Arabis sens. lat. - P. B. Heenan; A. D. Mitchell; M. Koch (New Zealand Journal of Botany, 2002)
Nuclear ribosomal DNA ITS sequence data were used to assess the relationships of Cheesemania, Ischnocarpus, and Pachycladon to each other and to other genera in the Brassicaceae. Phylogenetic analyses are congruent with other studies that infer the Pachycladon complex (including Pachycladon, Cheesemania, and Ischnocarpus) is monophyletic. The complex occurs within an Arabidopsoid clade that includes Arabidopsis and the recently recognised segregate genera Beringia, Crucihimalaya, Olimarabidopsis, and Pseudoarabidopsis, and the Arabis segregates Boechera and Turritis. The Pachycladon complex is sister to Beringia and Crucihimalaya, and forms a distinct New Zealand lineage. Molecular clock estimates suggest the Pachycladon complex diverged from its nearest relatives between 1.0 and 3.5 million years ago. The close relationship of Cheesemania, Ischnocarpus, and Pachycladon is reflected in low ( Pachycladon to include species placed in Cheesemania and Ischnocarpus. New combinations are made in Pachycladon for species previously placed in Cheesemania and Ischnocarpus. A new name, P. cheesemanii, is presented for Ischnocarpus novae‐zelandiae as that species epithet is preoccupied in Pachycladon.

Effects of nitric oxide synthase inhibitors on the febrile response to muramyl dipeptide and lipopolysaccharide in rats - Kamerman P.; Mitchell D.; Laburn H. (Journal of Comparative Physiology B, 2002)

Melting experiments on SiO 2 -rich lamproites to 6.4 GPa and their bearing on the sources of lamproite magmas - R. H. Mitchell; A. D. Edgar (Mineralogy and Petrology, 2002)

Production of Australian freshwater crayfish in earthen-based systems using pelleted diets and forage crops as food - Paul L. Jones; Jose R. Chavez; Brad D. Mitchell (Aquaculture International, 2002)

Molecular characterization of a novel recombinant strain of human astrovirus associated with gastroenteritis in children - J. E. Walter; J. Briggs; M. L. Guerrero; D. O. Matson; L. K. Pickering; G. Ruiz-Palacios; T. Berke; D. K. Mitchell (Archives of Virology, 2001)

Relative Base Excision Repair in Xiphophorus Fish Tissue Extracts - Ronald B. Walter; Huang-Mo Sung; Rebecca D. Obermoeller; David L. Mitchell; Gabriel W. Intano; Christi A. Walter (Marine Biotechnology, 2001)

Ozone Profile Retrieval from Satellite Observation Using High Spectral Resolution Infrared Sounding Instrument - Yanni Qu; Mitchell D. Goldberg; Murty Divakarla (Advances in Atmospheric Sciences, 2001)

The impact of dynamic sea-ice on the climatology and climate sensitivity of a GCM: a study of past, present, and future climates - C. D. Hewitt; C. A. Senior; J. F. B. Mitchell (Climate Dynamics, 2001)

DNA markers for Fusarium head blight resistance QTLs in two wheat populations - J. A. Anderson; R. W. Stack; S. Liu; B. L. Waldron; A. D. Fjeld; C. Coyne; B. Moreno-Sevilla; J. Mitchell Fetch; Q. J. Song; P. B. Cregan; R. C. Frohberg (Theoretical and Applied Genetics, 2001)

Risedronate Pharmacokinetics and Intra- and Inter-Subject Variability Upon Single-Dose Intravenous and Oral Administration - David Y. Mitchell; William H. Barr; Rachelle A. Eusebio; Karen A. Pallone Stevens; Frank P. Duke; Darrell A. Russell; John D. Nesbitt; James H. Powell; Gary A. Thompson (Pharmaceutical Research, 2001)

Associations between smoking and adenocarcinomas and squamous cell carcinomas of the uterine cervix (United States) - James V. Lacey; Morten Frisch; Louise A. Brinton; Fouad M. Abbas; Willard A. Barnes; Patti E. Gravitt; Mitchell D. Greenberg; Sarah M. Greene; Olympia C. Hadjimichael; Larry McGowan; Rodrigue Mortel; Peter E. Schwartz; et al. (Cancer Causes & Control, 2001)

The effect of crop residue incorporation date on soil inorganic nitrogen, nitrate leaching and nitrogen mineralization - R. D. J. Mitchell; R. Harrison; K. J. Russell; J. Webb (Biology and Fertility of Soils, 2000)

Damage to grass shrimp ( Palaemonetes pugio ) embryo DNA by summer sunlight followed by DNA repair in the dark - G. B. Kim; R. F. Lee; D. L. Mitchell (Marine Biology, 2000)

The dopamine D3/2 agonist 7-OH-DPAT attenuates the development of morphine tolerance but not physical dependence in rats - Charles D. Cook; Andrew C. Barrett; Chockeo Syvanthong; Mitchell J. Picker (Psychopharmacology, 2000)

Modulatory effects of dopamine D3/2 agonists on kappa opioid-induced antinociception and diuresis in the rat - Charles D. Cook; Andrew C. Barrett; Chockeo Syvanthong; Mitchell J. Picker (Psychopharmacology, 2000)

Phylogeny and biogeography of the Chilean pseudopanax laetevirens - Anthony D. Mitchell; Steven J. Wagstaff (New Zealand Journal of Botany, 2000)
Nuclear ribosomal DNA sequences are used in phylogenetic analyses to assess relationships of the Chilean Pseudopanax laetevirens. Close relatives of P. laetevirens are P. gunnii, an endemic to Tasmania, Raukaua species from New Zealand, and Cheirodendron tryginum from Hawai'i. Analyses suggest that P. laetevirens is the sister species to P. gunnii. The current distribution of these taxa may be consistent with the movement of continental plates during the late Eocene or early Miocene. Cheirodendron may have had a southern origin and be the result Of long distance dispersa1 to the northwest.

α-Keto acid elongation and glucosinolate biosynthesis in Arabidopsis thaliana - H. Campos de Quiros; R. Magrath; D. McCallum; J. Kroymann; D. Scnabelrauch; T. Mitchell-Olds; R. Mithen (Theoretical and Applied Genetics, 2000)

Sex-related differences in the antinociceptive effects of opioids: importance of rat genotype, nociceptive stimulus intensity, and efficacy at the µ opioid receptor - Charles D. Cook; Andrew C. Barrett; Emily L. Roach; Joseph R. Bowman; Mitchell J. Picker (Psychopharmacology, 2000)

The effects of in situ drying on sediment–phosphate interactions in sediments from an old wetland - D. S. Baldwin; A. M. Mitchell; G. N. Rees (Hydrobiologia, 2000)

Investigating Climate Change Impacts and Thresholds: An Application of the CLIMPACTS Integrated Assessment Model for New Zealand Agriculture - G. J. Kenny; R. A. Warrick; B. D. Campbell; G. C. Sims; M. Camilleri; P. D. Jamieson; N. D. Mitchell; H. G. McPherson; M. J. Salinger (Climatic Change, 2000)

Estimation of the absorption and backscattering coefficients from inߚwater radiometric measurements - Malgorzata Stramska; Dariusz Stramski; B. Greg Mitchell; Curtis D. Mobley (Limnology and Oceanography, 2000)
Numerical simulations of radiative transfer within the ocean surface mixed layer have been used to derive a set of simple equations for estimating the absorption, a, and backscattering, b b , coefficients in the blue‐green spectral region from measurements of downwelling irradiance, E d , upwelling irradiance, E u , and upwelling nadir radiance, L u . Two relationships are used in this derivation: (i) irradiance reflectance, R = E u /E d , is approximately proportional to b b /a and inversely proportional to the average cosine of the underwater light field, µ; and (ii) radiance reflectance, R L = L u /E d , is proportional to b b /a but changes little with µ. Accordingly, µ is first estimated from L u /E u and then the absorption coefficient is obtained from Gershun's equation. Having determined a, b b is estimated from the relation between R L and b b /a. We also show how the estimation of µ, a, and b b is improved with additional data of the beam attenuation coefficient, c. The retrieval of a and b b from E d , E u , and L u has been tested using field data collected in the Southern California Bight. The a values predicted by the model show good agreement with absorption determinations from the ac‐9 instrument and on‐board spectrophotometric method, and the modeled b b agrees well with the backscattering determinations from the Hydroscat‐6 instrument. The algorithm has been derived for a broad range of the ocean inherent optical properties that do not necessarily covary with one another like in chlorophyll‐based bio‐optical models. However, the model should be used with caution if significant departure from the average Petzold particle scattering phase function is expected, for example in waters with high load of mineral particles.

Non-thermal signals govern selective brain cooling in pigs - A. Fuller; G. Mitchell; D. Mitchell (Journal of Comparative Physiology B, 1999)

Species of Agaricus occurring in New Zealand - A. D. Mitchell; M. Walter (New Zealand Journal of Botany, 1999)
A key is provided for 21 species occurring in New Zealand: Agaricus arvensis,A. augustus, A. bambusae var. australis, A. bernardii, A. bisporus var. bisporus, A. bitorquis, A. campestris var. campestris, A. campestris cf. var. floccipes, A. cupreobrunneus, A. horakii, A. impudicus (= A. variegans ) ,A. lanatoniger, A. lanipes,A. meleagris, A. oligocystis, A. porphyrocephalus, A. purpureoniger, A. semotus, A. subperonatus, A. viridopurpurascens , and A. xanthoderma . Full descriptions are given for those taxa encountered by the authors in the field, including 10 species which are considered cosmoplitan in distribution. Six of these species are new records for New Zealand.

Brain, abdominal and arterial blood temperatures of free-ranging eland in their natural habitat - A. Fuller; D.G. Moss; J.D. Skinner; P.T. Jessen; G. Mitchell; D. Mitchell (Pflügers Archiv - European Journal of Physiology, 1999)

Brain, abdominal and arterial blood temperatures of free-ranging eland in their natural habitat - A. Fuller; D.G. Moss; J.D. Skinner; P.T. Jessen; G. Mitchell; D. Mitchell (Pflügers Archiv - European Journal of Physiology, 1999)

Molecular characterization of radiation- and chemically induced mutations associated with neuromuscular tremors, runting, juvenile lethality, and sperm defects in jdf2 mice - Mitchell Walkowicz; Yonggang Ji; Xiaojia Ren; Bernhard Horsthemke; Liane B. Russell; Dabney Johnson; Eugene M. Rinchik; Robert D. Nicholls; Lisa Stubbs (Mammalian Genome, 1999)

Effects of plant species richness on invasion dynamics, disease outbreaks, insect abundances and diversity - J.M.H. Knops; D. Tilman; N.M. Haddad; S. Naeem; C.E. Mitchell; J. Haarstad; M.E. Ritchie; K.M. Howe; P.B. Reich; E. Siemann; J. Groth (Ecology Letters, 1999)
Declining biodiversity represents one of the most dramatic and irreversible aspects of anthropogenic global change, yet the ecological implications of this change are poorly understood. Recent studies have shown that biodiversity loss of basal species, such as autotrophs or plants, affects fundamental ecosystem processes such as nutrient dynamics and autotrophic production. Ecological theory predicts that changes induced by the loss of biodiversity at the base of an ecosystem should impact the entire system. Here we show that experimental reductions in grassland plant richness increase ecosystem vulnerability to invasions by plant species, enhance the spread of plant fungal diseases, and alter the richness and structure of insect communities. These results suggest that the loss of basal species may have profound effects on the integrity and functioning of ecosystems.

Body Temperature Changes in Free-ranging Baboons (Papio hamadryas ursinus) in the Namib Desert, Namibia - C. Brain; D. Mitchell (International Journal of Primatology, 1999)

Selective attenuation of the antinociceptive effects of μ opioids by the putative dopamine D 3 agonist 7-OH-DPAT - C. D. Cook; J. S. Rodefer; Mitchell J. Picker (Psychopharmacology, 1999)

Evolution of Stilbocarpa , a megaherb from New Zealand's sub‐antarctic islands - Anthony D. Mitchell; Colin D. Meurk; Steven J. Wagstaff (New Zealand Journal of Botany, 1999)
Challenges to the traditional circumscription of Apiaceae and Araliaceae are emerging as a result of phylogenetic analysis of DNA sequences. Traditionally classified as Araliaceae, Stilbocarpa emerges with Schizeilema and Azorella , both members of the Apiaceae. In our analyses of nuclear ITS sequences, these three genera comprise a distinct Southern Hemisphere lineage. The humid climate, cool equable temperatures, locally abundant nutrients, and absence of herbivores are ecological features of the sub‐antarctic islands that may have contributed to the evolution of the unusual megaherb, Stilbocarpa , from these diminutive apiaceous ancestors.

Uncertainty Analysis of Regional Mercury Exposure - C. Seigneur; K. Lohman; P. Pai; K. Heim; D. Mitchell; L. Levin (Water, Air, & Soil Pollution, 1999)

The effects of sediment desiccation on the potential for nitrification, denitrification, and methanogenesis in an Australian reservoir - A. M. Mitchell; D. S. Baldwin (Hydrobiologia, 1999)

Electroporation-mediated transient gene expression in intact cells of sweetpotato - Tonya D. Mitchell; Ajmer S. Bhagsari; Peggy Ozias-Akins; Sarwan K. Dhir (In Vitro Cellular & Developmental Biology - Plant, 1998)

Variant in sulfonylurea receptor-1 gene is associated with high insulin concentrations in non-diabetic Mexican Americans: SUR-1 gene variant and hyperinsulinemia - Denise L. Goksel; Kathryn Fischbach; Ravindranath Duggirala; Braxton D. Mitchell; Lydia Aguilar-Bryan; John Blangero; M. P. Stern; Peter O’Connell (Human Genetics, 1998)

Phylogenetic relationships of species of Gingidia and related genera (Apiaceae, subfamily Apioideae) - A. D. Mitchell; C. J. Webb; S. J. Wagstaff (New Zealand Journal of Botany, 1998)
Five genera of Australasian apioid Apiaceae (Gingidia, Scandia, Lignocarpa, Anisotome, and Aciphylla) have a complex taxo‐nomic history with the circumscription of, and inferred relationships among, the currently accepted genera based on only morphological characters. This molecular and phylogenetic study focuses on the relationships among the taxa currently included within Gingidia using the other genera as outgroups. Phylogenetic analyses of nuclear ribosomal DNA internal transcribed spacer region sequences for 17 species from these genera, and comparison with Smyrnium to root the trees, indicate that Gingidia is polyphyletic as currently circumscribed, the species belonging in two distinct monophyletic groups. However, morphological characters do not support these two groups, making taxonomic interpretation difficult. The monophyletic G. montana group includes the ditypic endemic genera Scandia and Lignocarpa, suggesting that they should not be maintained. The second monophyletic group includes G. decipiens and G. flabellata with species of Anisotome. Although our sampling of Anisotome and Aciphylla is limited, nothing in the analysis of the molecular data is inconsistent with earlier suggestions, based on morphological data, that Gingidia, Scandia, Lignocarpa, Anisotome, and Aciphylla form a monophyletic group.

Chloral hydrate alters the organization of the ciliary basal apparatus and cell organelles in sea urchin embryos - Amitabha Chakrabarti; H. Schatten; Kirk D. Mitchell; Michael Crosser; Meghan Taylor (Cell and Tissue Research, 1998)

Effects of desiccation/oxidation on the potential for bacterially mediated P release from sediments - A. Mitchell; D. S. Baldwin (Limnology and Oceanography, 1998)
The effect of desiccation/oxidation on the potential for phosphorus release from reservoir sediments under anoxic conditions was studied. When sediments were exposed to the air and subsequently dried, their ability to release P under anaerobic conditions was severely limited relative to sediments that were not exposed. Anaerobic P release in response to the addition of a toxicant (formaldehyde), bioavailable carbon sources (acetate or glucose), available sulfur (sulfate), and sulfide were used to infer possible causes for the decrease in anaerobic P release as a function of desiccation/oxidation. A substantial reduction in P release occurred in sediments that had not been exposed when formaldehyde was added. This suggests that anaerobic P release may be microbially driven. Addition of acetate and sulfate slightly enhanced P release from nondesiccated sediments, suggesting some C and(or) S limitation of the bacterial processes occurring in these sediments. Substantial P was released when sulfide was added to the nonexposed sediments, indicating that there is a significant amount of P associated with sulfide‐reducible minerals (e.g. iron oxyhydroxides). Sulfide addition to exposed sediments released only about one‐fourth of the P compared with nonexposed sediments. Furthermore, no additional P was released when sulfate was added to exposed sediments, but P was released in the presence of either glucose or acetate. Together these results indicate that the decrease in potential for P release from exposed sediments was caused by a shift in bacterial community structure (specifically the loss of viable sulfate‐reducing bacteria), carbon limitation as a result of drying, and aging of minerals with which P is associated.

Dopaminergic activity and the discriminative stimulus effects of mu opioids in pigeons: importance of training dose and attenuation by the D 3 agonist (±)-7-OH-DPAT - C. D. Cook; Mitchell J. Picker (Psychopharmacology, 1998)

DNA damage induced by ultraviolet radiation in coral-reef microbial communities - M. M. Lyons; P. Aas; J. D. Pakulski; L. Van Waasbergen; R. V. Miller; D. L. Mitchell; W. H. Jeffrey (Marine Biology, 1998)

Risedronate Gastrointestinal Absorption Is Independent of Site and Rate of Administration - David Y. Mitchell; Rachelle A. Eusebio; Lisa E. Dunlap; Karen A. Pallone; John D. Nesbitt; Darrell A. Russell; Marian E. Clay; Pirow J. Bekker (Pharmaceutical Research, 1998)

Peanut yellow spot virus is a member of a new serogroup of Tospovirus genus based on small (S) RNA sequence and organization - T. Satyanarayana; S. Gowda; K. Lakshminarayana Reddy; S. E. Mitchell; W. O. Dawson; D. V. R. Reddy (Archives of Virology, 1998)

TRP64ARG β3-adrenergic receptor and obesity in Mexican Americans - K. Silver; Braxton D. Mitchell; Jeremy Walston; J. D. Sorkin; Michael P. Stern; Jesse Roth; A. R. Shuldiner (Human Genetics, 1997)

Radiative forcing and response of a GCM to ice age boundary conditions: cloud feedback and climate sensitivity - C. D. Hewitt; J. F. B. Mitchell (Climate Dynamics, 1997)

Reinstatement of Raukaua , a genus of the Araliaceae centred in New Zealand - A. D. Mitchell; D. G. Frodin; M. J. Heads (New Zealand Journal of Botany, 1997)
The genus Pseudopanax is recognised as polyphyletic. Morphological and anatomical characters are described that support the monophyly of Pseudopanax anomalus , P. edgerleyi , and P. simplex . Reinstatement of the genus Raukaua is recommended to accommodate these species. The new combinations R. anomalus and R. simplex are made.

Detection of chromosomal aneuploidy in endometriosis by multi-color fluorescence in situ hybridization (FISH) - Jong-Chul Shin; Helen L. Ross; Sherman Elias; Dianne D. Nguyen; Dorothy Mitchell-Leef; Joe Leigh Simpson; F. Z. Bischoff (Human Genetics, 1997)

Probabilistic assessment of regional mercury exposure - C. Seigneur; P. Pai; M. Gerath; D. Mitchell; G. Hamby; G. Gong; C. Whipple; L. Levin (Water, Air, & Soil Pollution, 1997)

Probabilistic Assessment of Regional Mercury Exposure - C. Seigneur; P. Pai; M. Gerath; D. Mitchell; G. Hamby; G. Gong; C. Whipple; L. Levin (Water, Air, & Soil Pollution, 1997)

Northern Bobwhite Egg Hatchability and Chick Immunocompetence Following a Field Application of Clopyralid - C. B. Dabbert; R. B. Mitchell; D. T. Oberheu (Bulletin of Environmental Contamination and Toxicology, 1997)

Phylogenetic relationships ofPseudopanax species (Araliaceae) inferred from parsimony analysis of rDNA sequence data and morphology - A. D. Mitchell; S. J. Wagstaff (Plant Systematics and Evolution, 1997)

The effect of dietary protein source on growth and carcass composition in juvenile Australian freshwater crayfish - Paul L. Jones; Sena S. De Silva; Brad D. Mitchell (Aquaculture International, 1996)

Effects of replacement of animal protein by soybean meal on growth and carcass composition in juvenile Australian freshwater crayfish - Paul L. Jones; Sena S. De Silva; Brad D. Mitchell (Aquaculture International, 1996)

SUMMER MOISTURE AVAILABILITY OVER EUROPE IN THE HADLEY CENTRE GENERAL CIRCULATION MODEL BASED ON THE PALMER DROUGHT SEVERITY INDEX - P. D. JONES; M. HULME; K. R. BRIFFA; C. G. JONES; J. F. B. MITCHELL; J. M. MURPHY (International Journal of Climatology, 1996)

Peanut bud necrosis tospovirus S RNA: complete nucleotide sequence, genome organization and homology to other tospoviruses - T. Satyanarayana; S. E. Mitchell; D. V. R. Reddy; S. Brown; S. Kresovich; R. Jarret; R. A. Naidu; J. W. Demski (Archives of Virology, 1996)

Genetic instability in Streptomyces niveus plasmid pSN2: in vivo formation of deletion derivatives - H. A. Hussain; J. I. Mitchell; D. A. Ritchie (Archives of Microbiology, 1990)

Organochlorine pesticide, polychlorobiphenyl, and mercury residues in bald eagle eggs?1969?79?and their relationships to shell thinning and reproduction - Stanley N. Wiemeyer; Thair G. Lamont; Christine M. Bunck; Charles R. Sindelar; Francis J. Gramlich; James D. Fraser; Mitchell A. Byrd (Archives of Environmental Contamination and Toxicology, 1984)

Lymphocytotoxic and microbial antibodies in Crohn's disease and matched controls - D. Gump; E. Caul; O. Eade; H. Greenberg; A. Kapikian; B. MacPherson; P. Mitchell; K. Parent; S. Richmond; W. Beeken (Antonie van Leeuwenhoek, 1981)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Phenol oxidase activation in Drosophila: A cascade of reactions - William D. Seybold; Paul S. Meltzer; Herschel K. Mitchell (Biochemical Genetics, 1975)

Physiological and DNA characterization of Candida maltosa, a hydrocarbon-utilizing yeast - S. A. Meyer; K. Anderson; R. E. Brown; M. Th. Smith; D. Yarrow; G. Mitchell; D. G. Ahearn (Archives of Microbiology, 1975)

Sectional notes - L. M. Ware; Geo D. Ruehle; J. G. Richard; J. C. Campbell; E. V. Hardenbueg; C. A. Henderson; Robert Schmidt; J. Mitchell Jenkins; John Noonan (American Journal of Potato Research, 1941)

Sectional notes - E. Marx; B. A. Brown; Frank W. Hussey; Marx Koehnke; E. V. Hardenburg; Robert Schmidt; Earl B. Tussing; Mitchell Jenkins; John Noonan; H. L. Bailey; Chas D. Gaines (American Journal of Potato Research, 1940)